Toward more meaningful “top–bottom” paleolimnological assessments: evaluation of a Canada-wide lacustrine sedimentation rate map using LakePulse data - Neal Michelutti; Alexandre Baud; Carsten Meyer-Jacob; Adam Jeziorski; Irene Gregory-Eaves; John P. Smol (Journal of Paleolimnology, 2026)

Circulating metabolites and fatty acids associated with ultra-processed food consumption: results from the EPIC study - Jessica Blanco-Lopez; Sahar Yammine; Joseph A. Rothwell; Mathilde His; Carine Biessy; Pekka Keski-Rahkonen; Bernadette Chimera; Inarie Jacobs; Aline Al Nahas; Emine Koc Cakmak; Oliver Robinson; Fernanda Morales Berstein; et al. (Critical Reviews in Food Science and Nutrition, 2026)

A scalable P2P energy trading platform with automated bidding using blockchain: Detailed implementation and pilot study in India - Vivek Mohan; Jacob P. Varghese; Anith Krishnan; Dhanesh Haridas; Karthik Thirumala; Martin Scherfler (The Electricity Journal, 2026)

Understanding the importance of social and environmental stressors in predicting maternal sleep quality during late pregnancy - Xiaoran Yang; Sandrah P. Eckel; Yuhong Hu; Yan Xu; Roxana Khalili; Aviva Wolf-Jacobs; Tingyu Yang; Xinci Chen; Brendan Grubbs; Laila Al-Marayati; Claudia M. Toledo-Corral; Jill Johnston; et al. (Environmental Research, 2026)

Measuring the electrical charge and settling velocity of volcanic ash with a new, cost-effective apparatus (VoltAsh) both in the laboratory and in the field - Allan Fries; Eduardo Rossi; Jonathan P. Merrison; Jens Jacob Iversen; Tatsushi Matsuyama; Frédéric Arlaud; Jonathan Lemus; Simon Thivet; Carolina Diaz-Vecino; Riccardo Simionato; Costanza Bonadonna (Bulletin of Volcanology, 2026)
Electrical charges play a key role in particle-particle interactions during transport and deposition of volcanic ash with significant impact on their atmospheric residence time, as they can influence aggregation processes. Nonetheless, direct field measurements are rare due to logistic challenges, resulting in a very limited understanding of charge generation and aggregation mechanisms. This study introduces VoltAsh, a cost-effective, portable device for measuring the charge and velocity of settling volcanic ash particles using a Through-Type Faraday Cage (TTFC) and a charge amplifier circuit. Laboratory validation confirmed the accuracy of both charge and velocity measurements when compared with state-of-the-art techniques. Field deployments at Sakurajima volcano (Japan) in November 2023 enabled automated, semi-continuous measurements over several hours, detecting particle charges ranging from 0.5 to 250 pC and velocities up to 5 ms $$^{-1}$$ - 1 . Measurements at Etna volcano (Italy) in July 2024 detected fewer charged particles, likely due to differences in eruptive style, grain size, particle properties and atmospheric conditions. These findings highlight VoltAsh’s potential for advancing studies of volcanic ash transport and deposition processes.

Comparison of texture perception and acceptance using drinkable yogurts among three ethnic groups: Hispanic or Latino, Korean, and White or Caucasian in US - Jihye An; Michelle D Hayden; Linda S. Barahona-Dominguez; Ainsley P. Jessup; Jacob C. Dees; Sungeun Cho (International Dairy Journal, 2026)

Gibbsite solubility and aluminum speciation in alkaline nuclear waste containing nitrate, nitrite, and phosphate - Trent R. Graham; Ashley R. Kennedy; Winnie Liu; Daria V. Boglaienko; Robert G. Felsted; Jacob G. Morton; Micah P. Prange; Mark E. Bowden; Teresa L. Lemmon; Marie S. Swita; Hsiu-Wen Wang; Michael D. Britton; et al. (Chemical Engineering Journal, 2026)

Correction: Quantitative Mineral Resource Assessment of Lithium Pegmatite Deposits in the Northern Appalachian Orogen, USA - Niki E. Wintzer; Christopher S. Holm-Denoma; Jacob E. Poletti; Dalton M. McCaffrey; Stanley P. Mordensky; Erik R. Tharalson; Collin Cronkite-Ratcliff (Natural Resources Research, 2026)

Quantitative Mineral Resource Assessment of Lithium Pegmatite Deposits in the Northern Appalachian Orogen, USA - Niki E. Wintzer; Christopher S. Holm-Denoma; Jacob E. Poletti; Dalton M. McCaffrey; Stanley P. Mordensky; Erik R. Tharalson; Collin Cronkite-Ratcliff (Natural Resources Research, 2026)
Lithium demand is projected to increase more than 48 times by 2040 due to electric vehicle production and other energy storage needs. Most lithium production is outside of the USA, thereby increasing supply chain vulnerability. The combined end use importance and heightened supply risk of lithium make this lightest metallic element a critical commodity to the USA. To mitigate this supply risk, the US Geological Survey is actively assessing lithium deposits in the USA. Herein, we detail an assessment for lithium-mineralized pegmatites in the US northern Appalachian Mountains. Permissive tracts were generated by cross-referencing tectonic and geologic maps and mineral occurrence data with mappable criteria derived from generalized and region-specific lithium pegmatite ore deposit models; tracts were then ranked as having high, medium, or low permissibility. Available geophysical and geochemical data were found to be of minimal utility for this deposit type at the scale of the assessment. The number of undiscovered deposits were estimated and integrated into probabilistic simulations, which included an expanded and updated global grade and tonnage model of pegmatite-hosted lithium ore. The estimated total amount of undiscovered resources for the northern Appalachian Orogen has a median value of 1,410,000 metric tons of Li 2 O when considering moderate correlation across sub-regions. At a confidence level of 90%, a resource of at least 90,000 metric tons of Li 2 O remains undiscovered, and at a 10% confidence level, a resource of as much as 7,380,000 metric tons Li 2 O remains undiscovered. After applying an up-to-date economic filter to convert median contained lithium to recoverable material, a correlated total of 900,000 metric tons of Li 2 O may be economically extractable, equating to enough Li 2 O to provide the current annual US lithium supply deficit (presently obtained through net imports) for 127 years at 2025 rates of apparent consumption. This period of provision will inevitably shorten with projected increasing consumption rates, emphasizing that further research could be completed to better delineate regions of high lithium resource potential and support exploration and domestic production.

Dune Russet: A French-Fry Potato Cultivar with High Specific Gravity under High-Temperature Growing Conditions and Excellent Processing Quality after Long-Term Cold Storage - M. Isabel Vales; Douglas C. Scheuring; Jeffrey W. Koym; Jeewan Pandey; Stephany E. Toinga-Villafuerte; Joshua R. Johnson; Caroline P. Gray; David G. Holm; Mohamad Chikh-Ali; Robert G. Wilson; Richard G. Novy; Jonathan L. Whitworth; et al. (American Journal of Potato Research, 2026)
Dune Russet (COTX08063-2Ru) is the first French fry russet potato cultivar released by the Texas A&M Potato Breeding Program. It derives from a cross made by the Colorado State University Potato Program between Premier Russet and A99073-1 and was subsequently selected and advanced by the Texas Program. Dune Russet has oblong potato tubers with light russet skin texture and white flesh. It is characterized by having excellent French fry quality and cold-induced sweetening resistance, producing light-colored fries directly from the field and even after several months (three to eight) in cold storage at 4.4 °C. Dune Russet is especially recommended for areas that experience high-temperature stress during the growing season, as it can retain high specific gravity near 1.090 and produce light French fries despite heat stress. Across multi-location trials, Dune Russet outperformed the reference cultivar, Russet Burbank, and other processing cultivars in French fry quality, while offering some field-based PVY tolerance and good agronomic performance, including competitive marketable yields and a high proportion of US No. 1 tubers.

Land sparing outperforms land sharing across an elevational gradient in tropical cattle-farming landscapes - Giovanny Pérez; Simon C. Mills; Jacob B. Socolar; Jose M. Ochoa Quintero; Torbjørn Haugaasen; Robert P. Freckleton; Jos Barlow; James. J. Gilroy; David P. Edwards (Biological Conservation, 2026)

Advancing conservation through virtual livestock fencing - Drew E. Bennett; Travis Brammer; Jerod A. Merkle; Kurt T. Smith; Shawn Regan; Temple Stoellinger; Arthur Middleton; Kristin Barker; Jacob P. Hochard; Patrick E. Lendrum; Erin Welty; Craig Benjamin; et al. (Biological Conservation, 2026)

Correction to: Population Discrimination of Indian Halibut Psettodes erumei (Bloch & Schneider, 1801; Psettodidae) in the Eastern Indian Ocean - Ameen Ummath; K. V. Aneesh Kumar; Fahmeeda Parveen; Ashish P. Jacob; Samrat Kalita; G. Padmavati; Sasidharan Venu (Thalassas: An International Journal of Marine Sciences, 2026)

Interactive effects of heat and drought on wheat yield change from synergistic to antagonistic as their severity increases - Arisede Chisaka; John P. Hammond; Shinichi Nakagawa; Jacob Bishop (Agricultural and Forest Meteorology, 2026)

Joint optimization of a GRACE radiation pressure model, the accelerometer scale factors, and an empirical magnetic-field-induced accelerometer bias - F. Jacobs; N. Hładczuk; J. van den IJssel; C. Siemes; P. Visser (Advances in Space Research, 2026)

What Have We Learned From Empirical Applications of Modern Coexistence Theory? - Peter B. Adler; Matteo Detto; Stephen P. Ellner; Theo L. Gibbs; Zachary J. Gold; Samuel J. Leonard; Jacob I. Levine; Annie E. Schiffer; Chuliang Song; Michael Stemkovski; Megan L. Vahsen; Jonathan M. Levine (Ecology Letters, 2026)
Since the early 2000's, Modern Coexistence Theory (MCT) has guided empirical investigations of coexistence. We reviewed empirical applications of MCT to answer two questions: (1) What have we learned about the strength of temporal, spatial and variation‐independent mechanisms of coexistence in nature? (2) How have studies of niche and fitness differences advanced our understanding of coexistence? With respect to the first question, we now have evidence that the temporal storage effect and variation‐independent mechanisms help stabilize coexistence in many systems. We have not learned more due to the low number of tests of these mechanisms (24 out of 84 MCT studies), the narrow focus on mechanisms involving temporal variation and grassland communities, and lack of rigorous model validation. With respect to our second question, studies of niche and fitness differences (61 of 84 studies) have answered fundamental questions about the role of phylogenetic relatedness, plant–soil feedbacks, and functional traits in coexistence. We recommend that future empirical MCT studies (1) match hypotheses to MCT quantities, (2) address gaps in empirical studies, (3) avoid known biases in estimating competition coefficients, and (4) validate models with independent data.

Correction: Effects of Interphase and Interpulse Delays on Tissue Impedance and Pulsed Field Ablation - Edward J. Jacobs; Pedro P. Santos; Rafael V. Davalos (Annals of Biomedical Engineering, 2026)

Compound‐Specific Stable Isotope Analysis Reveals Population‐Specific Differences in Chinook Salmon Trophic Level and Basal Resource Use in the Northeast Pacific - Jacob E. Lerner; Brian P. V. Hunt (Fisheries Oceanography, 2026)
Chinook salmon exhibit far‐flung and disparate population‐specific marine migrations that have made it difficult to assess their trophic ecology. In this study, we collected returning and resident subadult Fraser River Chinook salmon in 2018 and 2019 from population groups with different known run‐timings (spring, summer, and fall) and marine distributions relative to the Fraser River (local/south, north, offshore) and processed them for carbon and nitrogen CSIA‐AA. We investigated population‐specific differences in trophic level using δ 15 N AA , and used δ 13 C AA with published taxon‐specific fingerprints of phytoplankton groups to investigate differences in the primary producer base that underpinned the food web they experienced. The south/local Fraser Fall 4 1 population exhibited distinct δ 13 C AA values from the north and offshore Summer 4 1 , Spring 5 2 , and Summer 5 2 populations, likely due to their different geographic distributions and corresponding differences in primary producer communities. Chinook salmon trophic level was variable, with evidence for more omnivory and lower trophic levels in the southern distributing populations (TL = 3.7 ± 0.2) relative to the northern ones (TL = 3.9 ± 0.1), although there was interannual variability in the trophic level of the southern distributing population. This analysis builds on previous investigations of Chinook salmon marine ecology, linking distribution to basal food web resources to trophic level, and highlights the importance of population‐specific marine distributions in structuring Chinook salmon trophic ecology. Knowledge of their food web ecology is necessary to understand how this species is and will respond to changing climate and ocean conditions and support management and conservation efforts.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

First Evidence of Porcine Epidemic Diarrhoea Virus and African Swine Fever Virus Natural Co-Infection in Pigs from Karnataka, India: An Epidemiological Investigation - Jagadish B. Hiremath; R. Ramamoorthy; M. V. Bhuvan Bharadwaj; S Ranganatha; Jayachandra H. Kempashi; Sharanagouda S. Patil; H. B. Chethankumar; K. P. Suresh; Shivasharanappa Nayakvadi; S. P. Satheesha; Siju Susan Jacob; Sathish Gowda; et al. (Current Microbiology, 2026)

Larval Genomics as a Viable, Fisheries‐Independent Tool for Investigating Population Structure in Tropical Pacific Tunas - Jacob E. Jaskiel; Hannah E. Aichelman; Giulia Anderson; Louw Claassens; James E. Fifer; Christina M. Hernandez; Alexa K. Huzar; Joel K. Llopiz; Jan W. Witting; Sean P. Mullen; Randi D. Rotjan (Molecular Ecology, 2026)
Understanding how dispersal, life history, and environmental variability shape genetic connectivity in the open ocean remains a central challenge in evolutionary biology. Highly migratory marine predators like tunas have traditionally been considered genetically homogeneous across ocean basins, yet emerging genomic evidence suggests that cryptic population structure can persist even in species with high gene flow and large effective population sizes. We used 2bRAD sequencing of 348 larval and subadult skipjack ( Katsuwonus pelamis ), yellowfin ( Thunnus albacares ), and bigeye tuna ( T. obesus ) collected from the central Pacific across 7 years of sampling to examine species boundaries, population genetic information, genetic structure, and connectivity. Larval sampling revealed consistent spawning by all three species and enabled unbiased detection of genetic patterns prior to recruitment bottlenecks. We found strong divergence amongst species, no evidence of structuring within skipjack or bigeye, and a divergent yellowfin population detected in 2 consecutive sampling years north of American Samoa. Comparisons between larvae and subadults suggest that sampling early life history stages can be a valuable tool for assessing population genetic information before recruitment bottlenecks, selective harvest by fisheries, adult dispersal, and selective pressures acting on adult populations, thereby contributing novel insights to the research and effective management of these species. These results highlight how larval genomics can complement traditional population genomic studies of adult tunas and reveal fine‐scale structure in highly vagile species, providing new perspectives on connectivity in the open ocean.

Intestinal microbiome in response to air pollutant exposure in pregestational and gestational murine females and their male and female offspring - Shubhamoy Ghosh; Amit Ganguly; Tien S. Dong; Venu Lagishetty; Jonathan P. Jacobs; Sherin U. Devaskar (Reproductive Toxicology, 2026)

Population Discrimination of Indian Halibut Psettodes erumei (Bloch & Schneider, 1801; Psettodidae) in the Eastern Indian Ocean - Ameen Ummath; K. V. Aneesh Kumar; Fahmeeda Parveen; Ashish P. Jacob; Samrat Kalita; G. Padmavati; Sasidharan Venu (Thalassas: An International Journal of Marine Sciences, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Evaluating the validity of using sea surface temperature as an alternative to bottom temperature in American lobster habitat suitability modeling - Xiangyan Yang; Robyn Linner; Cameron Hodgdon; Jacob P. Kritzer; George Maynard; Erin Pelletier; Yong Chen (Progress in Oceanography, 2026)

Prenatal exposure to heat stress and postpartum depressive symptoms in the MADRES cohort in urban Los Angeles - Yuhong Hu; Noelle Pardo; Xiaoran Yang; Tingyu Yang; Yan Xu; Roxana Khalili; Aviva Wolf-Jacobs; Xinci Chen; Zhongzheng Niu; Claudia M. Toledo-Corral; Jill Johnston; Genevieve F. Dunton; et al. (Environmental Research, 2026)

Initiation of dolutegravir vs. efavirenz on 12- and 24-month retention and viral suppression: a target trial emulation - Amy Zheng; Alana T. Brennan; Ross Greener; Emma M. Kileel; Jacob Bor; Willem D. F. Venter; Eleanor J. Murray; Pedro T. Pisa; Bridgette Goeieman; Matthew P. Fox; Mhairi Maskew (Infectious Diseases, 2026)

Effects of an intervention for a liquefied petroleum gas cook-stove with free fuel on food insecurity and dietary diversity among women and infants: a multi-country randomized controlled trial - Sheela S. Sinharoy; Rina Das; Anaité Diaz-Artiga; Lisa M. Thompson; Ghislaine Rosa; John McCracken; Miles A. Kirby; Carla Tarazona-Meza; Vigneswari Aravindalochanan; Shirin Jabbarzadeh; Jiantong Wang; Ajay Pillarisetti; et al. (Food Security, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Designing a rapid response process for urgent policy-relevant knowledge needs: A case study on deadwood and forest fires - R. Dianoux; L. Brotons; S. Corticeiro; J.-C. Dajka; U. Jacob; K. Korhonen-Kurki; M. Larjavaara; K. Locher-Krause; A.B. Leverkus; P. Maia; T.G.M. Sanders; M. Vandewalle; et al. (Environmental Science & Policy, 2026)

Strong Variation in Land‐Use Change Impacts on Tropical Avian Phylogenetic Diversity Between Ecoregions Highlights the Need to Sample Large Spatial Scales - Giovanny Pérez; Simon C. Mills; Jacob B. Socolar; Jose M. Ochoa Quintero; Robert P. Freckleton; Torbjørn Haugaasen; James J. Gilroy; David P. Edwards (Global Change Biology, 2026)
Forest conversion for agriculture is a major cause of tropical biodiversity loss, but its impacts vary with spatial scale. Higher species turnover in forests than in farmland means that land‐use change causes greater biodiversity loss at broader than at local scales, yet broad‐scale assessments are scarce. Phylogenetic diversity is increasingly prioritised in conservation to protect evolutionary history under global change, yet how deforestation‐driven changes in phylogenetic diversity scale spatially and accumulate in regions of high species turnover remains unclear. We compiled a large field database from across 13 biogeographically diverse regions affected by deforestation for cattle farming, covering most of Colombia, a megadiverse tropical country. Using occupancy models, we estimated bird communities for 1547 (936 observed plus 611 never‐observed) species across ecoregions and nationally in both forest and pasture habitats to quantify changes in phylogenetic diversity metrics and determine whether these impacts are dependent on spatial scale. We found an average loss of 2300 Myr of phylogenetic diversity at the country scale, with most species negatively affected across the phylogeny. Although single regional‐scale relative loss was on average comparable to broader scales, there was high variability between regional units. The latter was especially critical when evaluating metrics of evolutionary distinctiveness, which are key indicators for biodiversity conservation planning. Such underestimation of national‐scale impacts highlights the importance of sampling across multiple regions. Immediate conservation action is needed to safeguard evolutionarily unique species and prevent phylogenetic homogenisation driven by agricultural expansion across spatial scales—a threat often underestimated due to assessments limited to single biogeographic regions.

Computational analysis of Non-synonymous SNP effects on human PLVAP gene structure and function - Mehnaj Khatoon; Yamini Sri Sekar; Swati Rani; Varsha Ramesh; M. Shijili; Vinod Jangid; C. A. Archana; Azhahianambi Palavesam; Siju Susan Jacob; Jagadish Hiremath; Sharanagouda S. Patil; Baldev Raj Gulati; et al. (Journal of Applied Genetics, 2025)

The 10/20/30 planting rule aligns with traditional plant diversity metrics across spatial scales - Michael R. Freiburger; Colleen Murphy-Dunning; Danica A. Doroski; P. Mark Ashton; Jacob D.J. Peters (Urban Forestry & Urban Greening, 2025)

Prolonged exposure to low-dose traffic-derived PM2.5 causes fatty liver disorder in mice - Min Feng; Matthew P. Padula; Sara Al Asaad; Xu Bai; Charles Cranfield; Stephanie EL Town; Sonia Saad; Brian G. Oliver; Jacob George; Hui Chen (Journal of Environmental Sciences, 2025)

Favorability mapping for hydrothermal power resource assessments of the Great Basin, USA - Stanley P. Mordensky; Erick R. Burns; John J. Lipor; Jacob DeAngelo (Geothermics, 2025)

Mangrove-based carbon market projects: Current trends and future perspectives - Jorge F. Montenegro; Midhun Mohan; Ewane Basil Ewane; Daniel A. Friess; Pandi P. Selvam; Abhilash Dutta Roy; Aaron Althauser; Jacob Tidwell; Julieta Gamboa-Cutz; Caileigh Shoot; Michael S. Watt; Peter I. Macreadie; et al. (Forest Policy and Economics, 2025)

Corrigendum to “Subchronic inhalation exposure to ultrafine particulate matter alters the intestinal microbiome in various mouse models” [Environ. Res. 248 (2024) 118242] - Candace Chang; Rajat Gupta; Farzaneh Sedighian; Allen Louie; David M. Gonzalez; Collin Le; Jae Min Cho; Seul-Ki Park; Jocelyn Castellanos; To-Wei Ting; Tien S. Dong; Nerea Arias-Jayo; et al. (Environmental Research, 2025)

Molecular phylogeny of Psoroptes ovis isolated from ear canker in a domestic rabbit from South India - D. Akilkumar; Y. Ajith; Sasi Adithya; Rose Sherin; Siju Susan Jacob; P. V. Tresamol (Molecular Biology Reports, 2025)

Characterizing tick diversity among caprine hosts of Kerala, India: a phylogenetic study - Sasi Adithya; Andrews Megha; Y. Ajith; K. S. Athira; Anna-Maria Ettel; S. Gireesh Sangeetha; Siju Susan Jacob; P. V. Tresamol (Molecular Biology Reports, 2025)

Invasive freshwater jellyfish (Craspedacusta cf. sowerbii) in the Hudson River basin, NYS: comparisons of detection methods - Jacob P. Moore; Hyatt C. Green; Donald J. Stewart; Florian Lüskow; Maxwell L. Wilder (Hydrobiologia, 2025)

Upscaling nature-based solutions for reducing risk from natural hazards: From process to practice - Amanda Tritinger; Sydney Crisanti; Steven P. Bailey; Jacob F. Berkowitz; Elizabeth S. Godsey; Burton C. Suedel; Jeffrey K. King (Advances in Water Resources, 2025)

Solar and thermal radiation pressure modelling for improving the GOCE horizontal wind dataset - N.A. Hładczuk; J. van den IJssel; F. Jacobs; C. Siemes; P. Visser (Advances in Space Research, 2025)

Biological control of the sugarcane planthopper, Pyrilla perpusilla by the introduction and colonization of ectoparasitoid moth, Epiricania (= Fulgoraecia) melanoleuca in a sugarcane crop island ecosystem - B. Mahendran; P. Mahesh; R. Gopi; T. N. Madhu; S. K. Pandey; M. Nisha; Keerthana; Sony Jayaraman; Savio Jacob Saji (BioControl, 2025)

Household air pollution and blood pressure among adult women participants of the Household Air Pollution Intervention Network Trial: An exposure-response analysis - Ajay Pillarisetti; Wenlu Ye; Jennifer L. Peel; Howard Chang; Lindsay J. Underhill; Kalpana Balakrishnan; Anaité Díaz-Artiga; John P. McCracken; Ghislaine Rosa; Lisa M. Thompson; Vigneswari Aravindalochanan; Dana Boyd Barr; et al. (Environmental Research, 2025)

Gestational and postnatal exposures to fine particulate matter (PM2.5) and their association with acute ear infections, diarrhea, respiratory symptoms, and mortality: A longitudinal study of infants in the multicountry Household Air Pollution Intervention Network (HAPIN) trial - Brandie Banner Shackelford; Kyle Steenland; Miles A. Kirby; Kalpana Balakrishnan; Marilú Chiang; Anaité Diaz-Artiga; John P. McCracken; Lisa M. Thompson; Ghislaine Rosa; Lance A. Waller; Shirin Jabbarzadeh; Jiantong Wang; et al. (Environmental Research, 2025)

Tailoring Mg-MOF-74 for trace CO₂ capture by morphological tuning and piperazine functionalization - Qiao Liu; Shraavya Rao; John Matteson; Cassandra Gates; Nina S. Pappas; Kate Chen; Benjamin Stein; Xiaojing Wang; Piotr Zelenay; Rajinder P. Singh; Jacob S. Spendelow (Chemical Engineering Journal, 2025)

Integrated thermal and biological conversion of microalgal proteins to lipids - Tobias C. Hull; Eric P. Knoshaug; Robert S. Nelson; Stefanie Van Wychen; Nick Nagle; Jacob S. Kruger; Tao Dong (Bioresource Technology, 2025)

The key mechanisms associated with the survival of Gulf toadfish, Opsanus beta , when in severe hypoxia - Anastasiya Plotnikova; Isabelle R. Nelson; Shara Y. Sookhoo; Jacob M. Belkin; Vanessa P. Lima; Ross D. Bronfman Bunch; Athena M. Santomero; Sophia A. Santomero; Emily C. Rodriguez; Jayda K. Rodriguez; Kathleen M. Davis; Amanda J. Kaplan; et al. (Journal of Fish Biology, 2025)
Florida's shallow seagrass beds experience daily diurnal fluctuations in environmental oxygen, leading to hypoxic episodes (PO 2 −1 , ~6 kPa) that have increased in frequency and intensity in recent decades. The native Gulf toadfish ( Opsanus beta ) have been shown to employ a suite of adaptive cardiovascular, ventilatory and metabolic adjustments to survive moderate hypoxia, but little is known of the mechanisms used to survive severe hypoxia. The objective of this study was to characterize the acute response of Gulf toadfish to severe hypoxia ( 2 ~0.4 kPa for 3 h followed by 1 h recovery). Heart rate, pulse pressure, caudal arterial blood pressure, ventilation frequency and ventilation amplitude were monitored and blood samples were taken from both groups and analysed for pH, glucose, lactate and other endpoints. Hypoxia‐exposed fish experienced a statistically significant 70% decrease in heart rate and a 32% decrease in ventilation frequency during hypoxia exposure. Moreover, plasma glucose concentrations increased 5‐fold and plasma lactate concentrations increased 6‐fold, with a minimal reduction in pH. Our findings support our hypothesis that Gulf toadfish are highly hypoxia tolerant and survive severe hypoxia by reducing energy expenditure and switching to anaerobic metabolism. It is important to understand how the Gulf toadfish deal with severe hypoxia due to the increasing prevalence of severe hypoxia in its natural environment.

On the behavior of Fish Released Following Fisheries Capture: Methods, Endpoints, and Consequences - Luc LaRochelle; Lucas P. Griffin; Jacob W. Brownscombe; Chris K. Elvidge; Caleb T. Hasler; Jessica A. Robichaud; Jamie C. Madden; Sean J. Landsman; Vincent Raoult; Andy J. Danylchuk; Steven J. Cooke (Reviews in Fisheries Science & Aquaculture, 2025)

Physiological responses of Gutweed Ulva intestinalis (Linnaeus, 1753) exposed to high-density polyethylene microplastics - Philippe Anthony M. Alfafara; Pauleanne B. Nacario; Nelle Adrian M. Ceniza; Eugene T. Bacolod; Maria Kristina O. Paler; Maria Ligaya S. Suico; Alvin P. Monotilla; Ric Jacob Y. Hernandez; Noel Peter B. Tan; Lorenz Inri C. Banabatac (Marine Pollution Bulletin, 2025)

Disease-suppressive mechanisms in contrasting potato-based strip-cropping systems - Zohralyn Homulle; Paola Cassiano; Slava Shevchuk; Niels P. R. Anten; Tjeerd Jan Stomph; Wopke van der Werf; Jacob C. Douma (European Journal of Plant Pathology, 2025)
Intercropping has been shown to suppress diseases in many crop-pathogen combinations and could be a component of more sustainable integrated crop protection. While various disease-suppressive mechanisms have been proposed, it remains unclear how different companion species influence these mechanisms, and whether trade-offs or synergies exist between them. Field experiments were conducted in the Netherlands to study various disease-suppressive mechanisms affecting late blight epidemics in potato strip-cropped with contrasting companion crops (grass, faba bean, or maize). Strip cropping significantly altered the microclimate in the potato strip; relative humidity was lower in potato-grass than in the potato monoculture, whereas the humidity was increased in potato-maize, especially later in the season. Strip cropping with faba bean did not significantly change the microclimate. Furthermore, potato-maize intercropping received the lowest number of particles over the growing season (a proxy for incoming spores). Strip cropping had little to no effect on potato plant morphology or canopy structure. Grass as a companion created drier conditions in the neighbouring potato canopy making it less conducive for disease development, while maize formed a barrier for spore dispersal though it increased humidity later in the season. But the barrier strategy appears a less certain approach across growing seasons, as it relies on the companion crop reaching sufficient height before the epidemic begins, but the timing of the epidemic is unpredictable and may be very early. This study offers insights into how companion species with specific traits can assist disease control in strip cropping.

Distribution and Strandings of Risso’s Dolphin ( Grampus griseus (G. Cuvier, 1812)): First Sighting From the Bay of Bengal Inside the Indian EEZ - Yosuva Mariasingarayan; John Peter Raju; Kumar Pandion; Shruti Nair; Ayana Sholy; Ashish P. Jacob; Soumya Ranjan Panda; Nishant Umralkar; B. Arunima; Nidhi Johri; Lekkala Ramajyothi Madhavi; P. S. Ashik; et al. (Marine Mammal Science, 2025)

Application of mercury stable isotopes to examine sources and hydrologic factors impacting mercury bioaccumulation and cycling in invertebrates of a model saline lake - Samuel F. Lopez; Sarah E. Janssen; Michael T. Tate; Frank J. Black; Hannah E. McIlwain; Laura E. Flucke; Jacob M Ogorek; William P. Johnson (Water Research, 2025)

Life-cycle assessment of concrete production with carbon capture and carbon upcycling process - Tianyu Chen; Jacob P. Nelson; Vijay Gupta; Paul D. Mobley (Journal of Environmental Management, 2025)

Spatial disaggregation of coarse-scaled gridded rainfall data using open-source earth observation in a semi-arid region for water resources management - Kunal Karan; Dharmaveer Singh; Amzad Hussain Laskar; Jacob Noble; Nikhil Kumar; Debrupa Chatterjee; John P. Wilson (Advances in Space Research, 2025)

Synthesising Support for the Entrainment Hypothesis Through Spatially Explicit Life Cycles, Vagrancy and Collapse of Atlantic Tarpon ( Megalops atlanticus ) - Lucas P. Griffin; Aaron J. Adams; Jacob W. Brownscombe; Steven J. Cooke; Michael A. Dance; Susan K. Lowerre‐Barbieri; Eric S. Orbesen; Derke Snodgrass; Andy J. Danylchuk (Fish and Fisheries, 2025)
Understanding spatial dynamics and migratory behaviours of fish populations is essential for effective fisheries management. We focus on the migratory Atlantic tarpon ( Megalops atlanticus ) to explore how movement strategies and spatial life cycle patterns shape stock dynamics, contingent structure and mechanisms for collapse and recovery. The entrainment hypothesis posits that migratory routes are socially transmitted from experienced repeat spawners to younger conspecifics, resulting in distinct contingents within a population. Using a combination of literature review, life history data, mark‐and‐recapture records and electronic tagging, we evaluated five biological hypotheses related to entrainment mechanisms, habitat conservatism and phenotypic plasticity within Atlantic tarpon populations. Our findings provide evidence for migratory connectivity and the role of entrainment in shaping Atlantic tarpon contingent structure across the Western Atlantic. Movement and mark‐and‐recapture data revealed spatially discrete contingents with some intermixing, highlighting behavioural conservatism and phenotypic plasticity. Examples of vagrancy showed Atlantic tarpon caught far from their capture contingent, suggesting vagrant movements may contribute to colonising new habitats under suitable conditions. Straying by a subset of individuals may also increase the recovery and resilience of Atlantic tarpon stocks following collective memory loss in migratory routes. Research on contingent structure, larval recruitment patterns and abundance trends is needed to inform management measures to ensure the maintenance of migratory knowledge. This approach provides a framework for understanding Atlantic tarpon and other migratory marine fish stock dynamics, while underscoring the importance of coordinated management and conservation efforts across contingent boundaries.

Assessment of an integrated catalytic treatment system for the continuous removal of organic and inorganic pollutants in water - A. Sofia G.G. Santos; A. Rita L. Ribeiro; Jacob P. Troutman; Charles J. Werth; João Restivo; Carla A. Orge; M. Fernando R. Pereira; O. Salomé G.P. Soares (Journal of Environmental Chemical Engineering, 2025)

Personal exposures to air pollutants and respiratory health among brick kiln workers and household members - Laura Nicolaou; Evelyn Rowell; Chelsea Gaviola; Ram K. Chandyo; Arun K. Sharma; Laxman P. Shrestha; Santa Das; David L. Parker; Steven M. Thygerson; Joseph Jacob; Bojidar Rangelov; Ryoko Egashira; et al. (Environmental Research, 2025)

Decreases in chimpanzee respiratory disease signs and enteric viral quantity following implementation of anthroponotic disease prevention protocols at a long-term research site - Jacob D. Negrey; Samuel Angedakin; Rachna B. Reddy; Aaron A. Sandel; Salmah Jombela; Erone Akamumpa; Christopher Aliganyira; Charles Birungi; Davis Kalunga; Brian Kamugyisha; Diana Kanweri; Godfrey Mbabazi; et al. (Biological Conservation, 2025)

Effects of Interphase and Interpulse Delays on Tissue Impedance and Pulsed Field Ablation - Edward J. Jacobs; Pedro P. Santos; Rafael V. Davalos (Annals of Biomedical Engineering, 2025)
Purpose High-frequency irreversible electroporation (H-FIRE) is a pulsed field ablation (PFA) technique that employs a series of high-voltage, microseconds-long positive and negative pulses, separated by interphase (d1) and interpulse (d2) delays to non-thermally ablate tissue. Previous experimental and computational data suggest an impact of delays on nerve excitation and electrochemical effects. However, the impact of delays on PFA outcomes, such as change in resistance and ablation generation, has only recently started to be elucidated. Methods While recording the applied voltage and currents, we delivered a series of increasing voltages, termed voltage ramps, into tuber and cardiac tissues using both needle electrode pairs and flat plate electrodes. Tissues were stained for metabolic activity to measure irreversible electroporation areas following treatment. Results Our findings support previous in vitro data that delays do not significantly affect ablation areas. While there were significant differences in applied current, resistance, and conductivity between different pulse widths at sub-electroporation electric fields, we found no significant differences after inducing electroporation between different delays and pulse widths. Consequently, since delays do not affect ablation areas or local conductivity, the data suggests that delays should not affect the electric field threshold or Joule heating within the tissue. Conclusion The findings presented here provide critical insights into electroporation-dependent tissue conductivity changes from H-FIRE with implications for improving H-FIRE parameterization and computational models for treatment planning in cancer and cardiac pulsed field ablation.

Migratory patterns and seasonal habitat use of great hammerhead sharks ( Sphyrna mokarran ) in the southeastern United States - Grace A. Casselberry; Gregory B. Skomal; Lucas P. Griffin; Jacob W. Brownscombe; John T. Finn; Joseph Dello Russo; Alex Filous; Peter E. Holder; Ben Daughtry; Jeff Kneebone; Danielle Morley; Susan K. Lowerre‐Barbieri; et al. (Journal of Fish Biology, 2025)
The great hammerhead shark ( Sphyrna mokarran ) is a highly mobile shark species whose population in the United States declined dramatically through the early 2000s. Their spatial ecology is poorly understood, creating challenges for effective conservation of this enigmatic marine predator. Using acoustic telemetry and network analyses, we describe the movement patterns of 15 mature great hammerhead sharks (207–331.5 cm fork length) primarily within the waters of the southeastern United States from April 2019 to December 2022, including identifying movement corridors, core use areas and seasonal shifts in habitat use. Great hammerheads exhibited partial migration; some sharks undertook consistent, repeatable, round‐trip migrations between the tagging site in the Florida Keys and northern points in the Gulf of Mexico and Atlantic coast. Conversely, others remained in the Florida Keys year‐round. Network analysis coupled with community detection algorithms revealed that individual great hammerheads displayed oceanic basin affinity, favouring migration to either the Atlantic Ocean or Gulf of Mexico. Great hammerheads that remained in the Florida Keys shifted their habitat use seasonally from inshore channels (spring and summer) to offshore artificial reefs and the natural reef tract (summer through winter). These shifts may be driven by prey availability, as core use areas often corresponded to known locations of seasonal spawning aggregations for reef fish. These data fill an important knowledge gap for great hammerhead migratory patterns that can improve spatial management strategies for this historically overexploited species. We discuss the importance of drawing upon data from multiple tagging locations for highly mobile species management, particularly in the designation of essential fish habitat.

Doxorubicin treatment has a biphasic effect over time on dopamine release and impulsive behavior in Wistar rats - Kiersten J. Garcia; Jacob T. Theismann; Tadd D. Schneider; Robert S. LeComte; David P. Jarmolowicz; Michael A. Johnson (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Disulfide-based 2-pyridyl-hydrazone prochelators induce iron deprivation and oxidative stress in ovarian cancer cells - Jacob B. Fussell; Jake P. Shaw; Madison A. Grams; Yu-Shien Sung; Ren-Hua Jheng; Andrei V. Astashkin; Elisa Tomat (JBIC Journal of Biological Inorganic Chemistry, 2025)

Spatial Variability of Marine Heatwaves in the Chesapeake Bay - Rachel Wegener; Jacob Wenegrat; Veronica P. Lance; Skylar Lama (Estuaries and Coasts, 2025)
The Chesapeake Bay is the largest estuary in the continental United States. Extreme temperature events, termed marine heatwaves, are impacting this ecologically important zone with increasing frequency. Although marine heatwaves evolve across space and time, a complete spatial picture of marine heatwaves in the Bay is missing. Here, we use satellite sea surface temperature to characterize marine heatwaves in the Chesapeake Bay. We consider three products: NASA MUR, NOAA Geo-Polar, and Copernicus Marine OSTIA, and validate their effectiveness using in situ data from the Chesapeake Bay Program. We find that Geo-Polar SST is the most suitable dataset for marine heatwave analysis in this location, with a root mean squared error of 1.6 $$^° $$ ∘ C. Marine heatwaves occur on average of 2.3 times per year and last 10.8 days per event. A north-south (along estuary) gradient is identified as a common pattern of spatial variability. Seasonally, summer marine heatwaves are shorter, more frequent, and have a more consistent duration, with an inter-quartile range of 6–11 days (median=8 days). December marine heatwaves have a much larger inter-quartile range of 6–28 days (median=13 days). Marine heatwaves are increasing at a rate of 4 events/year in the upper Bay and 2 events/year in the main stem of the lower Bay. Our analysis suggests that the major observed spatial patterns are a result of long-term warming, not shifts in the spread of the temperature distribution. Overall, the qualitative character of marine heatwaves in the Chesapeake Bay is not changing but they are becoming more frequent.

Harmonizing nature’s timescales in ecosystem models - Vivienne P. Groner; Jacob Cook; C. David L. Orme; Priyanga Amarasekare; Edward Comyn-Platt; Taran Rallings; Jaideep Joshi; Robert M. Ewers (Trends in Ecology & Evolution, 2025)

Investigation regarding the physiological effects of cobalt on physiological functions in Drosophila, crayfish, and crab: Behavioral, cardiac, neural, and synaptic properties - Jaycie E. Gard; Kaitlyn E. Brock; Elizabeth R. Elliott; Alaina C. Taul; Jeremy Nadolski; Jiwoo Kim; Shelby McCubbin; Jordon Hecht; Remy Ronen; Sonya M. Bierbower; Jayden P. Alcorn; Nikitha Dharanipragada; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Using paleolimnology to assess long-term acidification and recovery trajectories in lakes from Killarney Provincial Park and Sudbury (Ontario, Canada) - Courtney Lanigan; Neal Michelutti; Andrew M. Paterson; Carsten Meyer-Jacob; Brigitte Simmatis; John P. Smol (Journal of Paleolimnology, 2025)

Morpho-physiological traits underpinning high-temperature stress tolerance in cowpea (Vigna unguiculata L. Walp.) - Mallikarjun Biradar; Kuldeep Tripathi; Vijay Singh Meena; P. S. Basavaraj; Jyoti Kumari; Shashidhar B. Reddappa; Dhammaprakash Wankhede; Sherry Rachel Jacob; Sunil Archak (Genetic Resources and Crop Evolution, 2025)

Thermophysical properties and phase diagrams in the system MgO–SiO2–FeO at lower mantle conditions derived from a multiple-Einstein method - Michael H. G. Jacobs; Rainer Schmid-Fetzer; Arie P. van den Berg (Physics and Chemistry of Minerals, 2025)

Tree swallow (Tachycineta bicolor) demographics and metal(loid) concentrations in egg contents from the Kootenai River basin, Montana nest box colonies - Brian C. Balmer; Joseph P. Skorupa; Katherine B. Adams; Bridger M. Creel; Gregory C. Hoffman; Megan A. Fylling; Stephanie Le; Jacob M. Martin; Theresa L. McBride; Jacob T. Williams; Travis S. Schmidt (Environmental Monitoring and Assessment, 2025)

Structural brain correlates of balance control in children with cerebral palsy: baseline correlations and effects of training - Nina P. T. Jacobs; Marjolein M. van der Krogt; Annemieke I. Buizer; Laura A. van de Pol; Chloé E. C. Bras; Frederik Barkhof; Pieter Meyns; Petra J. W. Pouwels (Brain Structure and Function, 2025)
Structural brain abnormalities likely underlie impaired balance control in cerebral palsy (CP). This study investigated whether balance measures were associated with measures derived from conventional MRI and diffusion tensor imaging (DTI), and whether an X-Box One Kinect balance training (6 weeks, 5 days/week, 30 min/session) could induce neuroplastic changes in CP. Twelve children with spastic CP (age:11.3 ± 2.3y) underwent balance evaluation and MRI examination, at baseline and after training. Nine age-matched typically developing (TD) children underwent baseline measurements. Balance control was evaluated testing advanced motor skills (Challenge score) and during gait (medio-lateral Margin of Stability, MoS). With conventional MRI, but especially with DTBM (DTI-based VBM), we found smaller volumes of several deep grey matter structures and within the right inferior parietal cortex, right supramarginal cortex, and left postcentral cortex, and lower fractional anisotropy (FA) and smaller volumes of various white matter regions in CP compared to TD. Within the CP group alone, no correlations within brain tissue were found. After training, Challenge scores of children with CP improved. In an exploratory analysis DTBM showed a trend for volume increase within the right inferior parietal cortex, volume decrease within the right retrolenticular limb of the internal capsule, and an increase of FA within the right corticospinal tract. This indicates that a 6-week balance intervention may induce neuroplastic changes in children with CP. CP-RehOP (trial registration number: NTR6034/NL5854, date of registration: August 26th 2016).

Colonoscopy findings in CDH1 carriers from a multicenter international study - Arjun Chatterjee; Robert Hüneburg; Qijun Yang; Shannon Morrison; Anna Bettzüge; Tim Marwitz; Stefan Aretz; Isabel Spier; Tim Ripperger; Silke Redler; Mykyta Kachanov; Alexander E. Volk; et al. (Familial Cancer, 2025)
Germline (likely-)pathogenic variants (PV) in CDH1 predispose carriers to hereditary diffuse gastric cancer and lobular breast cancer. Previous studies from the United States suggest CDH1 variant carriers have an increased risk for adenomas or sessile serrated lesions (SSL), yet data linking CDH1 PVs and colorectal neoplasia are scarce. We aimed to investigate colonoscopy findings in CDH1 PVs. Adults carrying a PV/LPV in CDH1 with ≥ 1 colonoscopy between 01/01/2004–12/31/2023 were included. Patients were sourced from the David G. Jagelman Inherited Colorectal Cancer Registries at Cleveland Clinic and the German Consortium for Familial Intestinal Cancer. 103 CDH1 PV carriers were included. Most were female (66%) and white (93.1%). The median age at first colonoscopy was 47 years. The adenoma detection rate (ADR) was 29.4% (95% CI:19.9–41.1%) in the German cohort and 48.6% (95% CI: 33.0-64.4%) in the Cleveland cohort ( p = 0.055) and significantly correlated with age (< 45 years, 13.6% (95% CI: 6.40–26.7%); 45–49 years, 52.4% (95% CI: 32.4–71.7%); ≥50 years, 52.6% (95% CI: 37.3–67.5%); p < 0.001). The ADR in Cleveland was higher than the U.S. average ADR but the difference was not statistically significant (48.6% vs. 35.6%, p = 0.08), and the ADR in the German cohort (29.4%) was similar to the national German average risk screening cohort (31.3% in men, p = 0.84; 20.1% in women, p = 0.08). In our screening cohort with CDH1 PV carriers, we demonstrated an ADR of 13.5% in individuals under 45 years, similar to the ADR in patients aged 25–40 years with a family history of CRC. Overall, SSL detection rate was 9.7%. Colorectal cancer was diagnosed in 3 patients (3.2%), 2/3 with an early age of onset before the age of 50 years. This first international study provides preliminary evidence of a higher ADR in U.S. CDH1 PV carriers compared to the general population, with a high number of adenomas detected before the age of 50. This may indicate an increased CRC risk that should be explored in larger studies.

Fire Frequency Driven Increases in Burn Heterogeneity Promote Microbial Beta Diversity: A Test of the Pyrodiversity‐Biodiversity Hypothesis - Jacob R. Hopkins; Alison E. Bennett; Thomas P. McKenna (Molecular Ecology, 2025)
Fire is a common ecological disturbance that structures terrestrial ecosystems and biological communities. The ability of fires to contribute to ecosystem heterogeneity has been termed pyrodiversity and has been directly linked to biodiversity (i.e., the pyrodiversity–biodiversity hypothesis). Since climate change models predict increases in fire frequency, understanding how fire pyrodiversity influences soil microbes is important for predicting how ecosystems will respond to fire regime changes. Here we tested how fire frequency‐driven changes in burn patterns (i.e., pyrodiversity) influenced soil microbial communities and diversity. We assessed pyrodiversity effects on soil microbes by manipulating fire frequency (annual vs. biennial fires) in a tallgrass prairie restoration and evaluating how changes in burn patterns influenced microbial communities (bacteria and fungi). Annual burns produced more heterogeneous burn patterns (higher pyrodiversity) that were linked to shifts in fungal and bacterial community composition. While fire frequency did not influence microbial (bacteria and fungi) alpha diversity, beta diversity did increase with pyrodiversity. Changes in fungal community composition were not linked to burn patterns, suggesting that pyrodiversity effects on other ecosystem components (e.g., plants and soil characteristics) influenced fungal community dynamics and the greater beta diversity observed in the annually burned plots. Shifts in bacterial community composition were linked to variation in higher severity burn pattern components (grey and white ash), suggesting that thermotolerance contributed to the observed changes in bacterial community composition and lower beta diversity in the biennially burned plots. This demonstrates that fire frequency‐driven increases in pyrodiversity augment biodiversity and may influence productivity in fire‐prone ecosystems.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Tropical Land‐Use Change Disrupts Zeta‐Diversity Across Taxa - Edicson Parra‐Sanchez; Guillaume Latombe; Simon C. Mills; Jacob B. Socolar; Felicity A. Edwards; Diego Martinez‐Revelo; Oscar A. Perez‐Escobar; Robert W. Davies; Christopher G. Bousfield; Gianluca R. Cerullo; Jose Manuel Ochoa‐Quintero; Torbjørn Haugaasen; et al. (Global Change Biology, 2025)
Land‐use change causes community turnover via local extinction and colonisation of species, driving biotic homogenization or heterogenization at larger spatial scales. Quantification of these processes has focused on beta‐diversity metrics, which upweight rarity and overlook the role of widespread species. A key knowledge gap is understanding the impact of land‐use change on both rare and widespread species—zeta‐diversity—allowing the detection of statistical patterns and drivers based on community turnover across space. We sampled bird, dung beetle, and orchid communities in 341 plots across natural (Andean forests and paramo) and transformed habitats (pasturelands) spanning ~270 km north‐to‐south in the Colombian Andes. We detected major losses in species richness following land‐use conversion, which disrupts zeta‐diversity across elevation in two ways. First, biodiversity patterns are rewired such that bird and dung beetle communities become structured by dispersal ability, overriding the effects of natural biogeographical drivers (i.e., elevation) and landscape conditions (i.e., canopy cover). Second, land‐use change causes biotic homogenization across bird communities, with pasture retaining twice as many widespread species than natural habitats, and a four‐fold reduction in widespread dung beetle species pointing to subtractive heterogenization. Orchid communities show high community turnover in both natural and transformed habitat. Our results show that the effect of local deforestation has a doubly devastating impact simplifying communities and reducing widespread species. Transforming natural habitats into anthropogenic landscapes may substantially raise extinction risk for communities composed of both widespread and rare species, especially in orchids as the most sensitive taxon.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Far-red light perception by the shoot influences root growth and development in cereal-legume crop mixtures - Jin L. Wang; Jochem B. Evers; Niels P. R. Anten; Yitong Li; Xiaoyi Yang; Jacob C. Douma; Hannah M. Schneider (Plant and Soil, 2025)
Background and aims Above- and below-ground signals for and responses to competition in mixed-species stands have mostly been studied separately. This leaves unclear if aboveground signals specific to mixed stands have consequences for how plants respond and compete belowground. This study investigated the effect of an aboveground signal, the ratio of red to far-red light (R/FR), on plant biomass allocation and root architecture and morphology when plants grow with different species. Methods A greenhouse experiment with a mixture of wheat ( Triticum aestivum ) and faba bean ( Vicia faba ) and their respective mono stands was carried out in deep pots (22.6 L, 72 cm in depth) for 52 days of growth. Light-emitting diode (LED) lights were used to enrich FR levels (i.e., reduce the R/FR) of the light environment. Results Exposure of the shoots to FR-enriched light predominantly affected adventitious roots, with species-specific effects. Especially in species mixtures, increased FR caused wheat to produce more adventitious roots per tiller, while adventitious root mass of faba bean decreased. The influence of FR on rooting depth (D75, i.e. depth of 75% of root biomass) was species specific, with higher FR levels causing a reduction in D75 in wheat, but a greater D75 in faba bean. Conclusions Our findings demonstrate the plasticity of adventitious roots; they are highly responsive to the R/FR level to which the shoot is exposed and to whether neighboring plants are of the same or a different species. This highlights the complexity of plants' responses to environmental cues and how they modify interspecific interactions.

Multi-Omics Approach Reveals Genes and Pathways Affected in Miller-Dieker Syndrome - Gowthami Mahendran; Kurtis Breger; Phillip J. McCown; Jacob P. Hulewicz; Tulsi Bhandari; Balasubrahmanyam Addepalli; Jessica A. Brown (Molecular Neurobiology, 2025)
Miller-Dieker syndrome (MDS) is a rare neurogenetic disorder resulting from a heterozygous deletion of 26 genes in the MDS locus on human chromosome 17. MDS patients often die in utero and only 10% of those who are born reach 10 years of age. Current treatments mostly prevent complications and control seizures. A detailed understanding of the pathogenesis of MDS through gene expression studies would be useful in developing precise medical approaches toward MDS. To better understand MDS at the molecular level, we performed RNA sequencing on RNA and mass spectrometry on total protein isolated from BJ (non-MDS) cells and GM06097 (MDS) cells, which were derived from a healthy individual and an MDS patient, respectively. Differentially expressed genes (DEGs) at the RNA and protein levels involved genes associated with phenotypic features reported in MDS patients (CACNG4, ADD2, SPTAN1, SHANK2), signaling pathways (GABBR2, CAMK2B, TRAM-1), and nervous system development (CAMK2B, BEX1, ARSA). Functional assays validated enhanced calcium signaling, downregulated protein translation, and cell migration defects in MDS. Interestingly, overexpression of methyltransferase-like protein 16 (METTL16), a protein encoded in the MDS locus, restored defects in protein translation, phosphor states of mTOR (mammalian target of rapamycin) pathway regulators, and cell migration in MDS cells. Although DNA- and RNA-modifying enzymes were among the DEGs and the intracellular SAM/SAH ratio was eightfold lower in MDS cells, global nucleoside modifications remained unchanged. Thus, this study identified specific genes and pathways responsible for the gene expression changes, which could lead to better therapeutics for MDS patients.

Investigating the neural network correlates of apathy, disinhibition, and executive dysfunction in active-duty United States Special Operations Forces - Natalie Gilmore; Isabella R. McKinney; Chieh-En J. Tseng; Douglas N. Greve; Chiara Maffei; Brian C. Healy; Nicole R. Zürcher; Jacob M. Hooker; Samantha L. Tromly; Daniel P. Perl; Kristen Dams-O’Connor; Christine L. Mac Donald; et al. (Brain Imaging and Behavior, 2025)

External loading-induced deformations of deteriorated pipelines rehabilitated with internal replacement technologies - Jacob Klingaman; Brad P. Wham; Patrick G. Dixon; Shideh Dashti (Tunnelling and Underground Space Technology, 2025)

Anthropogenic increase in organic carbon production and burial in two tropical Mexican crater lakes - Marttiina Rantala; Isabel Israde-Alcántara; Reza Safaierad; Wojciech Tylmann; Gilles Lepoint; Pierre Francus; John P. Smol; Carsten Meyer-Jacob; Christopher Grooms; Nadine Mattielli; Sarah Metcalfe; Paweł Etmański; et al. (Science of The Total Environment, 2025)

A holo-omics analysis shows how sugar kelp can boost gut health in Atlantic salmon - Jacob A. Rasmussen; Annette Bernhard; Laurène A. Lecaudey; Varsha Kale; Germana Baldi; Lene S. Myrmel; Martin Hansen; Jaelle C. Brealey; Sarah S.T. Mak; Ida B. Nielsen; Lorna Richardson; Lise Madsen; et al. (Aquaculture, 2025)

Growth and metabolic performance of house fly and black soldier fly larvae differ across densities and waste-based growth substrates - Asmus Toftkær Muurmann; Niels Thomas Eriksen; Jacob Agerbo Rasmussen; Morten T. Limborg; Jeffery K. Tomberlin; M.Thomas P. Gilbert; Simon Bahrndorff (Waste Management, 2025)

Influence of ozonized autohemotherapy at acupuncture points on stallion sperm quality - J.C. Ferraz Jacob; P. Junqueira Ferraz; L. Bastos Mello Rosa; H. Siqueira da Costa e Souza; M. Tainá Resende Ribeiro; A.C. Oliveira de Andrade; V. Souza de Freitas; F. Batalha Knackfuss; V.L. Teixeira de Jesus; J.G. Fernandes Joaquim (Journal of Equine Veterinary Science, 2025)

Dynamics of rain-triggered lahars and destructive power inferred from seismo-acoustic arrays and time-lapse camera correlation at Volcán de Fuego, Guatemala - Ashley R. Bosa; Gustavo Bejar; Gregory P. Waite; Jerry C. Mock; Armando Pineda; Jacob F. Anderson (Natural Hazards, 2025)
Lahars, or volcanic mudflows, are one of the most devastating natural, volcanic hazards. Deadly lahars, such as the one that occurred after the Nevado del Ruiz, Columbia eruption in 1985, in which at least 23,000 people tragically lost their lives, threaten the safety and well-being of humans, the economy, and the infrastructure of many of the communities living in the vicinity of volcanoes. Due to their complex flow behaviors, lahars remain a major challenge to those studying them. We present an analysis of several rain-triggered lahar events at Volcán Fuego in Guatemala using both seismic and infrasound monitoring to quantify both ground vibrations and low-frequency atmospheric sound waves associated with these mudflows. Geophysical data collected over this field campaign quantifies flow parameters such as velocities, stage and the frequency of these rain-triggered lahars. Time-lapse imagery of lahar flows is compared with filtered seismo-acoustic signal characteristics to ascertain stage predictions and relationship to stage fluxes. Using random forest regression models, we establish moderate correlations (correlation coefficient modes 0.48–0.53) with statistical significance ( p value = 0.01–0.02) between signal energetics and respective stage. Compiling a catalog of rain-triggered lahar events in Volcán de Fuego’s drainages over a season permits a dataset amenable to statistical analysis. Our goal is the development of new-generation geophysical monitoring tools that will be capable of remote and real-time estimation of flow parameters.

Delignification of Rosa hybrida cv. Rose Sherbet Seed Pericarp Using Deep Eutectic Solvents for Improved Seed Quality Parameters - Debshikha Dutta Roy; S. P. Jeevan Kumar; Ganesh B. Kadam; D. V. S. Raju; Uday Bhaskar Kethineni; K. V. Prasad; Samuel Jacob (Journal of Plant Growth Regulation, 2025)

Predictive alternating runs and random task-switching sequences produce dissociative switch costs in the Consonant–Vowel/Odd–Even task - Nicholas P. Maxwell; Mark J. Huff; Jacob M. Namias (Cognitive Processing, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Modeling the advective supply of Calanus finmarchicus to Stellwagen Bank as an indicator of sand lance foraging habitat, and the climate vulnerability of a National Marine Sanctuary - Cameron R. S. Thompson; Isabel A. Honda; Jacob P. Kritzer; Jackie Motyka; Jeffrey A. Runge; Rubao Ji (Frontiers in Marine Science, 2025)
The northern sand lance ( Ammodytes dubius ), a key species in the food web supporting the Stellwagen Bank National Marine Sanctuary (SBNMS), feeds primarily on the lipid-rich copepod Calanus finmarchicus . Climate change poses a significant threat to this dynamic, as C. finmarchicus populations are at the southern edge of their subarctic distribution and are vulnerable to warming waters and changing oceanographic conditions. Declines in the advective supply of C. finmarchicus to Stellwagen Bank could adversely affect sand lance populations and, consequently, the ecological and economic resources that depend on them. To quantify the connectivity between SBNMS and potential sources of C. finmarchicus , we used the Finite-Volume Community Ocean Model (FVCOM) coupled with Lagrangian particle tracking over the years 1978 to 2016. Numerical experiments revealed that Stellwagen Bank is highly connected to upstream areas in the Maine Coastal Current (MCC), where existing time series monitoring stations observe C. finmarchicus populations. The connectivity exhibited strong seasonal patterns, with peak connectivity occurring during spring and early summer, aligning with the sand lance feeding period on C. finmarchicus . We found significant interannual variability, influenced by changes in the strength of the MCC and circulation patterns in the western Gulf of Maine. Years with stronger MCC flow showed higher connectivity and a greater potential supply of C. finmarchicus particles to Stellwagen Bank. Conversely, periods of reduced flow corresponded with decreased connectivity, potentially limiting the availability of C. finmarchicus to sand lance populations. Meanwhile, observations from drifters and buoys since 2001 have documented decreases in MCC current speed which has been linked to a climate driven strengthening of southwesterly winds. These findings underscore the importance of pelagic habitat connectivity in assessing the climate vulnerability of marine protected areas (MPAs) like SBNMS. Furthermore, monitoring C. finmarchicus populations at upstream time series stations can provide information on downstream foraging habitat in MPAs, and potentially in other vulnerable areas of ecological and socioeconomic interest. By incorporating these indicators of connectivity and upstream C. finmarchicus population abundance into decision support tools, Sanctuary managers and stakeholders can make informed decisions to mitigate potential climate impacts.

Substrate stiffness dictates unique doxorubicin-induced senescence-associated secretory phenotypes and transcriptomic signatures in human pulmonary fibroblasts - Huixun Du; Jacob P. Rose; Joanna Bons; Li Guo; Taylor R. Valentino; Fei Wu; Jordan B. Burton; Nathan Basisty; Max Manwaring-Mueller; Priya Makhijani; Nan Chen; Veronica Chang; et al. (GeroScience, 2025)

Seasonal resource tracking and use of sea-ice foraging habitats by albatrosses and large petrels - Ewan D. Wakefield; Erin L. McClymont; Ana P.B. Carneiro; John P. Croxall; Jacob González-Solís; Hannah M.V. Granroth-Wilding; Lesley Thorne; Victoria Warwick-Evans; Andrew G. Wood; Jose C. Xavier; Richard A. Phillips (Progress in Oceanography, 2025)

The positive reinforcing effects of cocaine and opposite-sex social contact: roles of biological sex and estrus - Mark A. Smith; Samantha P. Armas; Jacob D. Camp; Hannah N. Carlson (Psychopharmacology, 2025)
Rationale Preclinical studies report that drug use and social contact mutually influence the reinforcing effects of one another. Most of these studies have used same-sex dyads exclusively, and the role of factors related to biological sex and hormonal fluctuations are not well understood. Objectives The purpose of this study was to examine the reinforcing effects of cocaine and social contact with an opposite-sex partner in male and female rats, and how these effects are modulated by ovarian hormones. Methods Male and female rats were trained in a nonexclusive choice procedure in which cocaine and social contact with an opposite-sex partner were simultaneously available on concurrent progressive ratio schedules of reinforcement. To examine the effects of ovarian hormones related to estrous cycling, Experiment 1 used naturally cycling, gonadally intact females, whereas Experiment 2 used ovariectomized females, and estrus was artificially induced with exogenous hormones. Results In both experiments, cocaine and social contact functioned as robust reinforcers, and there were no significant effects of biological sex or estrus status of the females. The positive reinforcing effects of both cocaine and social contact increased as a function of cocaine dose, indicating that contingent cocaine administration increases the reinforcing effects of social contact. Conclusions These data suggest that cocaine use among opposite-sex partners may enhance factors that contribute to social bonding.

After the n10: late oVEMP peaks in patients with unilateral vestibular loss and healthy volunteers - Alyssa C. Dyball; Xiao Ping Wu; Belinda Y. C Kwok; Chao Wang; Benjamin Nham; Jacob M. Pogson; Jonathan H. K. Kong; Rachael L. Taylor; Konrad P. Weber; Miriam S. Welgampola; Sally M. Rosengren (Experimental Brain Research, 2025)

Low densities and little change in water clarity characterize zebra mussel invasions near the southern extent of their range - Jacob A. Cianci-Gaskill; Anthony P. Thorpe; John R. Jones; Rebecca L. North (Biological Invasions, 2025)
Invasive species are often assumed to have measurable impacts throughout their potential range, but this is not always true. This study evaluated whether zebra mussels ( Dreissena polymorpha ) were causing an increase in water clarity near the southern edge of their North American expansion using a 40+ year dataset. We looked for abrupt shifts and long-term trends in water clarity and compared these to the estimated zebra mussel invasion date for 7 reservoirs in Missouri, USA. We also looked at water clarity in 26 non-invaded reservoirs to evaluate whether zebra mussel impacts were being masked by variation in environmental factors. Collectively, our analyses provide a weight of evidence based on a lack of consistent shifts in water clarity corresponding with zebra mussel invasions. Mussel establishment did not increase water clarity, likely because densities were too low to result in a measurable impact. The highest zebra mussel density we observed was 65 mussels m −2 , an order of magnitude less than in systems where they have had a sustained impact. Low densities could be due to a combination of sublethal environmental conditions such as warm water temperatures, suspended inorganic particulates, fluctuating water levels, and reduced oxygen concentrations, as well as limited hard substrata or predation by fish. While additional study is required to understand which, if any, of these factors may be limiting zebra mussel establishment in Missouri, our study shows that dreissenids are not having an impact as elsewhere throughout their range, suggesting that how an invader alters ecosystem functions is critical to determining its impact.

Site‐Specific Nutrient Data Reveal the Importance of Soils in Driving the Mycorrhizal Make‐Up of Woody Vegetation Worldwide - Xiaobin Hua; Christopher H. Lusk; Ian A. Dickie; Stephen Adu‐Bredu; Kathryn J. Allen; Viviana Araus; Laurent Augusto; Pavel Barsukov; David Bauman; Félix Brédoire; David F. R. P. Burslem; James W. Dalling; et al. (Global Ecology and Biogeography, 2025)
Aim Arbuscular mycorrhizas (AM) and ectomycorrhizas (ECM) have different impacts on nutrient cycling, carbon storage, community dynamics and enhancement of photosynthesis by rising CO 2 . Recent global analyses have concluded that patterns of AM/ECM dominance in forests worldwide are shaped by climate, with soil nutrients contributing negligible additional explanatory power. However, their reliance on nutrient data from GIS surfaces masks important local influences of parent material, topography and soil age on soil nutrient status. We asked if use of site‐specific nutrient data reveals a more important role for nutrients. Time Period Present day. Location Global dataset comprising 703 sites, encompassing forests, savanna/woodlands, shrublands and deserts on all continents except Antarctica. Taxa Studied Arborescent plants, including angiosperms, gymnosperms and tree ferns. Methods Generalised Additive Models for Location, Scale and Shape (GAMLSS) to determine the effects of climate variables, soil nitrogen and soil phosphorus on the proportional representation of ECM and of non‐mycorrhizal species (NM) in woody vegetation. Results GAMLSS showed a strong negative relationship of ECM representation with mean annual temperature (MAT), and a strong negative relationship with soil total nitrogen. NM representation was highest on dry sites and phosphorus‐poor sites. Reanalysis showed that GIS‐derived soil nutrient data had less explanatory power than site‐specific nutrient data, and resulted in poorer model fits. Conclusions Our results support the long‐held belief that soil nutrients as well as climate influence the relative fitness of different mycorrhizal syndromes worldwide, and demonstrate the value of using site‐specific nutrient data. Soil nutrients should be considered when predicting the impact of climate change on the mycorrhizal composition of vegetation and resulting shifts in ecosystem processes.

Critical perspectives on advancing antibiotic resistant gene (ARG) detection technologies in aquatic ecosystems - Zainab N. Nassereddine; Somie D. Opara; Oliver A. Coutinho; Florent Qyteti; Reeghan Book; Matthew P. Heinicke; Jacob Napieralski; Sonia M. Tiquia-Arashiro (Science of The Total Environment, 2024)

Controls on spatial variation in porewater methane concentrations across United States tidal wetlands - Erika L. Koontz; Sarah M. Parker; Alice E. Stearns; Brian J. Roberts; Caitlin M. Young; Lisamarie Windham-Myers; Patricia Y. Oikawa; J. Patrick Megonigal; Genevieve L. Noyce; Edward J. Buskey; R. Kyle Derby; Robert P. Dunn; et al. (Science of The Total Environment, 2024)

Toxicity of crude oil-derived polar unresolved complex mixtures to Pacific herring embryos: Insights beyond polycyclic aromatic hydrocarbons - Maxwell L. Harsha; Yanila Salas-Ortiz; Alysha D. Cypher; Ed Osborn; Eduardo Turcios Valle; Jacob L. Gregg; Paul K. Hershberger; Yuri Kurerov; Sarah King; Aleksandar I. Goranov; Patrick G. Hatcher; Anastasia Konefal; et al. (Science of The Total Environment, 2024)

An investigation of personality in the Creek Chub, Semotilus atromaculatus - Jacob P. Barrett; Mollie F. Cashner (Environmental Biology of Fishes, 2024)
Intraspecific variation in personality traits is increasingly recognized as an important driver of ecological processes, particularly within the context of species invasions. However, relatively few studies have investigated personality in native fauna with more localized dispersal patterns, and information regarding the existence of personality in stream fishes native to the southeastern US is particularly lacking. In this study, we investigated personality in a native and widespread minnow species, the Creek Chub ( Semotilus atromaculatus ). Because of its piscivorous diet, use of its nests by nest-associating minnows, and its role as a colonizer of intermittent streams, the Creek Chub is an appropriate species for investigating the broad importance of personality-dependent processes to stream communities. We identified personality traits by estimating the repeatability of sociability, boldness, exploration, and activity in two separate behavioral assays and interpreted correlations between traits as evidence of behavioral syndromes. We did not detect repeatability for measures of sociability, possibly due to predatory interactions within this species. However, boldness, exploration, and activity were significantly repeatable and positively correlated, pointing to the existence of a bold-exploratory-active syndrome in this species. Larger individuals tended to be less active, and, despite a relatively small sample size, we detected significant differences between source populations for measures of boldness. This is the first study to identify the existence of a behavioral syndrome in Creek Chub and points to the importance of considering the role of personality in ecological processes involving native fauna.

Spawning migration, sex-specific home ranges, and seasonal site fidelity in a lacustrine population of Bowfin (Amia ocellicauda) - James R. Jackson; Gregory R. Jacobs; Alexander W. Latzka; Tomomi Landsman; Brian P. Young; Amy R. McCune (Environmental Biology of Fishes, 2024)

Identification and Molecular Characterization of Clogmia (Telmatoscopus) albipunctatus (Drain Fly) Larva in a Rare Case of Urinary Myiasis in a Domestic Dog in India - Bindu Lakshmanan; Jacob Alexander; Amrutha Anand; Krishnanunni Nair P. K; Devada K (Acta Parasitologica, 2024)

Trends in sedimentary Cladocera and metal(loid)s from Williams Lake (Washington, USA) track ∼125 years of trans-boundary contamination from smelter emissions in the upper Columbia River valley - Jamie A. Would; Kathleen M. Rühland; Brigitte Simmatis; Marlene S. Evans; Carsten Meyer-Jacob; John P. Smol (Science of The Total Environment, 2024)

Letter to the editors regarding “Inter-laboratory validation of bioaccessibility testing for metals” by Henderson et al. (2014) - P.E. Rasmussen; P. Huntsman; T.M. Singer; M.N. Jacobs; C.C. Trevithick-Sutton (Regulatory Toxicology and Pharmacology, 2024)

Evaluating soil quality and carbon storage in Western Ghats Forests, Karnataka, India, for sustainable forest management - Kaushik Saha; K. S. Anil Kumar; K. M. Nair; M. Lalitha; Parinita Das; S. P. Maske; P. James Jacob; M. D. Jessy; K. S. Karthika; V. Ramamurthy; N. G. Patil (Environmental Monitoring and Assessment, 2024)

The overlooked biodiversity loss - Morten T. Limborg; Caroline S. Winther-Have; Naia Morueta-Holme; M. Thomas P. Gilbert; Jacob A. Rasmussen (Trends in Ecology & Evolution, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Fire season and time since fire determine arbuscular mycorrhizal fungal trait responses to fire - Jacob R. Hopkins; Thomas P. McKenna; Alison E. Bennett (Plant and Soil, 2024)
Background and aims Arbuscular mycorrhizal (AM) fungi are common mutualists in grassland and savanna systems that are adapted to recurrent fire disturbance. This long-term adaptation to fire means that AM fungi display disturbance associated traits which should be useful for understanding environmental and seasonal effects on AM fungal community assembly. Methods In this work, we evaluated how fire effects on AM fungal spore traits and community composition vary with fire season (Fall vs. Spring) and time since fire. We tested this by analyzing AM fungal spore traits (e.g., colorimetric, sporulation, and size) from a fire regime experiment. Results Immediately following Fall and Spring fires, spore pigmentation darkened (became less hyaline); however, this trait response was not linked to fire driven changes in spore community composition and likely implies a plastic spore pigmentation response to fire. Six months after Fall fires, spores in burned plots were lower in volume, produced less color rich pigment, and had higher sporulation rates, and these differences in spore traits were associated with shifts in AM fungal spore communities demonstrating environmental filtering. Conclusion Fire drove plastic and longer-term changes in AM fungal spore traits and community assembly that varied with fire season (stronger effects in Fall) and time since fire. This demonstrates the utility of applying trait-based approaches to microbial community assembly, and the importance of considering changes in community assembly across time.

Influence of wind on kittiwake Rissa tridactyla flight and offshore wind turbine collision risk - Jacob G. Davies; Philipp H. Boersch-Supan; Gary D. Clewley; Elizabeth M. Humphreys; Nina J. O’Hanlon; Judy Shamoun-Baranes; Chris B. Thaxter; Ewan Weston; Aonghais S. C. P. Cook (Marine Biology, 2024)

Antinociceptive and anti-inflammatory activities of Ayapana triplinervis essential oil rich in thymohydroquinone dimethyl ether from Brazil - Luana de Sousa P. Barros; Ellen Nayara Silva de Jesus; Maria Juliana da L. Froz; Renata Cunha Silva; Pedro Iuri C. da Silva; Anderson B. de Lima; Jofre Jacob S. Freitas; Rosa Helena V. Mourão; William N. Setzer; Joyce Kelly R. da Silva; José Nazareno C. Negrão; Pablo Luis B. Figueiredo (Inflammopharmacology, 2024)

Mild Traumatic Brain Injury and Career Stage Associate with Visible Perivascular Spaces in Special Operations Forces Soldiers - Jacob R. Powell; Xiaopeng Zong; Joshua M. Weinstein; Stephen M. DeLellis; Shawn F. Kane; Gary E. Means; Jason P. Mihalik (Annals of Biomedical Engineering, 2024)

Multiple Pleistocene refugia for Arctic Bell‐Heather revealed with genomic analyses of modern and historic plants - Cassandra Elphinstone; Fernando Hernández; Marco Todesco; Jean‐Sébastien Légaré; Winnie Cheung; Paul C. Sokoloff; Annika Hofgaard; Casper T. Christiansen; Esther R. Frei; Esther Lévesque; Gergana N. Daskalova; Haydn J. D. Thomas; et al. (Journal of Biogeography, 2024)
Aim Arctic plants survived the Pleistocene glaciations in unglaciated refugia. The number, ages, and locations of these refugia are often unclear. We use high‐resolution genomic data from present‐day and Little‐Ice‐Age populations of Arctic Bell‐Heather to re‐evaluate the biogeography of this species and determine whether it had multiple independent refugia or a single refugium in Beringia. Location Circumpolar Arctic and Coastal British Columbia (BC) alpine. Taxon Cassiope tetragona L., subspecies saximontana and tetragona , outgroup C. mertensiana (Ericaceae). Methods We built genotyping‐by‐sequencing (GBS) libraries using Cassiope tetragona tissue from 36 Arctic locations, including two ~250‐ to 500‐year‐old populations collected under glacial ice on Ellesmere Island, Canada. We assembled a de novo GBS reference to call variants. Population structure, genetic diversity and demography were inferred from PCA, ADMIXTURE, fastsimcoal2, SplitsTree, and several population genomics statistics. Results Population structure analyses identified 4–5 clusters that align with geographic locations. Nucleotide diversity was highest in Beringia and decreased eastwards across Canada. Demographic coalescent analyses dated the following splits with Alaska: BC subspecies saximontana (5 mya), Russia (~1.4 mya), Europe (>200–600 kya), and Greenland (~60 kya). Northern Canada populations appear to have formed during the current interglacial (7–9 kya). Admixture analyses show genetic variants from Alaska appear more frequently in present‐day than historic plants on Ellesmere Island. Conclusions Population and demographic analyses support BC, Alaska, Russia, Europe and Greenland as all having had independent Pleistocene refugia. Northern Canadian populations appear to be founded during the current interglacial with genetic contributions from Alaska, Europe and Greenland. We found evidence, on Ellesmere Island, for continued recent gene flow in the last 250–500 years. These results suggest that a re‐analysis of other Arctic species with shallow population structure using higher resolution genomic markers and demographic analyses may help reveal deeper structure and other circumpolar glacial refugia.

Shell temperature: How shall we tell if a still gosling is under the eggshell? - Valeriy G. Narushin; Michael N. Romanov; Louis Gressier; Elouann Jacob; Attila Salamon; Sabine Klein; John P. Kent (Theriogenology, 2024)

Optimized bimetallic ratios for durable membrane catalyst-film reactors in treating nitrate-polluted water - Juliana Levi; Bongyeon Jung; Hunter P. Jacobs; Yihao Luo; Chung-Seop Lee; Kiheon Hong; Min Long; Juan Donoso; Sergi Garcia-Segura; Michael S. Wong; Bruce E. Rittmann; Paul Westerhoff (Science of The Total Environment, 2024)

Paleodiet reconstructions and human utilization of middle Holocene Equus ferus in northwest Europe - Jacob Kveiborg; Antigone Uzunidis; Lutz Klassen; Florian Klimscha; Niels Nørkjær Johannsen; Uffe Lind Rasmussen; Michael P. Richards; Jens-Christian Svenning (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Effects of age on oxidative stress and locomotion in the pollinator, Megachile rotundata - Jacob B. Pithan; Joseph P. Rinehart; Kendra J. Greenlee; Giancarlo López-Martínez (Journal of Insect Physiology, 2024)

Nursery provision of red-algal habitats in temperate Algoa Bay, South Africa - N. C. James; A. G. Jacobs; M. Gayiza; L. R.D. Human; P. P. Steyn; A. T. Bernard; G. M. Rishworth (Marine Biology, 2024)
This study examines the importance of both macroalgal heterogeneity and specific macroalgal species or morphotypes to nursery provision for juvenile sparids ( Diplodus capensis and Sarpa salpa ) in a shallow (< 2 m), sheltered rocky cove in warm-temperate Algoa Bay, South Africa. The rocky cove is comprised of a mosaic of two main benthic habitats; canopy-forming Plocamium corallorhiza beds on rocky outcrops and flat reef dominated by low growing red algae morphotypes. We assessed macroalgal communities and the trophic ecology (stomach contents and isotopes), abundance and size structure of D. capensis and S. salpa in the two different benthic habitats and the resources/food associated with the dominant macroalgae species/morphotypes. We found high densities of S. salpa and D. capensis , in both high profile reef (rocky outcrops) and low profile (flat) reef. Within this habitat mosaic resources (epiphytes and macroinvertebrates) were more abundant in the non-canopy forming low growing macroalgae ( Laurencia spp. and coralline turf algae) and these algae were also assimilated in the diets of both sparids. The high abundance of both juvenile S. salpa and D. capensis in high profile and low profile reef, suggests that within this mosaic of habitats these species may be using canopy-forming algae in the high profile reef for shelter and non-canopy forming algae in both the high and low profile reef for food. This shows that macroalgal habitats comprising several morphotypes have the potential to support higher juvenile diversity and abundance through both food provision and shelter.

Optimizing the dietary concentration of marine microalgae Nannochloropsis salina and Chaetoceros calcitrans for the enhancement of productivity and nutritional composition of the rotifer Brachionus rotundiformis (Tschugunoff, 1921) - Sruthy C. Sunil; Aswathy Krishnan; Vinu Jacob; Sijo P. Varghese; Earath R. Chaithanya (Journal of Applied Phycology, 2024)

Stormwise: Innovative Forest Management to Promote Storm Resistance in Roadside Forests - Thomas Worthley; Amanda Bunce; Anita T Morzillo; Chandi Witharana; Zhe Zhu; Jacob Cabral; Emlyn Crocker; Nicholas Cranmer; Steven DiFalco; Daniel Hale; Durga Joshi; Danielle P Kloster; et al. (Journal of Forestry, 2024)
A growing proportion of forested landscapes are interspersed with human infrastructure, such as utility lines and roads, increasing the potential for tree-failure consequences due to storms and other causes. Utilities and other institutions have strong incentives to reduce such interactions and allocate substantial resources to risk reduction, but trees and forests in densely populated landscapes also provide significant amenities to society. We present a generalized framework for “Stormwise” forest management, focused on resistance of roadside forests to storms, based on elements of arboricultural and silvicultural practice and tree biomechanics and architecture. We detail results of a multidisciplinary research program focused on management outcomes, opportunities and barriers to implementation, and allocation of investment based on physical and social landscape characteristics. We discuss initial findings, the potential for widespread adoption of resilience-focused management in roadside and infrastructure-adjacent forests, and the importance of such work, considering a changing climate. Study Implications: The research and implementation program we detail here illustrates the potential for “Stormwise” forest management to reduce storm-damage recovery costs, result in fewer and shorter-duration power and transportation interruptions, and allow for low-investment ground-based management in future forest entries. We illustrate a multifaceted, interdisciplinary research program that links the geospatial, social, and biophysical components of understanding forest infrastructure systems. We illustrate how implementation of Stormwise management has the potential to benefit stakeholders such as residents and utilities, offset the substantial economic costs of tree-related power outages, and reduce societal disruptions associated with interactions between trees and infrastructure during storms.

Cycling of fluid-mobile elements through the forearc: Insights from the Cl, B, and Li isotope composition of Costa Rican spring fluids - Jacob P. Helper; Jaime D. Barnes; J. Maarten de Moor; Alejandro Rodríguez; Samuele Agostini; George Segee-Wright; Rudra Chatterjee; Daniel F. Stockli (Geochimica et Cosmochimica Acta, 2024)

Recommendations for the safe use of direct oral anticoagulants in patients with cirrhosis based on a systematic review of pharmacokinetic, pharmacodynamic and safety data - Maaike M. E. Diesveld; Daniëlle W. M. Jacobs- Pijnenburg; Rianne A. Weersink; Ina Barzel; Joost P. H. Drenth; Ton Lisman; Herold J. Metselaar; Margje H. Monster-Simons; Midas B. Mulder; Eline Okel; Katja Taxis; Sander D. Borgsteede (European Journal of Clinical Pharmacology, 2024)

Cost–benefit analysis of ecosystem modeling to support fisheries management - Matthew H. Holden; Eva E. Plagányi; Elizabeth A. Fulton; Alexander B. Campbell; Rachel Janes; Robyn A. Lovett; Montana Wickens; Matthew P. Adams; Larissa Lubiana Botelho; Catherine M. Dichmont; Philip Erm; Kate J. Helmstedt; et al. (Journal of Fish Biology, 2024)
Mathematical and statistical models underlie many of the world's most important fisheries management decisions. Since the 19th century, difficulty calibrating and fitting such models has been used to justify the selection of simple, stationary, single‐species models to aid tactical fisheries management decisions. Whereas these justifications are reasonable, it is imperative that we quantify the value of different levels of model complexity for supporting fisheries management, especially given a changing climate, where old methodologies may no longer perform as well as in the past. Here we argue that cost‐benefit analysis is an ideal lens to assess the value of model complexity in fisheries management. While some studies have reported the benefits of model complexity in fisheries, modeling costs are rarely considered. In the absence of cost data in the literature, we report, as a starting point, relative costs of single‐species stock assessment and marine ecosystem models from two Australian organizations. We found that costs varied by two orders of magnitude, and that ecosystem model costs increased with model complexity. Using these costs, we walk through a hypothetical example of cost‐benefit analysis. The demonstration is intended to catalyze the reporting of modeling costs and benefits.

Grazing herbivores reduce herbaceous biomass and fire activity across African savannas - A. Tyler Karp; Sally E. Koerner; Gareth P. Hempson; Joel O. Abraham; T. Michael Anderson; William J. Bond; Deron E. Burkepile; Elizabeth N. Fillion; Jacob R. Goheen; Jennifer A. Guyton; Tyler R. Kartzinel; Duncan M. Kimuyu; et al. (Ecology Letters, 2024)
Fire and herbivory interact to alter ecosystems and carbon cycling. In savannas, herbivores can reduce fire activity by removing grass biomass, but the size of these effects and what regulates them remain uncertain. To examine grazing effects on fuels and fire regimes across African savannas, we combined data from herbivore exclosure experiments with remotely sensed data on fire activity and herbivore density. We show that, broadly across African savannas, grazing herbivores substantially reduce both herbaceous biomass and fire activity. The size of these effects was strongly associated with grazing herbivore densities, and surprisingly, was mostly consistent across different environments. A one‐zebra increase in herbivore biomass density (~100 kg/km 2 of metabolic biomass) resulted in a ~53 kg/ha reduction in standing herbaceous biomass and a ~0.43 percentage point reduction in burned area. Our results indicate that fire models can be improved by incorporating grazing effects on grass biomass.

Diversity of haemoparasites in migratory small ruminants of Himalayas, India - Gopinath Devi; Putan Singh; Umesh Dimri; Siju Susan Jacob; Gauri Jairath; Jobin Jose Kattoor; P. Preena; Y. Ajith; Gorakh Mal; Rinku Sharma; Surender Kumar; Rajni Chaudhary; et al. (Small Ruminant Research, 2024)

Subchronic inhalation exposure to ultrafine particulate matter alters the intestinal microbiome in various mouse models - Candace Chang; Rajat Gupta; Farzaneh Sedighian; Allen Louie; David M. Gonzalez; Collin Le; Jae Min Cho; Seul-Ki Park; Jocelyn Castellanos; To-Wei Ting; Tien S. Dong; Nerea Arias-Jayo; et al. (Environmental Research, 2024)

Evidence of sociality and group foraging in Antarctic minke whales (Balaenoptera bonaerensis) - Jenny A. Allen; David E. Cade; Caroline B. Casey; Sarah Weindorf; David W. Johnston; Jacob M.J. Linsky; Jeremy A. Goldbogen; Doug P. Nowacek; Ari S. Friedlaender (Behavioral Ecology and Sociobiology, 2024)

Assessing preconception exposure to environmental chemicals and fecundity: Strategies, challenges, and research priorities - Jillian Ashley-Martin; Jacob Hammond; Maria P. Velez (Reproductive Toxicology, 2024)

Multiple Ecological Axes Drive Molecular Evolution of Cone Opsins in Beloniform Fishes - Katherine D. Chau; Frances E. Hauser; Alexander Van Nynatten; Jacob M. Daane; Matthew P. Harris; Belinda S. W. Chang; Nathan R. Lovejoy (Journal of Molecular Evolution, 2024)

Mechanistic understanding of thermodynamic metastability of core-shell catalysts in the polymer electrolyte fuel cell catalyst layer durability - Navneet Goswami; Kate Chen; Xiaojing Wang; Jacob S. Spendelow; Rodney L. Borup; Partha P. Mukherjee (Chemical Engineering Journal, 2024)

Construction of relatedness matrices in autopolyploid populations using low-depth high-throughput sequencing data - Timothy P. Bilton; Sanjeev Kumar Sharma; Matthew R. Schofield; Michael A. Black; Jeanne M. E. Jacobs; Glenn J. Bryan; Ken G. Dodds (Theoretical and Applied Genetics, 2024)
Key message An improved estimator of genomic relatedness using low-depth high-throughput sequencing data for autopolyploids is developed. Its outputs strongly correlate with SNP array-based estimates and are available in the package GUSrelate. Abstract High-throughput sequencing (HTS) methods have reduced sequencing costs and resources compared to array-based tools, facilitating the investigation of many non-model polyploid species. One important quantity that can be computed from HTS data is the genetic relatedness between all individuals in a population. However, HTS data are often messy, with multiple sources of errors (i.e. sequencing errors or missing parental alleles) which, if not accounted for, can lead to bias in genomic relatedness estimates. We derive a new estimator for constructing a genomic relationship matrix (GRM) from HTS data for autopolyploid species that accounts for errors associated with low sequencing depths, implemented in the R package GUSrelate. Simulations revealed that GUSrelate performed similarly to existing GRM methods at high depth but reduced bias in self-relatedness estimates when the sequencing depth was low. Using a panel consisting of 351 tetraploid potato genotypes, we found that GUSrelate produced GRMs from genotyping-by-sequencing (GBS) data that were highly correlated with a GRM computed from SNP array data, and less biased than existing methods when benchmarking against the array-based GRM estimates. GUSrelate provides researchers with a tool to reliably construct GRMs from low-depth HTS data.

Sustainability assessment of peri-urban organic horticulture — A case study in the United Kingdom - Mustafa Ali; Lenny Koh; Adolf Acquaye; Jonathan Leake; Jacob Nickles; Toby P. Evans; Gareth Roberts; Douglas Kemp (The International Journal of Life Cycle Assessment, 2024)
Purpose There is a growing concern about the resilience and sustainability of horticultural production in the United Kingdom (UK) as a result of high energy costs and insufficient local labour, causing over-reliance on imports. In this study, we present an integrated environmental and economic assessment of organic peri-urban horticulture using primary data from a farm in Sheffield. Methods This study includes a farm-to-gate hybrid life cycle assessment (LCA) using the ReCIPE (H) approach for the functional unit of 1-kg tomatoes produced in an unheated polytunnel without supplementary lighting, and 1 kg of field-grown courgettes. All analyses were conducted in SimaPro software using environmental data from the ecoinvent database. Results were compared with those from a systematic literature review of similar studies. Results We found that the production of organic tomatoes and courgettes resulted in a global warming potential (GWP) of 0.61 kg CO 2 -eq and 0.11 kg CO 2 -eq respectively using a process-based LCA approach. Using a hybrid LCA approach, however, yielded a GWP of 3.53 kg CO 2 -eq and 1.70 kg CO 2 -eq for the production of organic tomatoes and courgettes respectively. An additional scenario included farmgate-to-warehouse transportation for both domestic and imported produce from Spain, but found that the GWP of tomatoes in the case study was 1.87 times higher than those from Spain. Economic analysis showed that the marginal increase in the prices of tomatoes and courgettes from the case study farm was 4.6 and 5.15 times less than the market prices. Conclusion We conclude that the studied production system is both economically and environmentally sustainable as compared to the existing scenario. Other potential benefits of peri-urban organic horticulture include employment, mental health, community cohesion, which remain to be explored in a future qualitative study. The present study is novel as it appears to be the first application of hybrid LCA to UK horticulture. The findings are highly topical given the recent horticultural supply constraints in the UK.

ELSSIE: A compact stereo spectral imager for planetary surface morphology and composition - Scott L. Murchie; Frank P. Seelos; Bethany L. Ehlmann; John D. Boldt; Lawrence E. Brown; Jacob M. Greenberg; Karl A. Hibbitts; W. Jeffrey Lees; David M. Linko; Joseph J. Linden; Graham P. Murphy; Jorge I. Núñez; et al. (Planetary and Space Science, 2024)

Geothermal Play Fairway Analysis, Part 2: GIS methodology - Jacob DeAngelo; John W. Shervais; Jonathan M. Glen; Dennis Nielson; Sabodh Garg; Patrick F. Dobson; Erika Gasperikova; Eric Sonnenthal; Lee M. Liberty; Drew L. Siler; James P. Evans (Geothermics, 2024)

Geothermal play fairway analysis, part 1: Example from the Snake River Plain, Idaho - John W. Shervais; Jacob DeAngelo; Jonathan M. Glen; Dennis L. Nielson; Sabodh Garg; Patrick Dobson; Erika Gasperikova; Eric Sonnenthal; Lee M. Liberty; Dennis L. Newell; Drew Siler; James P. Evans (Geothermics, 2024)

Exploring the microbial diversity of novel misos with metagenomics - Caroline Isabel Kothe; Jacob Agerbo Rasmussen; Sarah S.T. Mak; M. Thomas P. Gilbert; Joshua Evans (Food Microbiology, 2024)

Single-component multi-rate real time hybrid simulation pilot test on a composite structure - Jacob P. Waldbjoern; Sebastian Andersen; Jacob Herold Hoegh; Christian Berggreen (Engineering Structures, 2024)

Impacts of acid deposition and lake browning on long-term organic carbon storage in Canadian northern forest lakes - Carsten Meyer-Jacob; Andrew L. Labaj; Andrew M. Paterson; Daniel Layton-Matthews; John P. Smol (Journal of Paleolimnology, 2024)

Possibly pathogenic bacteria in aerosols and foams as a result of aeration remediation in a polluted urban waterway - Joby Jacob; Ingrid Veras; Olga Calderόn; Holly A. Porter-Morgan; Joshua Tan; Harry E. Aguilar; Willis T. Elkins; Veronica P. Martinez Castro; Vania Fulton; Wesam K. Yousri (Folia Microbiologica, 2024)
Newtown Creek is a tributary of the Hudson River Estuary. It has a legacy of both industrial pollution and sewage pollution and has been designated a Superfund site. To ameliorate the chronically low levels of dissolved oxygen detected in the Creek, the New York City Department of Environmental Protection has been installing aerators. The abundance of various bacteria in the aerosols, foams, and water, at two sites in the Creek, was studied before, during, and after the aeration process. Additionally, aerosols and dispersed foams created by the aeration process were sampled and cultured to determine what unique taxa of bacteria could be grown and identified. Taxa including Actinobacteria and Firmicutes were prevalent in cultures taken from aerosols, whereas Gammaproteobacteria were prevalent in cultures taken from foam. Campylobacteria was found to have a significant presence in both samples taken after the aerators were turned off. These taxa include potentially pathogenic bacteria and are therefore of particular concern.

Further insights into killer whales Orcinus orca preying on white sharks Carcharodon carcharias in South Africa - A Towner; P Micarelli; D Hurwitz; MJ Smale; AJ Booth; C Stopforth; E Jacobs; FR Reinero; V Ricci; A Di Bari; S Gavazzi; G Carugno; et al. (African Journal of Marine Science, 2024)

Dispersant-enhanced photodissolution of macondo crude oil: A molecular perspective - David C. Podgorski; Jacob Walley; Matthew P. Shields; Deja Hebert; Maxwell L. Harsha; Robert G.M. Spencer; Matthew A. Tarr; Phoebe Zito (Journal of Hazardous Materials, 2024)

Spatial asynchrony and cross‐scale climate interactions in populations of a coldwater stream fish - George P. Valentine; Xinyi Lu; Evan S. Childress; C. Andrew Dolloff; Nathaniel P. Hitt; Matthew A. Kulp; Benjamin H. Letcher; Kasey C. Pregler; Jacob M. Rash; Mevin B. Hooten; Yoichiro Kanno (Global Change Biology, 2024)
Climate change affects populations over broad geographic ranges due to spatially autocorrelated abiotic conditions known as the Moran effect. However, populations do not always respond to broad‐scale environmental changes synchronously across a landscape. We combined multiple datasets for a retrospective analysis of time‐series count data (5–28 annual samples per segment) at 144 stream segments dispersed over nearly 1,000 linear kilometers of range to characterize the population structure and scale of spatial synchrony across the southern native range of a coldwater stream fish (brook trout, Salvelinus fontinalis ), which is sensitive to stream temperature and flow variations. Spatial synchrony differed by life stage and geographic region: it was stronger in the juvenile life stage than in the adult life stage and in the northern sub‐region than in the southern sub‐region. Spatial synchrony of trout populations extended to 100–200 km but was much weaker than that of climate variables such as temperature, precipitation, and stream flow. Early life stage abundance changed over time due to annual variation in summer temperature and winter and spring stream flow conditions. Climate effects on abundance differed between sub‐regions and among local populations within sub‐regions, indicating multiple cross‐scale interactions where climate interacted with local habitat to generate only a modest pattern of population synchrony over space. Overall, our analysis showed higher degrees of response heterogeneity of local populations to climate variation and consequently population asynchrony than previously shown based on analysis of individual, geographically restricted datasets. This response heterogeneity indicates that certain local segments characterized by population asynchrony and resistance to climate variation could represent unique populations of this iconic native coldwater fish that warrant targeted conservation. Advancing the conservation of this species can include actions that identify such priority populations and incorporate them into landscape‐level conservation planning. Our approach is applicable to other widespread aquatic species sensitive to climate change.

Observing Antarctic Bottom Water in the Southern Ocean - Alessandro Silvano; Sarah Purkey; Arnold L. Gordon; Pasquale Castagno; Andrew L. Stewart; Stephen R. Rintoul; Annie Foppert; Kathryn L. Gunn; Laura Herraiz-Borreguero; Shigeru Aoki; Yoshihiro Nakayama; Alberto C. Naveira Garabato; et al. (Frontiers in Marine Science, 2023)
Dense, cold waters formed on Antarctic continental shelves descend along the Antarctic continental margin, where they mix with other Southern Ocean waters to form Antarctic Bottom Water (AABW). AABW then spreads into the deepest parts of all major ocean basins, isolating heat and carbon from the atmosphere for centuries. Despite AABW’s key role in regulating Earth’s climate on long time scales and in recording Southern Ocean conditions, AABW remains poorly observed. This lack of observational data is mostly due to two factors. First, AABW originates on the Antarctic continental shelf and slope where in situ measurements are limited and ocean observations by satellites are hampered by persistent sea ice cover and long periods of darkness in winter. Second, north of the Antarctic continental slope, AABW is found below approximately 2 km depth, where in situ observations are also scarce and satellites cannot provide direct measurements. Here, we review progress made during the past decades in observing AABW. We describe 1) long-term monitoring obtained by moorings, by ship-based surveys, and beneath ice shelves through bore holes; 2) the recent development of autonomous observing tools in coastal Antarctic and deep ocean systems; and 3) alternative approaches including data assimilation models and satellite-derived proxies. The variety of approaches is beginning to transform our understanding of AABW, including its formation processes, temporal variability, and contribution to the lower limb of the global ocean meridional overturning circulation. In particular, these observations highlight the key role played by winds, sea ice, and the Antarctic Ice Sheet in AABW-related processes. We conclude by discussing future avenues for observing and understanding AABW, impressing the need for a sustained and coordinated observing system.

Predicting preincubation parameters in goose eggs to reduce their hatching waste - Valeriy G. Narushin; Michael N. Romanov; Louis Gressier; Elouann Jacob; Attila Salamon; John P. Kent (Biosystems Engineering, 2023)

Chemodiversity controls microbial assimilation of soil organic carbon: A theoretical model - Jacob R. Weverka; Holly V. Moeller; Joshua P. Schimel (Soil Biology and Biochemistry, 2023)

Endophytic fungus Piriformospora indica mitigates moisture stress in rice by modifying root growth - Koya Madhuri Mani; M. Ameena; Joy Michel Johnson; K.N. Anith; P. Shalini Pillai; Jacob John; R. Beena (Rhizosphere, 2023)

The dynamic influence of subsurface geological processes on the assembly and diversification of thermophilic microbial communities in continental hydrothermal systems - Kenneth W.W. Sims; Cole M. Messa; Sean R. Scott; Andrew D. Parsekian; Andrew Miller; Abraham L. Role; Timothy P. Moloney; Everett L. Shock; Jacob B. Lowenstern; R. Blaine McCleskey; Matthew A. Charette; Bradley J. Carr; et al. (Geochimica et Cosmochimica Acta, 2023)

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Individual variation and repeatability of Atlantic tarpon Megalops atlanticus migrations in the southern US: implications for conservation and management - Lucas P. Griffin; Jacob W. Brownscombe; Aaron J. Adams; JoEllen K. Wilson; Grace A. Casselberry; Peter E. Holder; Alex Filous; Susan K. Lowerre-Barbieri; Steven J. Cooke; Andy J. Danylchuk (Marine Biology, 2023)

Strategies for safe management of hospital wastewater during the COVID-19 pandemic - A. Balakrishnan; M. M. Jacob; P. Senthil Kumar; A. Kapoor; M. Ponnuchamy; P. Sivaraman; M. Sillanpää (International Journal of Environmental Science and Technology, 2023)

Predictors of hippocampal tauopathy in people with and at risk for human immunodeficiency virus infection - Sophie Nader; Esma Karlovich; Etty P. Cortes; Ricardo Insausti; Gregory Meloni; Michelle Jacobs; John F. Crary; Susan Morgello (Journal of NeuroVirology, 2023)

Review of Solar Energetic Particle Prediction Models - Kathryn Whitman; Ricky Egeland; Ian G. Richardson; Clayton Allison; Philip Quinn; Janet Barzilla; Irina Kitiashvili; Viacheslav Sadykov; Hazel M. Bain; Mark Dierckxsens; M. Leila Mays; Tilaye Tadesse; et al. (Advances in Space Research, 2023)

Quantifying the linkages between California sea lion (Zalophus californianus) strandings and particulate domoic acid concentrations at piers across Southern California - Jayme Smith; Jacob A. Cram; Malena P. Berndt; Vanessa Hoard; Dana Shultz; Alissa C. Deming (Frontiers in Marine Science, 2023)
Domoic acid-producing blooms of the diatom genus Pseudo-nitzschia are pervasive in coastal environments globally. Domoic acid, a neurotoxin, accumulates via trophic transfer into marine food webs and is often associated with mass marine mammal mortality and stranding events. In Southern California, California sea lions ( Zalophus californianus ) are an indicator species for food web impacts of domoic acid because they are abundant secondary consumers, sensitive to domoic acid intoxication, and are actively monitored by stranding networks. However, domoic acid exposure may occur a distance from where a sea lion ultimately strands. This spatiotemporal variation complicates coupling domoic acid observations in water to strandings. Therefore, we sought to quantify whether monitoring data from four pier sites across the region, covering nearly 700 km of coastline from 2015-2019, could be used to predict adult and subadult sea lion strandings along the 68 km Orange County coastline surveyed by the Pacific Marine Mammal Center. We found that increased sea lion strandings were often observed just prior to an increase in particulate domoic acid at the piers, confirming that clusters of subadult and adult sea lion strandings with clinical signs of domoic acid intoxication serve as indicators of bloom events. In addition, domoic acid concentrations at Stearns Wharf, nearly 200 km from stranding locations, best predicted increased total sea lion strandings, and strandings of sea lions with domoic acid intoxication symptoms. Particulate domoic acid concentrations greater than 0.05 μg/L at Stearns Wharf were linked to stranding probabilities in Orange County ranging from 2.2% to 55% per week, and concentrations of 0.25 μg/L resulted in weekly stranding probabilities ranging from 16% to 81% depending on the stranding scenario modeled.

Restoration ecology through the lens of coexistence theory - Lauren M. Hallett; Lina Aoyama; György Barabás; Benjamin Gilbert; Loralee Larios; Nancy Shackelford; Chhaya M. Werner; Oscar Godoy; Emma R. Ladouceur; Jacob E. Lucero; Christopher P. Weiss-Lehman; Jonathan M. Chase; et al. (Trends in Ecology & Evolution, 2023)

Corrigendum to “Large-scale nutrient and carbon dynamics along the river-estuary-ocean continuum” [Sci. Total Environ. 890 (2023) 164421] - Norbert Kamjunke; Holger Brix; Götz Flöser; Ingeborg Bussmann; Claudia Schütze; Eric P. Achterberg; Uta Ködel; Philipp Fischer; Louise Rewrie; Tina Sanders; Johannes Pein; Benjamin Jacob; et al. (Science of The Total Environment, 2023)

Pectin emulsions and emulgels: Bridging the correlation between rheology and microstructure - Mohan Kavya; Alan Ranjit Jacob; P Nisha (Food Hydrocolloids, 2023)

Avian biodiversity losses from grazing of high Andean páramo - Simon C. Mills; Edicson Parra Sanchez; Jacob B. Socolar; Chris Bousfield; Bryn Coffey; Jos Barlow; Jose Manuel Ochoa Quintero; Torbjørn Haugaasen; David P. Edwards (Biological Conservation, 2023)

P10-12: Toxicological impact of biogenic and anthropogenic secondary organic aerosols - F. Jacob; N. Houzel; L.Y. Alleman; E. Perdrix; S. Antherieu; C. Coeur; P. Genevray; G. Garçon; A. Tomas; J.-M. Lo Guidice (Toxicology Letters, 2023)

Coastal response to global warming during the Paleocene-Eocene Thermal Maximum - Glenn R. Sharman; Jacob A. Covault; Peter P. Flaig; Regan Dunn; Preston Fussee-Durham; Toti E. Larson; Timothy M. Shanahan; Kalli Dubois; John B. Shaw; James L. Crowley; Barry Shaulis (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

New insights into the chemical composition and formation mechanisms of secondary organic aerosols produced in the ozonolysis of limonene - F. Jacob; N. Houzel; P. Genevray; C. Clety; C. Coeur; E. Perdrix; L.Y. Alleman; S. Anthérieu; G. Garçon; G. Dhont; A. Cuisset; J.-M. Lo Guidice; et al. (Journal of Aerosol Science, 2023)

Gas migration signatures over the volcanic cratered seamount, off the Nicobar Islands in the Andaman Sea - G. Sriram; P. Dewangan; V. Yatheesh; A. Peketi; P. Mahesh; A. Mazumdar; V. P. Mahale; J. Jacob; K.M. Dubey; P. Kumar; C.K. Mishra; S. Gautham; et al. (Geo-Marine Letters, 2023)

Muconic acid production from algae hydrolysate as a high-value co-product of an algae biorefinery - Robert S. Nelson; Eric P. Knoshaug; Ryan Spiller; Nick Nagle; Stefanie VanWychen; Matthew Wiatrowski; Ryan Davis; Philip T. Pienkos; Jacob S. Kruger (Algal Research, 2023)

Understanding drivers of mercury in lake trout (Salvelinus namaycush), a top-predator fish in southwest Alaska's parklands - Krista K. Bartz; Michael P. Hannam; Tammy L. Wilson; Ryan F. Lepak; Jacob M. Ogorek; Daniel B. Young; Collin A. Eagles-Smith; David P. Krabbenhoft (Environmental Pollution, 2023)

Effects of occurrence data density on conservation prioritization strategies - Marlon E. Cobos; Claudia Nuñez-Penichet; Peter D. Campbell; Jacob C. Cooper; Fernando Machado-Stredel; Narayani Barve; Uzma Ashraf; Abdelghafar A. Alkishe; Eric Ng'eno; Rahul Raveendran Nair; P. Joser Atauchi; Adeola Adeboje; et al. (Biological Conservation, 2023)

Where are we now with European forest multi-taxon biodiversity and where can we head to? - Sabina Burrascano; Francesco Chianucci; Giovanni Trentanovi; Sebastian Kepfer-Rojas; Tommaso Sitzia; Flóra Tinya; Inken Doerfler; Yoan Paillet; Thomas Andrew Nagel; Bozena Mitic; Lourdes Morillas; Silvana Munzi; et al. (Biological Conservation, 2023)

Environmental formation of methylmercury is controlled by synergy of inorganic mercury bioavailability and microbial mercury‐methylation capacity - Benjamin D. Peterson; David P. Krabbenhoft; Katherine D. McMahon; Jacob M. Ogorek; Michael T. Tate; William H. Orem; Brett A. Poulin (Environmental Microbiology, 2023)
Methylmercury (MeHg) production is controlled by the bioavailability of inorganic divalent mercury (Hg(II) i ) and Hg‐methylation capacity of the microbial community (conferred by the hgcAB gene cluster). However, the relative importance of these factors and their interaction in the environment remain poorly understood. Here, metagenomic sequencing and a full‐factorial MeHg formation experiment were conducted across a wetland sulfate gradient with different microbial communities and pore water chemistries. From this experiment, the relative importance of each factor on MeHg formation was isolated. Hg(II) i bioavailability correlated with the dissolved organic matter composition, while the microbial Hg‐methylation capacity correlated with the abundance of hgcA genes. MeHg formation responded synergistically to both factors. Notably, hgcA sequences were from diverse taxonomic groups, none of which contained genes for dissimilatory sulfate reduction. This work expands our understanding of the geochemical and microbial constraints on MeHg formation in situ and provides an experimental framework for further mechanistic studies.

Effect of packaging materials and storage temperature on the physicochemical and microbial properties of ultrasonicated mature coconut water during storage - Anjitha Jacob; I.P. Sudagar; R. Pandiselvam; P. Rajkumar; M. Rajavel (Food Control, 2023)

Reintroduction of at-risk forest tree species using biotechnology depends on regulatory policy, informed by science and with public support - Douglass F. Jacobs; R. Kasten Dumroese; Andrea N. Brennan; Faith T. Campbell; Anna O. Conrad; Jason A. Delborne; Sara Fitzsimmons; David Flores; Christian P. Giardina; Leigh Greenwood; Juan A. Martín; Scott A. Merkle; et al. (New Forests, 2023)
Introduced pests (insects and pathogens) have rapidly increased the numbers of at-risk native forest tree species worldwide. Some keystone species have been functionally extirpated, resulting in severe commercial and ecological losses. When efforts to exclude or mitigate pests have failed, researchers have sometimes applied biotechnology tools to incorporate pest resistance in at-risk species to enable their reintroduction. Often erroneously equated solely with genetic engineering, biotechnology also includes traditional and genome informed breeding—and may provide a holistic approach toward applying genomic-based information and interventions to increase tree species’ pest resistance. Traditional tree breeding is responsible for successes to date, but new technologies offer hope to increase the efficiency of such efforts. Remarkable recent progress has been made, and for some at-risk species, novel biotechnological advances put reintroduction within reach. The high costs of reintroduction of at-risk species at necessary scale, however, will initially limit the pursuit to a few species. Successful deployment of pest resistant material may require improved species-specific knowledge and should integrate into and leverage existing reforestation systems, but these operations are sometimes rare where pest threats are greatest. While use of some biotechnologies, such as traditional tree breeding, are commonplace, others such as genetic engineering are controversial and highly regulated, yet may be the only viable means of achieving reintroduction of some at-risk species. Efforts to modify policy toward allowing the use of appropriate biotechnology, especially genetic engineering, have lagged. Provided that risk-benefits are favorable, policy is likely to follow with public opinion; in some countries, society is now increasingly open to using available biotechnologies. Continued engagement using the most recent advances in social science to build public trust, combined with a science-based collaboration among land managers and regulators, will generate the collective momentum needed to motivate policymakers to act rapidly given the speed at which forest health threats unfold and the large areas they affect.

A framework for establishing a rapid ‘Ōhi‘a death resistance program - Blaine C. Luiz; Christian P. Giardina; Lisa M. Keith; Douglass F. Jacobs; Richard A. Sniezko; Marc A. Hughes; James B. Friday; Philip Cannon; Robert Hauff; Kainana Francisco; Marian M. Chau; Nicklos Dudley; et al. (New Forests, 2023)
Metrosideros polymorpha Gaud. (‘ōhi‘a) is the most abundant native forest tree in Hawai‘i and a keystone species of cultural, ecological, and economic importance. ‘Ōhi‘a forests, particularly on Hawaiʻi Island, are being severely impacted by Rapid ‘Ōhi‘a Death (ROD), which is caused by the fungal pathogens Ceratocystis lukuohia and C. huliohia . ROD is characterized by branch dieback, crown wilting, and mortality. Initial disease resistance screening of four varieties of M. polymorpha with C. lukuohia demonstrated that varieties may differ in susceptibility. Several survivors of field or screening-based infections still exist, providing strong impetus for the establishment of the ‘Ōhiʻa Disease Resistance Program (ʻŌDRP). Here, we outline a framework for guiding the ʻŌDRP throughout the process of identifying and developing ROD resistance in M. polymorpha and, possibly, all Hawaiian Metrosideros species. Core ʻŌDRP projects include: (1) evaluating and operationalizing methods for greenhouse-based production and screening of test plants; (2) greenhouse screening of seedlings and rooted cuttings sampled from native Metrosideros throughout Hawaiʻi; (3) establishing field trials to validate results from greenhouse assays; (4) understanding environmental and genetic drivers of resistance to characterize the durability of resistance to ROD; (5) developing remote sensing and molecular methods to rapidly detect ROD-resistant individuals; and (6) conducting breeding trials to improve the degree and durability of ROD resistance. Ultimately, the ʻŌDRP seeks to produce ROD-resistant material for the perpetuation of M. polymorpha across Hawai‘i, with the goal of preserving the ecology, culture, and communities that are dependent on this tree species.

Rapidly Changing Range Limits in a Warming World: Critical Data Limitations and Knowledge Gaps for Advancing Understanding of Mangrove Range Dynamics in the Southeastern USA - Rémi Bardou; Michael J. Osland; Steven Scyphers; Christine Shepard; Karen E. Aerni; Jahson B. Alemu I; Robert Crimian; Richard H. Day; Nicholas M. Enwright; Laura C. Feher; Sarah L. Gibbs; Kiera O’Donnell; et al. (Estuaries and Coasts, 2023)
Climate change is altering species’ range limits and transforming ecosystems. For example, warming temperatures are leading to the range expansion of tropical, cold-sensitive species at the expense of their cold-tolerant counterparts. In some temperate and subtropical coastal wetlands, warming winters are enabling mangrove forest encroachment into salt marsh, which is a major regime shift that has significant ecological and societal ramifications. Here, we synthesized existing data and expert knowledge to assess the distribution of mangroves near rapidly changing range limits in the southeastern USA. We used expert elicitation to identify data limitations and highlight knowledge gaps for advancing understanding of past, current, and future range dynamics. Mangroves near poleward range limits are often shorter, wider, and more shrublike compared to their tropical counterparts that grow as tall forests in freeze-free, resource-rich environments. The northern range limits of mangroves in the southeastern USA are particularly dynamic and climate sensitive due to abundance of suitable coastal wetland habitat and the exposure of mangroves to winter temperature extremes that are much colder than comparable range limits on other continents. Thus, there is need for methodological refinements and improved spatiotemporal data regarding changes in mangrove structure and abundance near northern range limits in the southeastern USA. Advancing understanding of rapidly changing range limits is critical for foundation plant species such as mangroves, as it provides a basis for anticipating and preparing for the cascading effects of climate-induced species redistribution on ecosystems and the human communities that depend on their ecosystem services.

Influence of phosphate fertilizers on the radioactivity of agricultural soils and tobacco plants in Kenya, Tanzania, and Uganda - Dennis A. Mwalongo; Nils H. Haneklaus; Fernando P. Carvalho; Jacob B. Lisuma; Thomas T. Kivevele; Kelvin M. Mtei (Environmental Science and Pollution Research, 2023)
Three brands of NPK fertilizers that contain variable concentrations of natural radioactivity are commonly used in tobacco plantations in Kenya, Tanzania, and Uganda. Tobacco plants are known for hyper-accumulation of natural radionuclides, particularly 238 U. This study investigated if the elevated radioactivity in phosphate fertilizers could enhance radioactivity in soils and tobacco plant leaves. The 232 Th, 238 U, and 40 K radionuclide levels in NPK-fertilized soils and tobacco leaves were measured using gamma-ray spectroscopy. The research included a one-year reference experiment with tobacco growing in plots, a ten-year semi-controlled experiment in well-managed tobacco farms, and a field survey of radioactivity in soils and tobacco leaves at three traditional tobacco fields in Migori (Kenya), Urambo (Tanzania), and Kanungu (Uganda). The findings demonstrated that soils and tobacco leaves exposed to NPK fertilizers with increased radioactivity had activity concentrations of 232 Th, 238 U, and 40 K that were considerably higher (at all sites) than in the control samples (with no use of NPK fertilizers). As the continued application of NPK fertilizers raises concentrations of 232 Th, 238 U, and 40 K in agricultural soils, the study assessed radiological risks for humans from exposure to agricultural soils enriched with phosphate fertilizers, and it was found to be below the exposure limit of 1 mSvy -1 suggested by the International Commission on Radiological Protection (ICRP). However, tobacco consumers, both by snuffing and smoking, may face significant radiological risks, as the snuffing and smoking resulted in effective doses that were 2.41 to 6.53 and 1.14 to 2.45 times greater than the average yearly dose that the general public receives from inhalation of natural radionuclides (United Nations Scientific Committee on Atomic Radiations estimates). Furthermore, the results indicate that the lifetime excess cancer risk for tobacco snuffers and smokers ranged from 5 × 10 -5 to 24.48 × 10 -3 and 2.0 × 10 -5 to 9.18 × 10 -3 , respectively. The influence of phosphorus-derived fertilizer containing relatively high natural radioactivity, potential human radiation exposure, and radiological risk due to gamma radionuclides is estimated and discussed. The results reveal that applying phosphate fertilizers enhances natural radioactivity in soil and is subsequently influenced by soil to tobacco plant uptake. Therefore, the study recommends that countries use fertilizers with lower radionuclide content to conserve soil quality and reduce gamma-emitting radionuclides in tobacco plants.

Promoting self-determination, minimizing green gentrification, and maximizing community benefits in urban forestry expansion: A systematic review - Aviva Wolf-Jacobs; John P. Wilson; Esther Margulies (Urban Forestry & Urban Greening, 2023)

Ocean drifter velocity data assimilation, Part 1: Formulation and diagnostic results - Robert W. Helber; Scott R. Smith; Gregg A. Jacobs; Charlie N. Barron; Matt J. Carrier; Clark D. Rowley; Hans E. Ngodock; Max Yaremchuk; Ivo Pasmans; Brent P. Bartels; Chris J. DeHaan (Ocean Modelling, 2023)

Use of ozonated sunflower oil in the treatment of infectious endometritis in mares - Naiane F Oliveira; Camila S Ferreira; Luis F Silva; Isadora P Santos; Julio C Jacob; Bruno A Penna; Aline E Pinna (Journal of Equine Veterinary Science, 2023)

Impacts of anthropogenic pressures on underwater light conditions and diatom functional group distributions in mountain lakes - Sanna Atti; Marttiina V. Rantala; Andrea Lami; Carsten Meyer-Jacob; John P. Smol; Jan Weckström; Liisa Nevalainen (Journal of Paleolimnology, 2023)
Underwater light availability and exposure of ultraviolet radiation (UV) in mountain lakes is mainly controlled by dissolved organic matter and ice cover. However, both of these factors are affected by climate warming and other anthropogenic pressures. Still, little is known of the impacts of long-term fluctuations in underwater light conditions onto functional distribution of diatoms, species sensitive to changes in climate and UV penetration in mountain lakes. Two mountain lakes in the Italian Alps were analysed using paleolimnological approaches to investigate impacts of anthropogenic pressures (e.g., climate warming, acidification) on underwater light availability, exposure to UV and diatom functional group distributions, focusing on the post-industrial era. Contemporary diatom communities were collected from the main habitats in the shallow, high irradiance littoral zones of these lakes and geochemical proxies describing the development of lake-water transparency and carbon dynamics were analyzed from the sediment cores covering the time period from ca. 1400 CE to present. The geochemical data indicate that cultural acidification decreased lake-water organic carbon concentrations in both lakes, which suggests increased light availability and UV exposure during the past century. The responses of the studied lakes to anthropogenic pressures varied, as the lake situated at a lower altitude with a larger catchment showed only a few biotic changes indicating higher resilience, whereas the lake situated at higher altitude showed distinct changes in its ecological status. In this alpine lake, almost 30% of the diatom functional groups shifted from benthic to planktic during the post-industrial era. The role of increased light availability and UV exposure as a driver of diatom functional group distributions could not be unambiguously separated, and such diatom assemblage changes have been shown in many regions and most closely linked to a warming climate. However, low guild functional groups, prevalent also in the contemporary samples from the shallow littoral zone, dominated the diatom communities throughout the studied period, suggesting high tolerance to UV radiation.

Zoning strategies for managing outbreaks of alien plant pests in the European Union: a review - Hongyu Sun; Jacob C. Douma; Martijn F. Schenk; Roel P. J. Potting; Donato Boscia; Antonio Vicent; Alan MacLeod; Wopke van der Werf (Journal of Pest Science, 2023)
Managing outbreaks of alien plant pests is key to preserving biodiversity and safeguarding crop production. Zoning strategies are applied by plant health authorities to tailor measures to the risk of spread in relation to distance from the outbreak epicentre and the biology of the pest. Here we synthesize information on outbreak management to evaluate the diversity and consistency of such approaches. We collected information on the zoning strategies of 121 outbreaks of 25 plant pests in the European Union (EU). According to the organism’s presence and the measures applied, five zones were distinguished: an infested zone (83% of cases), a buffer zone (76%), a clear-cutting zone (28%), an eradication zone (1%) and a containment zone (1%). Infested zones and buffer zones were adjacent non-overlapping zones, while the clear-cutting zone, eradication zone or containment zone was within either the infested zone or buffer zone. A combination of infested and buffer zones was used in 51% of recorded cases. Measures differed within different zones. Destruction of infested plants in the infested zone was done in 78% of the cases, while surveillance was always applied in the buffer zone. Regulation of an organism at EU level led to a convergence of zoning strategies applied by different member states. Regulations often prescribed the greatest widths used before regulations were issued. Further analyses are needed to explore the efficacy of different strategies including the costs of each strategy. Such analyses should combine insight from practice with bio-economic modelling.

Angler and guide perceptions provide insights into the status and threats of the Atlantic tarpon (Megalops atlanticus) fishery - Lucas P. Griffin; Grace A. Casselberry; Ezra M. Markowitz; Jacob W. Brownscombe; Aaron J. Adams; Bill Horn; Steven J. Cooke; Andy J. Danylchuk (Marine Policy, 2023)

Comparing methods to deposit Pd-In catalysts on hydrogen-permeable hollow-fiber membranes for nitrate reduction - Juliana Levi; Sujin Guo; Shalinee Kavadiya; Yihao Luo; Chung-Seop Lee; Hunter P. Jacobs; Zachary Holman; Michael S. Wong; Sergi Garcia-Segura; Chen Zhou; Bruce E. Rittmann; Paul Westerhoff (Water Research, 2023)

When less is more: How increasing the complexity of machine learning strategies for geothermal energy assessments may not lead toward better estimates - Stanley P. Mordensky; John J. Lipor; Jacob DeAngelo; Erick R. Burns; Cary R. Lindsey (Geothermics, 2023)

Legacy effects of acidification and climate warming affect recent recovery of diatom assemblages in Sudbury-region lakes (Ontario, Canada) - Yuanyu Cheng; Neal Michelutti; Carsten Meyer-Jacob; Andrew M. Paterson; Wendel Keller; John M. Gunn; John P. Smol (Hydrobiologia, 2023)

Rabies virus infection is associated with variations in calbindin D-28K and calretinin mRNA expression levels in mouse brain tissue - George C. Korie; Abdullahi B. Sallau; Brenda Kanu; Grace S. N. Kia; Jacob K. P. Kwaga (Archives of Virology, 2023)

Host phylogeny and functional traits differentiate gut microbiomes in a diverse natural community of small mammals - Bianca R. P. Brown; Jacob R. Goheen; Seth D. Newsome; Robert M. Pringle; Todd M. Palmer; Leo M. Khasoha; Tyler R. Kartzinel (Molecular Ecology, 2023)
Differences in the bacterial communities inhabiting mammalian gut microbiomes tend to reflect the phylogenetic relatedness of their hosts, a pattern dubbed phylosymbiosis. Although most research on this pattern has compared the gut microbiomes of host species across biomes, understanding the evolutionary and ecological processes that generate phylosymbiosis requires comparisons across phylogenetic scales and under similar ecological conditions. We analysed the gut microbiomes of 14 sympatric small mammal species in a semi‐arid African savanna, hypothesizing that there would be a strong phylosymbiotic pattern associated with differences in their body sizes and diets. Consistent with phylosymbiosis, microbiome dissimilarity increased with phylogenetic distance among hosts, ranging from congeneric sets of mice and hares that did not differ significantly in microbiome composition to species from different taxonomic orders that had almost no gut bacteria in common. While phylosymbiosis was detected among just the 11 species of rodents, it was substantially weaker at this scale than in comparisons involving all 14 species together. In contrast, microbiome diversity and composition were generally more strongly correlated with body size, dietary breadth, and dietary overlap in comparisons restricted to rodents than in those including all lineages. The starkest divides in microbiome composition thus reflected the broad evolutionary divergence of hosts, regardless of body size or diet, while subtler microbiome differences reflected variation in ecologically important traits of closely related hosts. Strong phylosymbiotic patterns arose deep in the phylogeny, and ecological filters that promote functional differentiation of cooccurring host species may disrupt or obscure this pattern near the tips.

Nonequilibrium spherulitic magnetite in the Ryugu samples - Elena Dobrică; Hope A. Ishii; John P. Bradley; Kenta Ohtaki; Adrian J. Brearley; Takaaki Noguchi; Toru Matsumoto; Akira Miyake; Yohei Igami; Mitsutaka Haruta; Hikaru Saito; Satoshi Hata; et al. (Geochimica et Cosmochimica Acta, 2023)

Arterial stiffness and augmentation index are associated with balance function in young adults - Burak T. Cilhoroz; Andrew R. Heckel; Jacob P. DeBlois; Allison Keller; Jacob J. Sosnoff; Kevin S. Heffernan (European Journal of Applied Physiology, 2023)

Assessment of the relations between crop yield variability and the onset and intensity of the West African Monsoon - Jacob Emanuel Joseph; Folorunso M. Akinseye; Omonlola Nadine Worou; Aliou Faye; Oumar Konte; Anthony M. Whitbread; Reimund P. Rötter (Agricultural and Forest Meteorology, 2023)

Genomic diversity and differentiation between island and mainland populations of white‐tailed eagles ( Haliaeetus albicilla ) - Charles Christian Riis Hansen; Áki Jarl Láruson; Jacob Agerbo Rasmussen; Jesus Adrian Chimal Ballesteros; Mikkel‐Holger S. Sinding; Gunnar T. Hallgrimsson; Menja von Schmalensee; Robert A. Stefansson; Kristinn Haukur Skarphédinsson; Aili Lage Labansen; Madis Leivits; Christian Sonne; et al. (Molecular Ecology, 2023)
Divergence in the face of high dispersal capabilities is a documented but poorly understood phenomenon. The white‐tailed eagle ( Haliaeetus albicilla ) has a large geographic dispersal capability and should theoretically be able to maintain genetic homogeneity across its dispersal range. However, following analysis of the genomic variation of white‐tailed eagles, from both historical and contemporary samples, clear signatures of ancient biogeographic substructure across Europe and the North‐East Atlantic is observed. The greatest genomic differentiation was observed between island (Greenland and Iceland) and mainland (Denmark, Norway and Estonia) populations. The two island populations share a common ancestry from a single mainland population, distinct from the other sampled mainland populations, and despite the potential for high connectivity between Iceland and Greenland they are well separated from each other and are characterized by inbreeding and little variation. Temporal differences also highlight a pattern of regional populations persisting despite the potential for admixture. All sampled populations generally showed a decline in effective population size over time, which may have been shaped by four historical events: (1) Isolation of refugia during the last glacial period 110–115,000 years ago, (2) population divergence following the colonization of the deglaciated areas ~10,000 years ago, (3) human population expansion, which led to the settlement in Iceland ~1100 years ago, and (4) human persecution and exposure to toxic pollutants during the last two centuries.

Vulnerability to climate change increases with trophic level in terrestrial organisms - Carmen R.B. da Silva; Julian E. Beaman; Jacob P. Youngblood; Vanessa Kellermann; Sarah E. Diamond (Science of The Total Environment, 2023)

Search for CP violation and measurement of branching fractions and decay asymmetry parameters for Λ c + → Λ h + and Λ c + → Σ 0 h + ( h = K , π ) - L.K. Li; W. Shan; K. Kinoshita; I. Adachi; H. Aihara; D.M. Asner; H. Atmacan; T. Aushev; V. Babu; S. Bahinipati; Sw. Banerjee; P. Behera; et al. (Science Bulletin, 2023)

Neoglacial lake-ecosystem changes above and below the subarctic Fennoscandian treeline inferred from changes in diatom functional groups - Marttiina V. Rantala; E. Henriikka Kivilä; Carsten Meyer-Jacob; Sanna Atti; Tomi P. Luoto; John P. Smol; Liisa Nevalainen (Journal of Paleolimnology, 2023)
Algal communities act as sensitive indicators of past and present climate effects on northern lakes, but their responses can vary considerably between ecosystems. Functional trait-based approaches may help us better understand the nature of the diverse biotic responses and their underlying ecosystem changes. We explored patterns in diatom (Bacillariophyceae) growth forms and species composition during the Neoglacial in two shallow lakes typical of subarctic regions, including a dark-colored woodland lake and a clear tundra lake. Sediment carbon and nitrogen elemental and isotope biogeochemistry and spectral indices were used to track broadscale changes in lake productivity, the inflow of organic carbon from land, and benthic substratum over the past three millennia. The biogeochemical indices tracked declines in land-lake connectivity as well as lake-water and sediment organic enrichment above and below the subarctic treeline driven by Neoglacial cooling. This broadscale environmental transition was intercepted by periods of elevated primary production associated with transient Neoglacial warm anomalies and, in particular, the twentieth century warming. Although the Neoglacial development of the lakes showed conspicuous similarities, diatom functional and taxonomic responses were not uniform between the lakes pointing to intrinsic differences in the development of benthic habitats and underwater-light regimes. Many of the observed biotic shifts aligned with expectations based on earlier research linking diatom functional traits to changing light and organic levels but the results also point to further research needs, particularly to better differentiate the individual and interactive effects of substratum and light. Despite distinct anthropogenic imprints in the biogeochemical record, the scale of human impact on the lakes’ biota has not, as yet, been profound, but the changes are nonetheless clear when compared to the previous three millennia of natural lake development.

Cryptic Mate Preference in Male Bicyclus anynana Butterflies - Jacob P. Siebenmorgen; Taryn L. Tibbs; Deonna N. Robertson; Erica L. Westerman (Journal of Insect Behavior, 2023)

NASA’s NMME-based S2S hydrologic forecast system for food insecurity early warning in southern Africa - Abheera Hazra; Amy McNally; Kimberly Slinski; Kristi R. Arsenault; Shraddhanand Shukla; Augusto Getirana; Jossy P. Jacob; Daniel P. Sarmiento; Christa Peters-Lidard; Sujay V. Kumar; Randal D. Koster (Journal of Hydrology, 2023)

Long-term growing season aridity and grazing seasonality effects on perennial grass biomass in a Chihuahuan Desert rangeland - Sophia N. Lasché; Ryan W.R. Schroeder; Matthew M. McIntosh; Jacob E. Lucero; Sheri A. Spiegal; Micah P. Funk; Reldon F. Beck; Jerry L. Holechek; Akasha M. Faist (Journal of Arid Environments, 2023)

Understanding heterogeneity of responses to, and optimizing clinical efficacy of, exercise training in older adults: NIH NIA Workshop summary - Melissa L. Erickson; Jacob M. Allen; Daniel P. Beavers; Linda M. Collins; Karina W. Davidson; Kirk I. Erickson; Karyn A. Esser; Matthijs K. C. Hesselink; Kerrie L. Moreau; Eric B. Laber; Charlotte A. Peterson; Courtney M. Peterson; et al. (GeroScience, 2023)
Exercise is a cornerstone of preventive medicine and a promising strategy to intervene on the biology of aging. Variation in the response to exercise is a widely accepted concept that dates back to the 1980s with classic genetic studies identifying sequence variations as modifiers of the VO 2 max response to training. Since that time, the literature of exercise response variance has been populated with retrospective analyses of existing datasets that are limited by a lack of statistical power from technical error of the measurements and small sample sizes, as well as diffuse outcomes, very few of which have included older adults. Prospective studies that are appropriately designed to interrogate exercise response variation in key outcomes identified a priori and inclusive of individuals over the age of 70 are long overdue. Understanding the underlying intrinsic (e.g., genetics and epigenetics) and extrinsic (e.g., medication use, diet, chronic disease) factors that determine robust versus poor responses to various exercise factors will be used to improve exercise prescription to target the pillars of aging and optimize the clinical efficacy of exercise training in older adults. This review summarizes the proceedings of the NIA-sponsored workshop entitled, “Understanding Heterogeneity of Responses to, and Optimizing Clinical Efficacy of, Exercise Training in Older Adults” and highlights the importance and current state of exercise response variation research, particularly in older adults, prevailing challenges, and future directions.

Correction to: Cascading effects of climate change on recreational marine flats fishes and fisheries - Andy J. Danylchuk; Lucas P. Griffin; Robert Ahrens; Micheal S. Allen; Ross E. Boucek; Jacob W. Brownscombe; Grace A. Casselberry; Sascha Clark Danylchuk; Alex Filous; Tony L. Goldberg; Addiel U. Perez; Jennifer S. Rehage; et al. (Environmental Biology of Fishes, 2023)

Spatial-temporal patterns of Permit (Trachinotus falcatus) habitat residency in the Florida Keys, USA - Jacob W. Brownscombe; Lucas P. Griffin; Danielle Morley; Alejandro Acosta; Ross Boucek; Aaron J. Adams; Andy J. Danylchuk; Steven J. Cooke (Environmental Biology of Fishes, 2023)

Cascading effects of climate change on recreational marine flats fishes and fisheries - Andy J. Danylchuk; Lucas P. Griffin; Robert Ahrens; Micheal S. Allen; Ross E. Boucek; Jacob W. Brownscombe; Grace A. Casselberry; Sascha Clark Danylchuk; Alex Filous; Tony L. Goldberg; Addiel U. Perez; Jennifer S. Rehage; et al. (Environmental Biology of Fishes, 2023)

Correction to: Assessing the potential for red tide (Karenia brevis) algal bloom impacts on Atlantic tarpon (Megalops atlanticus) along the southwestern coast of Florida - Lucas P. Griffin; Claudia Friess; Micah D. Bakenhaster; Kim Bassos‑Hull; Sarah Walters Burnsed; Jacob W. Brownscombe; Steven J. Cooke; Robert D. Ellis; Jayne M. Gardiner; James Locascio; Susan Lowerre‑Barbieri; Gregg R. Poulakis; et al. (Environmental Biology of Fishes, 2023)

Assessing the potential for red tide (Karenia brevis) algal bloom impacts on Atlantic tarpon (Megalops atlanticus) along the southwestern coast of Florida - Lucas P. Griffin; Claudia Friess; Micah D. Bakenhaster; Kim Bassos-Hull; Sarah Walters Burnsed; Jacob W. Brownscombe; Steven J. Cooke; Robert D. Ellis; Jayne M. Gardiner; James Locascio; Susan Lowerre-Barbieri; Gregg R. Poulakis; et al. (Environmental Biology of Fishes, 2023)

There’s no place like home: high site fidelity and small home range of bonefish (Albula vulpes) inhabiting fringing reef flats in Culebra, Puerto Rico - Lucas P. Griffin; Jacob W. Brownscombe; Tyler O. Gagné; Christopher R. Haak; Roxann Cormier; Sarah L. Becker; Steven J. Cooke; John T. Finn; Andy. J. Danylchuk (Environmental Biology of Fishes, 2023)

Patterns in spatial use and movement of Silver Carp among tributaries and main-stem rivers: insight from otolith microchemistry analysis - Jacob P. Werner; Quintin J. Dean; Mark A. Pegg; Martin J. Hamel (Biological Invasions, 2023)

The structure and organisation of an Amazonian bird community remains little changed after nearly four decades in Manu National Park - Ari E. Martínez; José M. Ponciano; Juan P. Gomez; Thomas Valqui; Jorge Novoa; Mariamercedes Antezana; Gabriela Biscarra; Ettore Camerlenghi; Blaine H. Carnes; Renato Huayanca Munarriz; Eliseo Parra; Isabella M. Plummer; et al. (Ecology Letters, 2023)
Documenting patterns of spatiotemporal change in hyper‐diverse communities remains a challenge for tropical ecology yet is increasingly urgent as some long‐term studies have shown major declines in bird communities in undisturbed sites. In 1982, Terborgh et al. quantified the structure and organisation of the bird community in a 97‐ha. plot in southeastern Peru. We revisited the same plot in 2018 using the same methodologies as the original study to evaluate community‐wide changes. Contrary to longitudinal studies of other neotropical bird communities (Tiputini, Manaus, and Panama), we found little change in community structure and organisation, with increases in 5, decreases in 2 and no change in 7 foraging guilds. This apparent stability suggests that large forest reserves such as the Manu National Park, possibly due to regional topographical influences on precipitation, still provide the conditions for establishing refugia from at least some of the effects of global change on bird communities.

Multiple convective storms within a single cyclone on Saturn - Jacob L. Gunnarson; Kunio M. Sayanagi; Georg Fischer; Trevor Barry; Anthony Wesley; Ulyana A. Dyudina; Shawn P. Ewald; Andrew P. Ingersoll (Icarus, 2023)

The impacts of whole-lake acidification and eutrophication on the accumulation of lead in sediments from manipulated lakes in the Experimental Lakes Area (IISD-ELA) - Alexandre Baud; John P. Smol; Carsten Meyer-Jacob; Michael Paterson; Pierre Francus; Irene Gregory-Eaves (Environmental Pollution, 2023)

Identifying priority locations to protect a wide-ranging endangered species - Natasha M. Peters; Corinne J. Kendall; Jacob G. Davies; Claire Bracebridge; Aaron Nicholas; Msafiri P. Mgumba; Colin M. Beale (Biological Conservation, 2023)

High sensitivity of tropical forest birds to deforestation at lower altitudes - Simon C. Mills; Jacob B. Socolar; Felicity A. Edwards; Edicson Parra; Diego E. Martínez‐Revelo; Jose Manuel Ochoa Quintero; Torbjørn Haugaasen; Robert P. Freckleton; Jos Barlow; David P. Edwards (Ecology, 2023)
Habitat conversion is a major driver of tropical biodiversity loss, but its effects are poorly understood in montane environments. While community‐level responses to habitat loss display strong elevational dependencies, it is unclear whether these arise via elevational turnover in community composition and interspecific differences in sensitivity or elevational variation in environmental conditions and proximity to thermal thresholds. Here we assess the relative importance of inter‐ and intraspecific variation across the elevational gradient by quantifying how 243 forest‐dependent bird species vary in sensitivity to landscape‐scale forest loss across a 3000‐m elevational gradient in the Colombian Andes. We find that species that live at lower elevations are strongly affected by loss of forest in the nearby landscape, while those at higher elevations appear relatively unperturbed, an effect that is independent of phylogeny. Conversely, we find limited evidence of intraspecific elevational gradients in sensitivity, with populations displaying similar sensitivities to forest loss, regardless of where they exist in a species' elevational range. Gradients in biodiversity response to habitat loss thus appear to arise via interspecific gradients in sensitivity rather than proximity to climatically limiting conditions.

Optimization and Scale Up of Spray Dried CPZEN-45 Aerosol Powders for Inhaled Tuberculosis Treatment - Ian E. Stewart; Phillip G. Durham; Jacob M. Sittenauer; Aranza P. Barreda; Grayson W. Stowell; Carmella Moody; Jeffery B. Mecham; Catherine Simpson; Sharon Daily; Sara E. Maloney; Mark D. Williams; Diana Severynse-Stevens; et al. (Pharmaceutical Research, 2022)

A revision of the Inocybe grammata group in North America including four new taxa - P. Brandon Matheny; Adriana Corrales; Mary Grace Graddy; Roy E. Halling; Jacob Kalichman; Linas V. Kudzma; Clark L. Ovrebo; Rachel A. Swenie; Noah C. Walker (Brittonia, 2022)

Autochthonous nutrient recycling driven by soil microbiota could be sustaining high coconut productivity in Lakshadweep Islands sans external fertilizer application - Murali Gopal; Alka Gupta; V. Arunachalam; H. P. Maheswarappa; George V. Thomas; P. M. Jacob (World Journal of Microbiology and Biotechnology, 2022)

Association Between Head Impact Biomechanics and Physical Load in College Football - Bradley J. Lauck; Aaron M. Sinnott; Adam W. Kiefer; Darin A. Padua; Jacob R. Powell; Haley R. Sledge; Jason P. Mihalik (Annals of Biomedical Engineering, 2022)

Emerging harmful algal blooms caused by distinct seasonal assemblages of a toxic diatom - Alexa R. Sterling; Riley D. Kirk; Matthew J. Bertin; Tatiana A. Rynearson; David G. Borkman; Marissa C. Caponi; Jessica Carney; Katherine A. Hubbard; Meagan A. King; Lucie Maranda; Emily J. McDermith; Nina R. Santos; et al. (Limnology and Oceanography, 2022)
Diatoms in the Pseudo‐nitzschia genus produce the neurotoxin domoic acid. Domoic acid bioaccumulates in shellfish, causing illness in humans and marine animals upon ingestion. In 2017, high domoic acid levels in shellfish meat closed shellfish harvest in Narragansett Bay, Rhode Island for the first and only time in history, although abundant Pseudo‐nitzschia have been observed for over 60 years . To investigate whether an environmental factor altered endemic Pseudo‐nitzschia physiology or new domoic acid‐producing strain(s) were introduced to Narragansett Bay, we conducted weekly sampling from 2017 to 2019 and compared closure samples. Plankton‐associated domoic acid was quantified by LC‐MS/MS and Pseudo‐nitzschia spp. were identified using a taxonomically improved high‐throughput rDNA sequencing approach. Comparison with environmental data revealed a detailed understanding of domoic acid dynamics and seasonal multi‐species assemblages. Plankton‐associated domoic acid was low throughout 2017–2019, but recurred in fall and early summer maxima. Fall domoic acid maxima contained known toxic species as well as a novel Pseudo‐nitzschia genotype. Summer domoic acid maxima included fewer species but also known toxin producers . Most 2017 closure samples contained the particularly concerning toxic species, P. australis , which also appeared infrequently during 2017–2019. Recurring Pseudo‐nitzschia assemblages were driven by seasonal temperature changes, and plankton‐associated domoic acid correlated with low dissolved inorganic nitrogen. Thus, the Narragansett Bay closures were likely caused by both resident assemblages that become toxic depending on nutrient status as well as the episodic introductions of toxic species from oceanographic and climatic shifts.

Immersion challenge model for Flavobacterium psychrophilum infection of Atlantic salmon ( Salmo salar L.) fry - Valeria Macchia; Makoto Inami; Anne Ramstad; Fabian Grammes; Andrew Reeve; Thomas Moen; Jacob Seilø Torgersen; Alexandra Adams; Andrew P. Desbois; Rowena Hoare (Journal of Fish Diseases, 2022)
Flavobacterium psychrophilum is the causative agent of bacterial cold‐water disease (CWBD) and rainbow trout fry syndrome (RTFS), which affect salmonids. To better understand this pathogen and its interaction with the host during infection, including to support the development of resistant breeds and new vaccines and treatments, there is a pressing need for reliable and reproducible immersion challenge models that more closely mimic natural routes of infection. The aim of this present study was to evaluate a challenge model developed previously for rainbow trout for use in Atlantic salmon. First, preliminary challenges were conducted in Atlantic salmon ( n = 120) and rainbow trout ( n = 80) fry using two F. psychrophilum isolates collected from each fish species, respectively; fish had been pretreated with 200 mg/L hydrogen peroxide for 1 h. Thereafter, the main challenge was performed for just one F. psychrophilum isolate for each species (at 2 × 10 7 CFU/mL) but using larger cohorts (Atlantic salmon: n = 1187; rainbow trout: n = 2701). Survival in the main challenge was 81.2% in Atlantic salmon (21 days post‐challenge) and 45.3% in rainbow trout (31 days post‐challenge). Mortalities progressed similarly during the preliminary and main challenges for both species, demonstrating the reproducibility of this model. This is the first immersion challenge model of F. psychrophilum to be developed successfully for Atlantic salmon.

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

Particle Property Characterization and Data Curation for Effective Powder Property Modeling in the Pharmaceutical Industry - Robert C. Wadams; Ilgaz Akseli; Jacob Albrecht; Ana P. Ferreira; John F. Gamble; Michael Leane; Stephen Thomas; Yue Schuman; Lauren Taylor; Mike Tobyn (AAPS PharmSciTech, 2022)

Sleep duration and lipid metabolism in patients with diabetes mellitus: from the POWER2DM study - Isabel Perez-Corral; Francisco Gomez-Delgado; Merel M. Ruissen; Jose D. Torres-Peña; Antonio P. Arenas-de Larriva; Jacob K. Sont; Albert A. de Graaf; Bas S. Uitbeijerse; Eelco J. P. de Koning; Javier Delgado-Lista (Sleep and Biological Rhythms, 2022)

A phylogeographic assessment of the greater kudu (Tragelaphus strepsiceros) across South Africa - R. Jacobs; W. G. Coetzer; J. P. Grobler (Conservation Genetics, 2022)

The movement ecology of fishes - Steven J. Cooke; Jordanna N. Bergman; William M. Twardek; Morgan L. Piczak; Grace A. Casselberry; Keegan Lutek; Lotte S. Dahlmo; Kim Birnie‐Gauvin; Lucas P. Griffin; Jacob W. Brownscombe; Graham D. Raby; Emily M. Standen; et al. (Journal of Fish Biology, 2022)
Movement of fishes in the aquatic realm is fundamental to their ecology and survival. Movement can be driven by a variety of biological, physiological and environmental factors occurring across all spatial and temporal scales. The intrinsic capacity of movement to impact fish individually ( e.g. , foraging) with potential knock‐on effects throughout the ecosystem ( e.g. , food web dynamics) has garnered considerable interest in the field of movement ecology. The advancement of technology in recent decades, in combination with ever‐growing threats to freshwater and marine systems, has further spurred empirical research and theoretical considerations. Given the rapid expansion within the field of movement ecology and its significant role in informing management and conservation efforts, a contemporary and multidisciplinary review about the various components influencing movement is outstanding. Using an established conceptual framework for movement ecology as a guide ( i.e. , Nathan et al. , 2008: 19052), we synthesized the environmental and individual factors that affect the movement of fishes. Specifically, internal ( e.g. , energy acquisition, endocrinology, and homeostasis) and external (biotic and abiotic) environmental elements are discussed, as well as the different processes that influence individual‐level (or population) decisions, such as navigation cues, motion capacity, propagation characteristics and group behaviours. In addition to environmental drivers and individual movement factors, we also explored how associated strategies help survival by optimizing physiological and other biological states. Next, we identified how movement ecology is increasingly being incorporated into management and conservation by highlighting the inherent benefits that spatio‐temporal fish behaviour imbues into policy, regulatory, and remediation planning. Finally, we considered the future of movement ecology by evaluating ongoing technological innovations and both the challenges and opportunities that these advancements create for scientists and managers. As aquatic ecosystems continue to face alarming climate (and other human‐driven) issues that impact animal movements, the comprehensive and multidisciplinary assessment of movement ecology will be instrumental in developing plans to guide research and promote sustainability measures for aquatic resources.

SNAPSHOT USA 2020: A second coordinated national camera trap survey of the United States during the COVID ‐19 pandemic - Roland Kays; Michael V. Cove; Jose Diaz; Kimberly Todd; Claire Bresnan; Matt Snider; Thomas E. Lee; Jonathan G. Jasper; Brianna Douglas; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2022)
Managing wildlife populations in the face of global change requires regular data on the abundance and distribution of wild animals, but acquiring these over appropriate spatial scales in a sustainable way has proven challenging. Here we present the data from Snapshot USA 2020, a second annual national mammal survey of the USA. This project involved 152 scientists setting camera traps in a standardized protocol at 1485 locations across 103 arrays in 43 states for a total of 52,710 trap‐nights of survey effort. Most (58) of these arrays were also sampled during the same months (September and October) in 2019, providing a direct comparison of animal populations in 2 years that includes data from both during and before the COVID‐19 pandemic. All data were managed by the eMammal system, with all species identifications checked by at least two reviewers. In total, we recorded 117,415 detections of 78 species of wild mammals, 9236 detections of at least 43 species of birds, 15,851 detections of six domestic animals and 23,825 detections of humans or their vehicles. Spatial differences across arrays explained more variation in the relative abundance than temporal variation across years for all 38 species modeled, although there are examples of significant site‐level differences among years for many species. Temporal results show how species allocate their time and can be used to study species interactions, including between humans and wildlife. These data provide a snapshot of the mammal community of the USA for 2020 and will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, and the impacts of species interactions on daily activity patterns. There are no copyright restrictions, and please cite this paper when using these data, or a subset of these data, for publication.

The pZRS non-coding regulatory mutation resulting in triphalangeal thumb–polysyndactyly syndrome changes the pattern of local interactions - Jacob W. P. Potuijt; Anna Sowinska-Seidler; Ewelina Bukowska-Olech; Picard Nguyen; Aleksander Jankowski; Frank Magielsen; Karolina Matuszewska; Christianne A. van Nieuwenhoven; Robert-Jan H. Galjaard; Annelies de Klein; Aleksander Jamsheer (Molecular Genetics and Genomics, 2022)

Animal pollination increases stability of crop yield across spatial scales - Jacob Bishop; Michael P. D. Garratt; Shinichi Nakagawa (Ecology Letters, 2022)
The benefits of animal pollination to crop yield are well known. In contrast, the effects of animal pollination on the spatial or temporal stability (the opposite of variability) of crop yield remain poorly understood. We use meta‐analysis to combine variability information from 215 experimental comparisons between animal‐pollinated and wind‐ or self‐pollinated control plants in apple, oilseed rape and faba bean. Animal pollination increased yield stability (by an average of 32% per unit of yield) at between‐flower, ‐plant, ‐plot and ‐field scales. Evidence suggests this occurs because yield benefits of animal pollination become progressively constrained closer to the maximum potential yield in a given context, causing clustering. The increase in yield stability with animal pollination is greatest when yield benefits of animal pollination are greatest, indicating that managing crop pollination to increase yield also increases yield stability. These additional pollination benefits have not yet been included in economic assessments but provide further justification for policies to protect pollinators.

First report of leaf blight of Indian spinach caused by Colletotrichum siamense in India - Sajeena Abdulmajeed; Mathew Deepu; M. K. Dhanya; John Jacob; P. Rawal; D. Jain; M. Elina; D. S. Nair; T. S. Peteti (Journal of Plant Pathology, 2022)

Confluences and land cover as agents of change: habitat change modifies the movement and assemblage stability of headwater fishes - Joshua P. Hubbell; Jacob F. Schaefer (Urban Ecosystems, 2022)

Speciation with gene flow in a narrow endemic West Virginia cave salamander (Gyrinophilus subterraneus) - Evan H. Campbell Grant; Kevin P. Mulder; Adrianne B. Brand; Douglas B. Chambers; Addison H. Wynn; Grace Capshaw; Matthew L. Niemiller; John G. Phillips; Jeremy F. Jacobs; Shawn R. Kuchta; Rayna C. Bell (Conservation Genetics, 2022)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Cortical thickness of primary motor and vestibular brain regions predicts recovery from fall and balance directly after spaceflight - Vincent Koppelmans; Ajitkumar P. Mulavara; Rachael D. Seidler; Yiri E. De Dios; Jacob J. Bloomberg; Scott J. Wood (Brain Structure and Function, 2022)

Cortico-amygdalar connectivity and externalizing/internalizing behavior in children with neurodevelopmental disorders - Hajer Nakua; Colin Hawco; Natalie J. Forde; Grace R. Jacobs; Michael Joseph; Aristotle N. Voineskos; Anne L. Wheeler; Meng-Chuan Lai; Peter Szatmari; Elizabeth Kelley; Xudong Liu; Stelios Georgiades; et al. (Brain Structure and Function, 2022)
Background Externalizing and internalizing behaviors contribute to clinical impairment in children with neurodevelopmental disorders (NDDs). Although associations between externalizing or internalizing behaviors and cortico-amygdalar connectivity have been found in clinical and non-clinical pediatric samples, no previous study has examined whether similar shared associations are present across children with different NDDs. Methods Multi-modal neuroimaging and behavioral data from the Province of Ontario Neurodevelopmental Disorders (POND) Network were used. POND participants aged 6–18 years with a primary diagnosis of autism spectrum disorder (ASD), attention-deficit/hyperactivity disorder (ADHD) or obsessive–compulsive disorder (OCD), as well as typically developing children (TDC) with T1-weighted, resting-state fMRI or diffusion weighted imaging (DWI) and parent-report Child Behavioral Checklist (CBCL) data available, were analyzed (total n = 346). Associations between externalizing or internalizing behavior and cortico-amygdalar structural and functional connectivity indices were examined using linear regressions, controlling for age, gender, and image-modality specific covariates. Behavior-by-diagnosis interaction effects were also examined. Results No significant linear associations (or diagnosis-by-behavior interaction effects) were found between CBCL-measured externalizing or internalizing behaviors and any of the connectivity indices examined. Post-hoc bootstrapping analyses indicated stability and reliability of these null results. Conclusions The current study provides evidence towards an absence of a shared linear relationship between internalizing or externalizing behaviors and cortico-amygdalar connectivity properties across a transdiagnostic sample of children with different primary NDD diagnoses and TDC. Different methodological approaches, including incorporation of multi-dimensional behavioral data (e.g., task-based fMRI) or clustering approaches may be needed to clarify complex brain-behavior relationships relevant to externalizing/internalizing behaviors in heterogeneous clinical NDD populations.

Thermodynamic properties of geikielite (MgTiO3) and ilmenite (FeTiO3) derived from vibrational methods combined with Raman and infrared spectroscopic data - Michael H. G. Jacobs; Arie P. van den Berg; Rainer Schmid-Fetzer; Jellie de Vries; Wim van Westrenen; Yue Zhao (Physics and Chemistry of Minerals, 2022)

Distance decay 2.0 – A global synthesis of taxonomic and functional turnover in ecological communities - Caio Graco‐Roza; Sonja Aarnio; Nerea Abrego; Alicia T. R. Acosta; Janne Alahuhta; Jan Altman; Claudia Angiolini; Jukka Aroviita; Fabio Attorre; Lars Baastrup‐Spohr; José J. Barrera‐Alba; Jonathan Belmaker; et al. (Global Ecology and Biogeography, 2022)
Aim Understanding the variation in community composition and species abundances (i.e., β‐diversity) is at the heart of community ecology. A common approach to examine β‐diversity is to evaluate directional variation in community composition by measuring the decay in the similarity among pairs of communities along spatial or environmental distance. We provide the first global synthesis of taxonomic and functional distance decay along spatial and environmental distance by analysing 148 datasets comprising different types of organisms and environments. Location Global. Time period 1990 to present. Major taxa studied From diatoms to mammals. Method We measured the strength of the decay using ranked Mantel tests (Mantel r ) and the rate of distance decay as the slope of an exponential fit using generalized linear models. We used null models to test whether functional similarity decays faster or slower than expected given the taxonomic decay along the spatial and environmental distance. We also unveiled the factors driving the rate of decay across the datasets, including latitude, spatial extent, realm and organismal features. Results Taxonomic distance decay was stronger than functional distance decay along both spatial and environmental distance. Functional distance decay was random given the taxonomic distance decay. The rate of taxonomic and functional spatial distance decay was fastest in the datasets from mid‐latitudes. Overall, datasets covering larger spatial extents showed a lower rate of decay along spatial distance but a higher rate of decay along environmental distance. Marine ecosystems had the slowest rate of decay along environmental distances. Main conclusions In general, taxonomic distance decay is a useful tool for biogeographical research because it reflects dispersal‐related factors in addition to species responses to climatic and environmental variables. Moreover, functional distance decay might be a cost‐effective option for investigating community changes in heterogeneous environments.

Climate oscillations drive millennial‐scale changes in seabird colony size - Matthew P. Duda; Frédéric Cyr; Gregory J. Robertson; Neal Michelutti; Carsten Meyer‐Jacob; April Hedd; William A. Montevecchi; Linda E. Kimpe; Jules M. Blais; John P. Smol (Global Change Biology, 2022)
Seabird population size is intimately linked to the physical, chemical, and biological processes of the oceans. Yet, the overall effects of long‐term changes in ocean dynamics on seabird colonies are difficult to quantify. Here, we used dated lake sediments to reconstruct ~10,000‐years of seabird dynamics in the Northwest Atlantic to determine the influences of Holocene‐scale climatic oscillations on colony size. On Baccalieu Island (Newfoundland and Labrador, Canada)—where the world's largest colony of Leach's storm‐petrel ( Hydrobates leucorhous Vieillot 1818) currently breeds—our data track seabird colony growth in response to warming during the Holocene Thermal Maximum (ca. 9000 to 6000 BP). From ca. 5200 BP to the onset of the Little Ice Age (ca. 550 BP), changes in colony size were correlated to variations in the North Atlantic Oscillation (NAO). By contrasting the seabird trends from Baccalieu Island to millennial‐scale changes of storm‐petrel populations from Grand Colombier Island (an island in the Northwest Atlantic that is subjected a to different ocean climate), we infer that changes in NAO influenced the ocean circulation, which translated into, among many things, changes in pycnocline depth across the Northwest Atlantic basin where the storm‐petrels feed. We hypothesize that the depth of the pycnocline is likely a strong bottom‐up control on surface‐feeding storm‐petrels through its influence on prey accessibility. Since the Little Ice Age (LIA), the effects of ocean dynamics on seabird colony size have been altered by anthropogenic impacts. Subsequently, the colony on Baccalieu Island grew at an unprecedented rate to become the world's largest resulting from favorable conditions linked to climate warming, increased vegetation (thereby nesting habitat), and attraction of recruits from other colonies that are now in decline. We show that although ocean dynamics were an important driver of seabird colony dynamics, its recent influence has been modified by human interference.

A phylogenomic examination of Palmyra Atoll’s corallimorpharian invader - Kaitlyn P. Jacobs; Cynthia L. Hunter; Zac H. Forsman; Amanda L. Pollock; Mariana Rocha de Souza; Robert J. Toonen (Coral Reefs, 2022)

Comparative linkage mapping uncovers recombination suppression across massive chromosomal inversions associated with local adaptation in Atlantic silversides - Maria Akopyan; Anna Tigano; Arne Jacobs; Aryn P. Wilder; Hannes Baumann; Nina O. Therkildsen (Molecular Ecology, 2022)
The role of recombination in genome evolution has long been studied in theory, but until recently empirical investigations had been limited to a small number of model species. Here, we compare the recombination landscape and genome collinearity between two populations of the Atlantic silverside ( Menidia menidia ), a small fish distributed across the steep latitudinal climate gradient of the North American Atlantic coast. We constructed separate linkage maps for locally adapted populations from New York and Georgia and their interpopulation laboratory cross. First, we used one of the linkage maps to improve the current silverside genome assembly by anchoring three large unplaced scaffolds to two chromosomes. Second, we estimated sex‐specific recombination rates, finding 2.3‐fold higher recombination rates in females than males—one of the most extreme examples of heterochiasmy in a fish. While recombination occurs relatively evenly across female chromosomes, it is restricted to only the terminal ends of male chromosomes. Furthermore, comparisons of female linkage maps revealed suppressed recombination along several massive chromosomal inversions spanning nearly 16% of the genome. These inversions segregate between locally adapted populations and coincide near perfectly with blocks of highly elevated genomic differentiation between wild populations. Finally, we discerned significantly higher recombination rates across chromosomes in the northern population compared to the southern. In addition to providing valuable resources for ongoing evolutionary and comparative genomic studies, our findings represent a striking example of structural variation that impacts recombination between adaptively divergent populations, providing empirical support for theorized genomic mechanisms facilitating adaptation despite gene flow.

Climate variability and aridity modulate the role of leaf shelters for arthropods: A global experiment - Gustavo Q. Romero; Thiago Gonçalves‐Souza; Tomas Roslin; Robert J. Marquis; Nicholas A.C. Marino; Vojtech Novotny; Tatiana Cornelissen; Jerome Orivel; Shen Sui; Gustavo Aires; Reuber Antoniazzi; Wesley Dáttilo; et al. (Global Change Biology, 2022)
Current climate change is disrupting biotic interactions and eroding biodiversity worldwide. However, species sensitive to aridity, high temperatures, and climate variability might find shelter in microclimatic refuges, such as leaf rolls built by arthropods. To explore how the importance of leaf shelters for terrestrial arthropods changes with latitude, elevation, and climate, we conducted a distributed experiment comparing arthropods in leaf rolls versus control leaves across 52 sites along an 11,790 km latitudinal gradient. We then probed the impact of short‐ versus long‐term climatic impacts on roll use, by comparing the relative impact of conditions during the experiment versus average, baseline conditions at the site. Leaf shelters supported larger organisms and higher arthropod biomass and species diversity than non‐rolled control leaves. However, the magnitude of the leaf rolls’ effect differed between long‐ and short‐term climate conditions, metrics (species richness, biomass, and body size), and trophic groups (predators vs. herbivores). The effect of leaf rolls on predator richness was influenced only by baseline climate, increasing in magnitude in regions experiencing increased long‐term aridity, regardless of latitude, elevation, and weather during the experiment. This suggests that shelter use by predators may be innate, and thus, driven by natural selection. In contrast, the effect of leaf rolls on predator biomass and predator body size decreased with increasing temperature, and increased with increasing precipitation, respectively, during the experiment. The magnitude of shelter usage by herbivores increased with the abundance of predators and decreased with increasing temperature during the experiment. Taken together, these results highlight that leaf roll use may have both proximal and ultimate causes. Projected increases in climate variability and aridity are, therefore, likely to increase the importance of biotic refugia in mitigating the effects of climate change on species persistence.

First report of fruit rot of jackfruit caused by Athelia rolfsii in India - Abdulmajeed Sajeena; Deepu Mathew; Jacob John; M. K. Dhanya; K. Sushitha; P. Ruby Nahan (Journal of Plant Pathology, 2022)

Volcano infrasound: progress and future directions - Leighton M. Watson; Alexandra M. Iezzi; Liam Toney; Sean P. Maher; David Fee; Kathleen McKee; Hugo D. Ortiz; Robin S. Matoza; Julia E. Gestrich; Jordan W. Bishop; Alex J. C. Witsil; Jacob F. Anderson; et al. (Bulletin of Volcanology, 2022)
Over the past two decades (2000–2020), volcano infrasound (acoustic waves with frequencies less than 20 Hz propagating in the atmosphere) has evolved from an area of academic research to a useful monitoring tool. As a result, infrasound is routinely used by volcano observatories around the world to detect, locate, and characterize volcanic activity. It is particularly useful in confirming subaerial activity and monitoring remote eruptions, and it has shown promise in forecasting paroxysmal activity at open-vent systems. Fundamental research on volcano infrasound is providing substantial new insights on eruption dynamics and volcanic processes and will continue to do so over the next decade. The increased availability of infrasound sensors will expand observations of varied eruption styles, and the associated increase in data volume will make machine learning workflows more feasible. More sophisticated modeling will be applied to examine infrasound source and propagation effects from local to global distances, leading to improved infrasound-derived estimates of eruption properties. Future work will use infrasound to detect, locate, and characterize moving flows, such as pyroclastic density currents, lahars, rockfalls, lava flows, and avalanches. Infrasound observations will be further integrated with other data streams, such as seismic, ground- and satellite-based thermal and visual imagery, geodetic, lightning, and gas data. The volcano infrasound community should continue efforts to make data and codes accessible and to improve diversity, equity, and inclusion in the field. In summary, the next decade of volcano infrasound research will continue to advance our understanding of complex volcano processes through increased data availability, sensor technologies, enhanced modeling capabilities, and novel data analysis methods that will improve hazard detection and mitigation.

Current challenges in metastasis research and future innovation for clinical translation - Amelia L. Parker; Madeleine Benguigui; Jaime Fornetti; Erica Goddard; Serena Lucotti; Jacob Insua-Rodríguez; Adrian P. Wiegmans (Clinical & Experimental Metastasis, 2022)
While immense strides have been made in understanding tumor biology and in developing effective treatments that have substantially improved the prognosis of cancer patients, metastasis remains the major cause of cancer-related death. Improvements in the detection and treatment of primary tumors are contributing to a growing, detailed understanding of the dynamics of metastatic progression. Yet challenges remain in detecting metastatic dissemination prior to the establishment of overt metastases and in predicting which patients are at the highest risk of developing metastatic disease. Further improvements in understanding the mechanisms governing metastasis have great potential to inform the adaptation of existing therapies and the development of novel approaches to more effectively control metastatic disease. This article presents a forward-looking perspective on the challenges that remain in the treatment of metastasis, and the exciting emerging approaches that promise to transform the treatment of metastasis in cancer patients.

Ecological consequences of large herbivore exclusion in an A frican savanna: 12 years of data from the UHURU experiment - Jesse M. Alston; Courtney G. Reed; Leo M. Khasoha; Bianca R. P. Brown; Gilbert Busienei; Nathaniel Carlson; Tyler C. Coverdale; Megan Dudenhoeffer; Marissa A. Dyck; John Ekeno; Abdikadir A. Hassan; Rhianna Hohbein; et al. (Ecology, 2022)
Diverse communities of large mammalian herbivores (LMH), once widespread, are now rare. LMH exert strong direct and indirect effects on community structure and ecosystem functions, and measuring these effects is important for testing ecological theory and for understanding past, current, and future environmental change. This in turn requires long‐term experimental manipulations, owing to the slow and often nonlinear responses of populations and assemblages to LMH removal. Moreover, the effects of particular species or body‐size classes within diverse LMH guilds are difficult to pinpoint, and the magnitude and even direction of these effects often depends on environmental context. Since 2008, we have maintained the Ungulate Herbivory Under Rainfall Uncertainty (UHURU) experiment, a series of size‐selective LMH exclosures replicated across a rainfall/productivity gradient in a semiarid Kenyan savanna. The goals of the UHURU experiment are to measure the effects of removing successively smaller size classes of LMH (mimicking the process of size‐biased extirpation) and to establish how these effects are shaped by spatial and temporal variation in rainfall. The UHURU experiment comprises three LMH‐exclusion treatments and an unfenced control, applied to nine randomized blocks of contiguous 1‐ha plots ( n = 36). The fenced treatments are MEGA (exclusion of megaherbivores, elephant and giraffe), MESO (exclusion of herbivores ≥40 kg), and TOTAL (exclusion of herbivores ≥5 kg). Each block is replicated three times at three sites across the 20‐km rainfall gradient, which has fluctuated over the course of the experiment. The first 5 years of data were published previously ( Ecological Archives E095‐064) and have been used in numerous studies. Since that publication, we have (1) continued to collect data following the original protocols, (2) improved the taxonomic resolution and accuracy of plant and small‐mammal identifications, and (3) begun collecting several new data sets. Here, we present updated and extended raw data from the first 12 years of the UHURU experiment (2008–2019). Data include daily rainfall data throughout the experiment; annual surveys of understory plant communities; annual censuses of woody‐plant communities; annual measurements of individually tagged woody plants; monthly monitoring of flowering and fruiting phenology; every‐other‐month small‐mammal mark–recapture data; and quarterly large‐mammal dung surveys. There are no copyright restrictions; notification of when and how data are used is appreciated and users of UHURU data should cite this data paper when using the data.

Plasma potassium concentration and cardiac repolarisation markers, Tpeak–Tend and Tpeak–Tend/QT, during and after exercise in healthy participants and in end-stage renal disease - Cao Thach Tran; Tania Atanasovska; Claus Graff; Jacob Melgaard; Jørgen K. Kanters; Robert Smith; Aaron C. Petersen; Keld P. Kjeldsen; Michael J. McKenna (European Journal of Applied Physiology, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Distributions of native and invasive Typha (cattail) throughout the Prairie Pothole Region of North America - Brian A. Tangen; Sheel Bansal; Joanna R. Freeland; Steven E. Travis; Jennifer D. Wasko; Terence P. McGonigle; L. Gordon Goldsborough; Keira Gow; Joy E. Marburger; Jacob A. Meier (Wetlands Ecology and Management, 2022)

Kumquat essential oil decreases proliferation and activates JNK signaling and apoptosis in HT-1080 fibrosarcoma cells - Subah Soni; Mruga Y. Parekh; Jive A. Jacob; James P. Mack; Dorothy E. Lobo (Molecular and Cellular Biochemistry, 2022)

Landraces-potential treasure for sustainable wheat improvement - Sneha Adhikari; Jyoti Kumari; Sherry Rachel Jacob; Pramod Prasad; O. P. Gangwar; Charu Lata; Rajnikant Thakur; Amit Kumar Singh; Ruchi Bansal; Sundeep Kumar; S. C. Bhardwaj; Subodh Kumar (Genetic Resources and Crop Evolution, 2022)

A remote sensing‐based three‐source energy balance model to improve global estimations of evapotranspiration in semi‐arid tree‐grass ecosystems - Vicente Burchard‐Levine; Héctor Nieto; David Riaño; Wiliam P. Kustas; Mirco Migliavacca; Tarek S. El‐Madany; Jacob A. Nelson; Ana Andreu; Arnaud Carrara; Jason Beringer; Dennis Baldocchi; M. Pilar Martín (Global Change Biology, 2022)
It is well documented that energy balance and other remote sensing‐based evapotranspiration (ET) models face greater uncertainty over water‐limited tree‐grass ecosystems (TGEs), representing nearly 1/6th of the global land surface. Their dual vegetation strata, the grass‐dominated understory and tree‐dominated overstory, make for distinct structural, physiological and phenological characteristics, which challenge models compared to more homogeneous and energy‐limited ecosystems. Along with this, the contribution of grasses and trees to total transpiration ( T ), along with their different climatic drivers, is still largely unknown nor quantified in TGEs. This study proposes a thermal‐based three‐source energy balance (3SEB) model, accommodating an additional vegetation source within the well‐known two‐source energy balance (TSEB) model. The model was implemented at both tower and continental scales using eddy‐covariance (EC) TGE sites, with variable tree canopy cover and rainfall ( P ) regimes and Meteosat Second Generation (MSG) images. 3SEB robustly simulated latent heat (LE) and related energy fluxes in all sites (Tower: LE RMSD ~60 W/m 2 ; MSG: LE RMSD ~90 W/m 2 ), improving over both TSEB and seasonally changing TSEB (TSEB‐2S) models. In addition, 3SEB inherently partitions water fluxes between the tree, grass and soil sources. The modelled T correlated well with EC T estimates ( r > .76), derived from a machine learning ET partitioning method. The T /ET was found positively related to both P and leaf area index, especially compared to the decomposed grass understory T /ET. However, trees and grasses had contrasting relations with respect to monthly P . These results demonstrate the importance in decomposing total ET into the different vegetation sources, as they have distinct climatic drivers, and hence, different relations to seasonal water availability. These promising results improved ET and energy flux estimations over complex TGEs, which may contribute to enhance global drought monitoring and understanding, and their responses to climate change feedbacks.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

As above, so below? Effects of fungicides on microbial organic matter decomposition are stronger in the hyporheic than in the benthic zone - Eric Bollinger; Jochen P. Zubrod; Marco Konschak; Lenz Sulzer; Jacob Schnurr; Verena C. Schreiner; Ralf Schulz; Mirco Bundschuh (Limnology and Oceanography, 2022)
Microbial organic matter decomposition is a critical ecosystem function, which can be negatively affected by chemicals. Although the majority of organic matter is stored in sediments, the impact of chemicals has exclusively been studied in benthic systems. To address this knowledge gap, we assessed the impact of a fungicide mixture at three concentrations on the decomposition of black alder leaves in the benthic and hyporheic zone. We targeted two sediment treatments characterized by fine and coarse grain sizes (1–2 vs. 2–4 mm). Besides microbial communities' functioning (i.e., decomposition), we determined their structure through microbial biomass estimates and community composition. In absence of fungicides, leaf decomposition, microbial biomass estimates and fungal sporulation were lower in the hyporheic zone, while the importance of bacteria was elevated. Leaf decomposition was reduced (40%) under fungicide exposure in fine sediment with an effect size more than twice as high as in the benthic zone (15%). These differences are likely triggered by the lower hydraulic conductivity in the hyporheic zone influencing microbial dispersal as well as oxygen and nutrient fluxes. Since insights from the benthic zone are not easily transferable, these results indicate that the hyporheic zone requires a higher recognition with regard to ecotoxicological effects on organic matter decomposition.

Inhibition of CDK2/CyclinE1 by xanthones from the mangosteen ( Garcinia mangostana ): a structure-activity relationship study - Mirielle C. Nauman; Restituto Tocmo; Bhaskar Vemu; Jacob P. Veenstra; Jeremy J. Johnson (Natural Product Research, 2021)

Water-stained leaves: formation and application as a field indicator of wetland hydrology - Jacob F. Berkowitz; Jason P. Pietroski (Wetlands, 2021)
Wetland delineations conducted in the United States utilize field indicators as proxy measures of the presence or absence of wetland hydrology. Water-stained leaves provide a practical, qualitative field indicator of wetland hydrology; however, the formation of water-stained leaves has not been elucidated. In response, leaves from six tree species were examined under five treatments to investigate the water-staining process and concomitant timeframes. Results indicate that leaf staining occurred within 14-21 days of continuous exposure to wetland waters and sediment under both laboratory and field conditions. Leaf staining was characterized by readily observable shifts in leaf color (i.e., decreasing Munsell hue, value, and chroma) causing the leaves to appear very dark or black. No color shifts associated with leaf staining occurred in treatments exposed to upland conditions. The timeframe associated with leaf staining corresponds with established wetland hydrology criteria requiring a minimum hydroperiod of 14 consecutive days of soil saturation, flooding, or ponding. Leaves exposed to wetland waters and sediment underwent color shifts significantly faster and to a greater extent than leaves inundated with deionized water, likely as a result of increased microbial abundance and the presence of anaerobic conditions in the simulated wetland treatments. Results suggest that water-stained leaves 1) are a useful and reliable wetland hydrology field indicator for wetland delineation purposes, 2) may provide a proxy measure of wetland hydroperiod, and 3) Munsell color measurements can help differentiate between leaves exposed to wetland and upland conditions.

Vapor pressure deficit helps explain biogenic volatile organic compound fluxes from the forest floor and canopy of a temperate deciduous forest - Paul C. Stoy; Amy M. Trowbridge; Mario B. Siqueira; Livia Souza Freire; Richard P. Phillips; Luke Jacobs; Susanne Wiesner; Russell K. Monson; Kimberly A. Novick (Oecologia, 2021)

Tracking deepwater oxygen recovery using sedimentary chironomid assemblages: Peninsula Lake revisited - Adam Jeziorski; Clare Nelligan; Dara Corrigan; Carsten Meyer-Jacob; Andrew M. Paterson; John P. Smol (Journal of Paleolimnology, 2021)

Comparative effects of Plutella xylostella (L.) (Lepidoptera: Plutellidae) and Crocidolomia pavonana (F.) (Lepidoptera: Crambidae) on cabbage yield in Tanzania - Aaron Y. Mbogho; Robert Mwashimaha; Omary Mbwambo; Simon B. Boni; Jacob Yarro; Bruno Nyundo; Myron P. Zalucki; Srinivasan Ramasamy (International Journal of Tropical Insect Science, 2021)

Sex differences in cardiovascular adaptations in recreational marathon runners - Jacqueline A. Augustine; Wesley K. Lefferts; Jacob P. DeBlois; Tiago V. Barreira; Beth A. Taylor; Kan Liu; Kevin S. Heffernan (European Journal of Applied Physiology, 2021)

A beginner's guide to low‐coverage whole genome sequencing for population genomics - Runyang Nicolas Lou; Arne Jacobs; Aryn P. Wilder; Nina Overgaard Therkildsen (Molecular Ecology, 2021)
Low‐coverage whole genome sequencing (lcWGS) has emerged as a powerful and cost‐effective approach for population genomic studies in both model and nonmodel species. However, with read depths too low to confidently call individual genotypes, lcWGS requires specialized analysis tools that explicitly account for genotype uncertainty. A growing number of such tools have become available, but it can be difficult to get an overview of what types of analyses can be performed reliably with lcWGS data, and how the distribution of sequencing effort between the number of samples analysed and per‐sample sequencing depths affects inference accuracy. In this introductory guide to lcWGS, we first illustrate how the per‐sample cost for lcWGS is now comparable to RAD‐seq and Pool‐seq in many systems. We then provide an overview of software packages that explicitly account for genotype uncertainty in different types of population genomic inference. Next, we use both simulated and empirical data to assess the accuracy of allele frequency, genetic diversity, and linkage disequilibrium estimation, detection of population structure, and selection scans under different sequencing strategies. Our results show that spreading a given amount of sequencing effort across more samples with lower depth per sample consistently improves the accuracy of most types of inference, with a few notable exceptions. Finally, we assess the potential for using imputation to bolster inference from lcWGS data in nonmodel species, and discuss current limitations and future perspectives for lcWGS‐based population genomics research. With this overview, we hope to make lcWGS more approachable and stimulate its broader adoption.

Global exposure of population and land‐use to meteorological droughts under different warming levels and SSPs : A CORDEX ‐based study - Jonathan Spinoni; Paulo Barbosa; Edoardo Bucchignani; John Cassano; Tereza Cavazos; Alessandro Cescatti; Jens H. Christensen; Ole B. Christensen; Erika Coppola; Jason P. Evans; Giovanni Forzieri; Beate Geyer; et al. (International Journal of Climatology, 2021)
Global warming is likely to cause a progressive drought increase in some regions, but how population and natural resources will be affected is still underexplored. This study focuses on global population, forests, croplands and pastures exposure to meteorological drought hazard in the 21st century, expressed as frequency and severity of drought events. As input, we use a large ensemble of climate simulations from the Coordinated Regional Climate Downscaling Experiment (CORDEX), population projections from the NASA‐SEDAC dataset and land‐use projections from the Land‐Use Harmonization 2 project for 1981–2100. The exposure to drought hazard is presented for five Shared Socioeconomic Pathways (SSP1‐SSP5) at four Global Warming Levels (GWLs: 1.5°C to 4°C). Results show that considering only Standardized Precipitation Index (SPI; based on precipitation), the SSP3 at GWL4 projects the largest fraction of the global population (14%) to experience an increase in drought frequency and severity (versus 1981–2010), with this value increasing to 60% if temperature is considered (indirectly included in the Standardized Precipitation‐Evapotranspiration Index, SPEI). With SPEI, considering the highest GWL for each SSP, 8 (for SSP2, SSP4, SSP5) and 11 (SSP3) billion people, that is, more than 90%, will be affected by at least one unprecedented drought. For SSP5 at GWL4, approximately 2 × 10 6 km 2 of forests and croplands (respectively, 6% and 11%) and 1.5 × 10 6 km 2 of pastures (19%) will be exposed to increased drought frequency and severity according to SPI, but for SPEI this extent will rise to 17 × 10 6 km 2 of forests (49%), 6 × 10 6 km 2 of pastures (78%) and 12 × 10 6 km 2 of croplands (67%), being mid‐latitudes the most affected. The projected likely increase of drought frequency and severity significantly increases population and land‐use exposure to drought, even at low GWLs, thus extensive mitigation and adaptation efforts are needed to avoid the most severe impacts of climate change.

Escaping the fate of Sisyphus: assessing resistome hybridization baits for antimicrobial resistance gene capture - Megan S. Beaudry; Jesse C. Thomas; Rodrigo P. Baptista; Amanda H. Sullivan; William Norfolk; Alison Devault; Jacob Enk; Troy J. Kieran; Olin E. Rhodes; K. Allison Perry‐Dow; Laura J. Rose; Natalia J. Bayona‐Vásquez; et al. (Environmental Microbiology, 2021)
Summary Finding, characterizing and monitoring reservoirs for antimicrobial resistance (AMR) is vital to protecting public health. Hybridization capture baits are an accurate, sensitive and cost‐effective technique used to enrich and characterize DNA sequences of interest, including antimicrobial resistance genes (ARGs), in complex environmental samples. We demonstrate the continued utility of a set of 19 933 hybridization capture baits designed from the Comprehensive Antibiotic Resistance Database (CARD)v1.1.2 and Pathogenicity Island Database (PAIDB)v2.0, targeting 3565 unique nucleotide sequences that confer resistance. We demonstrate the efficiency of our bait set on a custom‐made resistance mock community and complex environmental samples to increase the proportion of on‐target reads as much as >200‐fold. However, keeping pace with newly discovered ARGs poses a challenge when studying AMR, because novel ARGs are continually being identified and would not be included in bait sets designed prior to discovery. We provide imperative information on how our bait set performs against CARDv3.3.1, as well as a generalizable approach for deciding when and how to update hybridization capture bait sets. This research encapsulates the full life cycle of baits for hybridization capture of the resistome from design and validation (both in silico and in vitro ) to utilization and forecasting updates and retirement.

High-Resolution Spatiotemporal Dynamics of Harmful Algae in the Indian River Lagoon (Florida)—A Case Study of Aureoumbra lagunensis, Pyrodinium bahamense, and Pseudo-nitzschia - Cary B. Lopez; Charles L. Tilney; Eric Muhlbach; Josée N. Bouchard; Maria Célia Villac; Karen L. Henschen; Laura R. Markley; Stephanie Keller Abbe; Sugandha Shankar; Colin P. Shea; Leanne Flewelling; Matthew Garrett; et al. (Frontiers in Marine Science, 2021)
The Indian River Lagoon (IRL), located on the east coast of Florida, is a complex estuarine ecosystem that is negatively affected by recurring harmful algal blooms (HABs) from distinct taxonomic/functional groups. Enhanced monitoring was established to facilitate rapid quantification of three recurrent bloom taxa, Aureoumbra lagunensis , Pyrodinium bahamense , and Pseudo-nitzschia spp., and included corroborating techniques to improve the identification of small-celled nanoplankton (<10 μm in diameter). Identification and enumeration of these target taxa were conducted during 2015–2020 using a combination of light microscopy and species-specific approaches, specifically immunofluorescence flow cytometry as well as a newly developed qPCR assay for A. lagunensis presented here for the first time. An annual bloom index (ABI) was established for each taxon based on occurrence and abundance data. Blooms of A. lagunensis (>2 × 10 8 cells L –1 ) were observed in all 6 years sampled and across multiple seasons. In contrast, abundance of P. bahamense , largely driven by the annual temperature cycle that moderates life cycle transitions and growth, displayed a strong seasonal pattern with blooms (10 5 –10 7 cells L –1 ) generally developing in early summer and subsiding in autumn. However, P. bahamense bloom development was delayed and abundance was significantly lower in years and locations with sustained A. lagunensis blooms. Pseudo-nitzschia spp. were broadly distributed with sporadic bloom concentrations (reaching 10 7 cells L –1 ), but with minimal concentrations of the toxin domoic acid detected (<0.02 μg L –1 ). In summer 2020, multiple monitoring tools characterized a novel nano-cyanobacterium bloom (reaching 10 9 cells L –1 ) that coincided with a decline in A. lagunensis and persisted into autumn. Statistical and time-series analyses of this spatiotemporally intensive dataset highlight prominent patterns in variability for some taxa, but also identify challenges of characterizing mechanisms underlying more episodic yet persistent events. Nevertheless, the intersect of temperature and salinity as environmental proxies proved to be informative in delineating niche partitioning, not only in the case of taxa with long-standing data sets but also for seemingly unprecedented blooms of novel nanoplanktonic taxa.

Movescapes and eco‐evolutionary movement strategies in marine fish: Assessing a connectivity hotspot - Susan K. Lowerre‐Barbieri; Claudia Friess; Lucas P. Griffin; Danielle Morley; Gregory B. Skomal; Joel W. Bickford; Neil Hammerschlag; Mitchell J. Rider; Matthew J. Smukall; Maurits P. M. van Zinnicq Bergmann; Tristan L. Guttridge; Andrea M. Kroetz; et al. (Fish and Fisheries, 2021)
Data from the Integrated Tracking of Aquatic Animals in the Gulf of Mexico (iTAG) network, and sister networks, were used to evaluate fish movements in the Florida Keys—an extensive reef fish ecosystem just north of Cuba connecting the Atlantic Ocean and Gulf of Mexico. We analysed ~2 million detections for 23 species, ranging from reef fish such as Nassau grouper ( Epinephelus striatus , Serranidae) to migratory apex predators such as white sharks ( Carcharodon carcharias , Lamnidae). To facilitate comparisons across species, we used an eco‐evolutionary movement strategy framework that identified measurable movement traits and their proximate and ultimate drivers. Detectability was species‐specific and quantified with a detection potential index. Life stages detected in the study area varied by species and residency varied with life stage. Four annual movement types were identified as follows: high site‐fidelity residents, range residents, seasonal migrants and general migrants. The endangered smalltooth sawfish ( Pristis pectinata , Pristidae), a seasonal migrant, exhibited the greatest within‐ecosystem connectivity. Site attachment, stopover and deep‐water migration behaviours differed between individuals, species and annual movement types. All apex predators were migratory. General migrants were significantly larger than fish in the other movement types, a life‐history and movement trait combination that is common but not exclusive, as many small pelagics also migrate. Most teleosts exhibited movements associated with spawning. As concerns grow over habitat and biodiversity loss, multispecies movescapes, such as presented here, are expected to play an increasingly important role in informing ecosystem‐based and non‐extractive fisheries management strategies.

Seabird Migration Strategies: Flight Budgets, Diel Activity Patterns, and Lunar Influence - Anne-Sophie Bonnet-Lebrun; Maria P. Dias; Richard A. Phillips; José P. Granadeiro; M. de L. Brooke; Olivier Chastel; Thomas A. Clay; Annette L. Fayet; Olivier Gilg; Jacob González-Solís; Tim Guilford; Sveinn A. Hanssen; et al. (Frontiers in Marine Science, 2021)
Every year, billions of birds undertake extensive migrations between breeding and non-breeding areas, facing challenges that require behavioural adjustments, particularly to flight timing and duration. Such adjustments in daily activity patterns and the influence of extrinsic factors (e.g., environmental conditions, moonlight) have received much more research attention in terrestrial than marine migrants. Taking advantage of the widespread deployment in recent decades of combined light-level geolocator-immersion loggers, we investigated diel organisation and influence of the moon on flight activities during the non-breeding season of 21 migrant seabird species from a wide taxonomic range (6 families, 3 orders). Migrant seabirds regularly stopped (to either feed or rest) during migration, unlike some terrestrial and wetland birds which fly non-stop. We found an overall increase for most seabird species in time in flight and, for several species, also in flight bout duration, during migration compared to when resident at the non-breeding grounds. Additionally, several nocturnal species spent more of the day in flight during migration than at non-breeding areas, and vice versa for diurnal species. Nocturnal time in flight tended to increase during full moon, both during migration and at the non-breeding grounds, depending on species. Our study provides an extensive overview of activity patterns of migrant seabirds, paving the way for further research on the underlying mechanisms and drivers.

“When the felid’s away, the mesocarnivores play”: seasonal temporal segregation in a neotropical carnivore guild - Shannon P. Finnegan; Mariela G. Gantchoff; Jacob E. Hill; Leandro Silveira; Natalia M. Tôrres; Anah T. Jácomo; Antonio Uzal (Mammalian Biology, 2021)

Distinguishing pure histopathological growth patterns of colorectal liver metastases on CT using deep learning and radiomics: a pilot study - Martijn P. A. Starmans; Florian E. Buisman; Michel Renckens; François E. J. A. Willemssen; Sebastian R. van der Voort; Bas Groot Koerkamp; Dirk J. Grünhagen; Wiro J. Niessen; Peter B. Vermeulen; Cornelis Verhoef; Jacob J. Visser; Stefan Klein (Clinical & Experimental Metastasis, 2021)
Histopathological growth patterns (HGPs) are independent prognosticators for colorectal liver metastases (CRLM). Currently, HGPs are determined postoperatively. In this study, we evaluated radiomics for preoperative prediction of HGPs on computed tomography (CT), and its robustness to segmentation and acquisition variations. Patients with pure HGPs [i.e. 100% desmoplastic (dHGP) or 100% replacement (rHGP)] and a CT-scan who were surgically treated at the Erasmus MC between 2003–2015 were included retrospectively. Each lesion was segmented by three clinicians and a convolutional neural network (CNN). A prediction model was created using 564 radiomics features and a combination of machine learning approaches by training on the clinician’s and testing on the unseen CNN segmentations. The intra-class correlation coefficient (ICC) was used to select features robust to segmentation variations; ComBat was used to harmonize for acquisition variations. Evaluation was performed through a 100 × random-split cross-validation. The study included 93 CRLM in 76 patients (48% dHGP; 52% rHGP). Despite substantial differences between the segmentations of the three clinicians and the CNN, the radiomics model had a mean area under the curve of 0.69. ICC-based feature selection or ComBat yielded no improvement. Concluding, the combination of a CNN for segmentation and radiomics for classification has potential for automatically distinguishing dHGPs from rHGP, and is robust to segmentation and acquisition variations. Pending further optimization, including extension to mixed HGPs, our model may serve as a preoperative addition to postoperative HGP assessment, enabling further exploitation of HGPs as a biomarker.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Ouabain-induced activation of phospholipase C zeta and its contributions to bovine sperm capacitation - Veena Unnikrishnan; John P Kastelic; Jacob C Thundathil (Cell and Tissue Research, 2021)

Modelling potential Pleistocene habitat corridors between Afromontane forest regions - Kaitlin E. Allen; Walter P. Tapondjou; Benedictus Freeman; Jacob C. Cooper; Rafe M. Brown; A. Townsend Peterson (Biodiversity and Conservation, 2021)

Mechanical loading of tissue engineered skeletal muscle prevents dexamethasone induced myotube atrophy - Kathryn W. Aguilar-Agon; Andrew J. Capel; Jacob W. Fleming; Darren J. Player; Neil R. W. Martin; Mark P. Lewis (Journal of Muscle Research and Cell Motility, 2021)
Skeletal muscle atrophy as a consequence of acute and chronic illness, immobilisation, muscular dystrophies and aging, leads to severe muscle weakness, inactivity and increased mortality. Mechanical loading is thought to be the primary driver for skeletal muscle hypertrophy, however the extent to which mechanical loading can offset muscle catabolism has not been thoroughly explored. In vitro 3D-models of skeletal muscle provide a controllable, high throughput environment and mitigating many of the ethical and methodological constraints present during in vivo experimentation. This work aimed to determine if mechanical loading would offset dexamethasone (DEX) induced skeletal muscle atrophy, in muscle engineered using the C2C12 murine cell line. Mechanical loading successfully offset myotube atrophy and functional degeneration associated with DEX regardless of whether the loading occurred before or after 24 h of DEX treatment. Furthermore, mechanical load prevented increases in MuRF-1 and MAFbx mRNA expression, critical regulators of muscle atrophy. Overall, we demonstrate the application of tissue engineered muscle to study skeletal muscle health and disease, offering great potential for future use to better understand treatment modalities for skeletal muscle atrophy.

Migratory Gaddi sheep and goats as potential carriers of Theileria infection: a molecular survey - Gopinath Devi; Y. Ajith; Gorakh Mal; Umesh Dimri; P. Preena; Gauri Jairath; Jobin Jose Kattoor; Siju Susan Jacob; Birbal Singh; Jyoti Babu Dhar (Tropical Animal Health and Production, 2021)

A global reconnaissance of particulates and metals/metalloids in untreated drinking water sources - Jonathan W. Peterson; Benjamin M. Fry; Daniel R. Wade; Ford J. Fishman; Jacob T. Stid; Jonas M. Peterson; Cleveland E. Tarp; Randall D. Wade; Sarah A. Brokus; Michael J. Pikaart; Brent P. Krueger; Aaron A. Best (Environmental Monitoring and Assessment, 2021)
Metal and metalloid contamination in drinking water sources is a global concern, particularly in developing countries. This study used hollow membrane water filters and metal-capturing polyurethane foams to sample 71 drinking water sources in 22 different countries. Field sampling was performed with sampling kits prepared in the lab at Hope College in Holland, MI, USA. Filters and foams were sent back to the lab after sampling, and subsequent analysis of flushates and rinsates allowed the estimation of suspended solids and metal and other analayte concentrations in source waters. Estimated particulate concentrations were 0–92 mg/L, and consisted of quartz, feldspar, and clay, with some samples containing metal oxides or sulfide phases. As and Cu were the only analytes which occurred above the World Health Organization (WHO) guidelines of 10 μg/L and 2000 μg/L, respectively, with As exceeding the guideline in 45% of the sources and Cu in 3%. Except for one value of ~ 285 μg/L, As concentrations were 45–200 μg/L (river), 65–179 μg/L (well), and 112–178 μg/L (tap). Other metals (Ce, Fe, Mg, Mn, Zn) with no WHO guideline were also detected, with Mn the most common. This study demonstrated that filters and foams can be used for reconnaissance characterization of untreated drinking water. However, estimated metal and other analyte concentrations could only be reported as minimum values due to potential incomplete retrieval of foam-bound analytes. A qualitative reporting methodology was used to report analytes as “present” if the concentration was below the WHO guideline, and “present-recommend retesting” if the concentration was quantifiable and above the WHO guideline.

Convergent character displacement in sympatric tamarin calls (Saguinus spp.) - Tainara V. Sobroza; Marcelo Gordo; Pedro A. C. L. Pequeno; Jacob C. Dunn; Wilson R. Spironello; Rafael M. Rabelo; Adrian P. A. Barnett (Behavioral Ecology and Sociobiology, 2021)

Does getting defensive get you anywhere?—Seasonal balancing selection, temperature, and parasitoids shape real‐world, protective endosymbiont dynamics in the pea aphid - Andrew H. Smith; Michael P. O’Connor; Brooke Deal; Coleman Kotzer; Amanda Lee; Barrett Wagner; Jonah Joffe; Stephen Woloszynek; Kerry M. Oliver; Jacob A. Russell (Molecular Ecology, 2021)
Facultative, heritable endosymbionts are found at intermediate prevalence within most insect species, playing frequent roles in their hosts’ defence against environmental pressures. Focusing on Hamiltonella defensa , a common bacterial endosymbiont of aphids, we tested the hypothesis that such pressures impose seasonal balancing selection, shaping a widespread infection polymorphism. In our studied pea aphid ( Acyrthosiphon pisum ) population, Hamiltonella frequencies ranged from 23.2% to 68.1% across a six‐month longitudinal survey. Rapid spikes and declines were often consistent across fields, and we estimated that selection coefficients for Hamiltonella ‐infected aphids changed sign within this field season. Prior laboratory research suggested antiparasitoid defence as the major Hamiltonella benefit, and costs under parasitoid absence. While a prior field study suggested these forces can sometimes act as counter‐weights in a regime of seasonal balancing selection, our present survey showed no significant relationship between parasitoid wasps and Hamiltonella prevalence. Field cage experiments provided some explanation: parasitoids drove modest ~10% boosts to Hamiltonella frequencies that would be hard to detect under less controlled conditions. They also showed that Hamiltonella was not always costly under parasitoid exclusion, contradicting another prediction. Instead, our longitudinal survey – and two overwintering studies – showed temperature to be the strongest predictor of Hamiltonella prevalence. Matching some prior lab discoveries, this suggested that thermally sensitive costs and benefits, unrelated to parasitism, can shape Hamiltonella dynamics. These results add to a growing body of evidence for rapid, seasonal adaptation in multivoltine organisms, suggesting that such adaptation can be mediated through the diverse impacts of heritable bacterial endosymbionts.

Mutualism disruption by an invasive ant reduces carbon fixation for a foundational East African ant‐plant - Patrick D. Milligan; Timothy A. Martin; Grace P. John; Corinna Riginos; Jacob R. Goheen; Scott M. Carpenter; Todd M. Palmer (Ecology Letters, 2021)
Invasive ants shape assemblages and interactions of native species, but their effect on fundamental ecological processes is poorly understood. In East Africa, Pheidole megacephala ants have invaded monodominant stands of the ant‐tree Acacia drepanolobium , extirpating native ant defenders and rendering trees vulnerable to canopy damage by vertebrate herbivores. We used experiments and observations to quantify direct and interactive effects of invasive ants and large herbivores on A. drepanolobium photosynthesis over a 2‐year period. Trees that had been invaded for ≥ 5 years exhibited 69% lower whole‐tree photosynthesis during key growing seasons, resulting from interaction between invasive ants and vertebrate herbivores that caused leaf‐ and canopy‐level photosynthesis declines. We also surveyed trees shortly before and after invasion, finding that recent invasion induced only minor changes in leaf physiology. Our results from individual trees likely scale up, highlighting the potential of invasive species to alter ecosystem‐level carbon fixation and other biogeochemical cycles.

Refining Fisheries Advice With Stock-Specific Ecosystem Information - Jacob W. Bentley; Mathieu G. Lundy; Daniel Howell; Steven E. Beggs; Alida Bundy; Francisco de Castro; Clive J. Fox; Johanna J. Heymans; Christopher P. Lynam; Debbi Pedreschi; Pia Schuchert; Natalia Serpetti; et al. (Frontiers in Marine Science, 2021)
Although frequently suggested as a goal for ecosystem-based fisheries management, incorporating ecosystem information into fisheries stock assessments has proven challenging. The uncertainty of input data, coupled with the structural uncertainty of complex multi-species models, currently makes the use of absolute values from such models contentious for short-term single-species fisheries management advice. Here, we propose a different approach where the standard assessment methodologies can be enhanced using ecosystem model derived information. Using a case study of the Irish Sea, we illustrate how stock-specific ecosystem indicators can be used to set an ecosystem-based fishing mortality reference point (F ECO ) within the “Pretty Good Yield” ranges for fishing mortality which form the present precautionary approach adopted in Europe by the International Council for the Exploration of the Sea (ICES). We propose that this new target, F ECO , can be used to scale fishing mortality down when the ecosystem conditions for the stock are poor and up when conditions are good. This approach provides a streamlined quantitative way of incorporating ecosystem information into catch advice and provides an opportunity to operationalize ecosystem models and empirical indicators, while retaining the integrity of current assessment models and the F MSY -based advice process.

Seasonal variability in planktonic food web structure and function of the Northeast U.S. Shelf - Pierre Marrec; Heather McNair; Gayantonia Franzè; Françoise Morison; Jacob P. Strock; Susanne Menden‐Deuer (Limnology and Oceanography, 2021)
Herbivorous consumption of primary production is a key transformation in global biogeochemical cycles, directing matter and energy either to higher trophic levels, export production, or remineralization. Grazing by microzooplankton is often poorly constrained, particularly in dynamic coastal systems. Temperate coastal areas are seasonally and spatially variable, which presents both challenges and opportunities to identify patterns and drivers of grazing pressure. Here we report on two winter and one summer week‐long cruises (2018–2019), as part of the new Northeast U.S. Shelf Long‐Term Ecological Research program. During both seasons, coastal waters were colder and fresher, and had higher phytoplankton biomass than waters at the shelf break. The phytoplankton community was dominated by large cells in winter and by small cells in summer. Phytoplankton growth rates ranged from −1 in winter and up to 1.4 d −1 in summer and were strongly correlated to temperature, to light availability, and to phytoplankton community size‐structure. Grazing rates were not correlated with total chlorophyll a , which points to other biological drivers, including species composition in predator‐prey interactions at the first trophic level. The percentage of primary production consumed (%PP) indicated higher trophic transfer in winter (%PP > 50%) than during summer (%PP

Effects of Nutrient Management Scenarios on Marine Food Webs: A Pan-European Assessment in Support of the Marine Strategy Framework Directive - Chiara Piroddi; Ekin Akoglu; Eider Andonegi; Jacob W. Bentley; Igor Celić; Marta Coll; Donna Dimarchopoulou; René Friedland; Kim de Mutsert; Raphael Girardin; Elisa Garcia-Gorriz; Bruna Grizzetti; et al. (Frontiers in Marine Science, 2021)
Eutrophication is one of the most important anthropogenic pressures impacting coastal seas. In Europe, several legislations and management measures have been implemented to halt nutrient overloading in marine ecosystems. This study evaluates the impact of freshwater nutrient control measures on higher trophic levels (HTL) in European marine ecosystems following descriptors and criteria as defined by the Marine Strategy Framework Directive (MSFD). We used a novel pan-European marine modeling ensemble of fourteen HTL models, covering almost all the EU seas, under two nutrient management scenarios. Results from our projections suggest that the proposed nutrient reduction measures may not have a significant impact on the structure and function of European marine ecosystems. Among the assessed criteria, the spawning stock biomass of commercially important fish stocks and the biomass of small pelagic fishes would be the most impacted, albeit with values lower than 2.5%. For the other criteria/indicators, such as species diversity and trophic level indicators, the impact was lower. The Black Sea and the North-East Atlantic were the most negatively impacted regions, while the Baltic Sea was the only region showing signs of improvement. Coastal and shelf areas were more sensitive to environmental changes than large regional and sub-regional ecosystems that also include open seas. This is the first pan-European multi-model comparison study used to assess the impacts of land-based measures on marine and coastal European ecosystems through a set of selected ecological indicators. Since anthropogenic pressures are expanding apace in the marine environment and policy makers need to use rapid and effective policy measures for fast-changing environments, this modeling framework is an essential asset in supporting and guiding EU policy needs and decisions.

Correction to: Population cycles and outbreaks of small rodents: ten essential questions we still need to solve - Harry P. Andreassen; Janne Sundell; Fraucke Ecke; Stefan Halle; Marko Haapakoski; Heikki Henttonen; Otso Huitu; Jens Jacob; Kaja Johnsen; Esa Koskela; Juan Jose Luque-Larena; Nicolas Lecomte; et al. (Oecologia, 2021)
Authors would like to correct error in affiliation in the original publication of the article.

Population cycles and outbreaks of small rodents: ten essential questions we still need to solve - Harry P. Andreassen; Janne Sundell; Fraucke Ecke; Stefan Halle; Marko Haapakoski; Heikki Henttonen; Otso Huitu; Jens Jacob; Kaja Johnsen; Esa Koskela; Juan Jose Luque-Larena; Nicolas Lecomte; et al. (Oecologia, 2021)
Most small rodent populations in the world have fascinating population dynamics. In the northern hemisphere, voles and lemmings tend to show population cycles with regular fluctuations in numbers. In the southern hemisphere, small rodents tend to have large amplitude outbreaks with less regular intervals. In the light of vast research and debate over almost a century, we here discuss the driving forces of these different rodent population dynamics. We highlight ten questions directly related to the various characteristics of relevant populations and ecosystems that still need to be answered. This overview is not intended as a complete list of questions but rather focuses on the most important issues that are essential for understanding the generality of small rodent population dynamics.

Long-term primary production trends in the Laurentian Great Lakes: a comparison of geochemical methods - Euan D. Reavie; Meijun Cai; Carsten Meyer-Jacob; John P. Smol; Josef P. Werne (Journal of Paleolimnology, 2021)

Correction to: Addition of nectar sources affects a parasitoid community without improving pest suppression - Jacob H. Miall; Paul K. Abram; Naomi Cappuccino; Andrew M. R. Bennett; José L. Fernández-Triana; Gary A. P. Gibson; Peter G. Mason (Journal of Pest Science, 2021)

Addition of nectar sources affects a parasitoid community without improving pest suppression - Jacob H. Miall; Paul K. Abram; Naomi Cappuccino; Andrew M. R. Bennett; José L. Fernández-Triana; Gary A. P. Gibson; Peter G. Mason (Journal of Pest Science, 2021)

Sharing and reporting benefits from biodiversity research - Emily Marden; Richard J. Abbott; Frédéric Austerlitz; Daniel Ortiz‐Barrientos; Regina S. Baucom; Pim Bongaerts; Aurélie Bonin; Camille Bonneaud; Luke Browne; C. Alex Buerkle; Ana L. Caicedo; David W. Coltman; et al. (Molecular Ecology, 2021)

Temperature acclimation alters phytoplankton growth and production rates - Jacob P. Strock; Susanne Menden‐Deuer (Limnology and Oceanography, 2021)
Temperature is a major driver of phytoplankton growth and physiology, but despite decades of study on temperature effects, the influence of temperature fluctuations on the growth acclimation of marine phytoplankton is largely unknown. To address this knowledge gap, we subjected a coastal phytoplankton species, Heterosigma akashiwo , to ecologically relevant temperature shifts of 2–3°C, cumulatively totaling 3–16°C across a range from 6°C to 31°C over a 3‐week period. Using a symmetric design, we show time dependent differences between growth rates and that these changes were related to the magnitude of the temperature shift, but not the direction. Cell size scaled inversely with temperature at a rate of −1.9 to −3.3%°C −1 at all except the highest temperature treatments > 25°C. Intraspecific variability in growth rates increased exponentially with cumulative thermal shifts, suggesting thermal variability may be a driver of intraspecific variation. The observed acclimation effects on phytoplankton growth rates suggest that ignoring acclimation effects could systematically under or overestimate temperature‐dependent primary production. Empirical results, contextualized with in situ coastal ocean temperature record, demonstrated that daily primary production could differ from current model assumptions utilizing acclimated rates by −33% to +36%. If broadly applicable to diverse phytoplankton species, these results have ramifications for predicting the ecology and production of phytoplankton in present day dynamic ecosystems and in future climate scenarios where thermal variability is expected to increase.

Spatial Connectivity and Drivers of Shark Habitat Use Within a Large Marine Protected Area in the Caribbean, The Bahamas Shark Sanctuary - Austin J. Gallagher; Oliver N. Shipley; Maurits P. M. van Zinnicq Bergmann; Jacob W. Brownscombe; Craig P. Dahlgren; Michael G. Frisk; Lucas P. Griffin; Neil Hammerschlag; Sami Kattan; Yannis P. Papastamatiou; Brendan D. Shea; Steven T. Kessel; et al. (Frontiers in Marine Science, 2021)
Marine protected areas (MPAs) have emerged as potentially important conservation tools for the conservation of biodiversity and mitigation of climate impacts. Among MPAs, a large percentage has been created with the implicit goal of protecting shark populations, including 17 shark sanctuaries which fully protect sharks throughout their jurisdiction. The Commonwealth of the Bahamas represents a long-term MPA for sharks, following the banning of commercial longlining in 1993 and subsequent designation as a shark sanctuary in 2011. Little is known, however, about the long-term behavior and space use of sharks within this protected area, particularly among reef-associated sharks for which the sanctuary presumably offers the most benefit. We used acoustic telemetry to advance our understanding of the ecology of such sharks, namely Caribbean reef sharks ( Carcharhinus perezi ) and tiger sharks ( Galeocerdo cuvier ), over two discrete islands (New Providence and Great Exuma) varying in human activity level, over 2 years. We evaluated which factors influenced the likelihood of detection of individuals, analyzed patterns of movement and occurrence, and identified variability in habitat selection among species and regions, using a dataset of 23 Caribbean reef sharks and 15 tiger sharks which were passively monitored in two arrays with a combined total of 13 acoustic receivers. Caribbean reef sharks had lower detection probabilities than tiger sharks, and exhibited relatively low habitat connectivity and high residency, while tiger sharks demonstrated wider roaming behavior across much greater space. Tiger sharks were associated with shallow seagrass habitats where available, but frequently transited between and connected different habitat types. Our data support the notion that large MPAs afford greater degrees of protection for highly resident species such as Caribbean reef sharks, yet still may provide substantial benefits for more migratory species such as tiger sharks. We discuss these findings within the context of species-habitat linkages, ecosystem services, and the establishment of future MPAs.

2-Aminoimidazoles as potent inhibitors of contaminating brewery biofilms - Lene Jacobs; Jolien Meesters; Ilse Parijs; Geert Hooyberghs; Erik V. Van der Eycken; Bram Lories; Hans P. Steenackers (Biofouling, 2021)

Population Pharmacokinetics of Intracellular 5-Fluorouridine 5′-Triphosphate and its Relationship with Hand-and-Foot Syndrome in Patients Treated with Capecitabine - Julie M. Janssen; Bart A. W. Jacobs; Jeroen Roosendaal; Ellen J. B. Derissen; Serena Marchetti; Jos H. Beijnen; Alwin D. R. Huitema; Thomas P. C. Dorlo (The AAPS Journal, 2021)

Novel approach of multi-targeted thiazoles and thiazolidenes toward anti-inflammatory and anticancer therapy—dual inhibition of COX-2 and 5-LOX enzymes - Jaismy Jacob P; Manju S L (Medicinal Chemistry Research, 2021)

Reliability and validity of the COSMED K5 portable metabolic system during walking - Jacob P. DeBlois; Lindsey E. White; Tiago V. Barreira (European Journal of Applied Physiology, 2021)

Tectonic appraisal of the Mid-Thane Creek of Mumbai, India: An integrated geophysical approach - J Jacob; V K Pitchika; K M Dubey; A Mishra; P Kumar; S Kumar; V P Mahale; A K Chaubey (Journal of Earth System Science, 2020)

Influence of sprint exercise on aortic pulse wave velocity and femoral artery shear patterns - Jacob P. DeBlois; Wesley K. Lefferts; Kevin S. Heffernan (European Journal of Applied Physiology, 2020)

Mud, Microbes, and Macrofauna: Seasonal Dynamics of the Iron Biogeochemical Cycle in an Intertidal Mudflat - Jacob P. Beam; Sarabeth George; Nicholas R. Record; Peter D. Countway; David T. Johnston; Peter R. Girguis; David Emerson (Frontiers in Marine Science, 2020)

Do Head Injury Biomechanics Predict Concussion Clinical Recovery in College American Football Players? - Jason P. Mihalik; Avinash Chandran; Jacob R. Powell; Patricia R. Roby; Kevin M. Guskiewicz; Brian D. Stemper; Alok S. Shah; Steven Rowson; Stefan Duma; Jaroslaw Harezlak; Larry Riggen; Steven P. Broglio; et al. (Annals of Biomedical Engineering, 2020)

Application of machine learning algorithms to identify cryptic reproductive habitats using diverse information sources - Jacob W. Brownscombe; Lucas P. Griffin; Danielle Morley; Alejandro Acosta; John Hunt; Susan K. Lowerre-Barbieri; Aaron J. Adams; Andy J. Danylchuk; Steven J. Cooke (Oecologia, 2020)

The Toxicology Investigators Consortium Case Registry—the 2019 Annual Report - Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Kim Aldy; Diane P. Calello; Sharan L. Campleman; Shao Li; Gillian A Beauchamp; Timothy Wiegand; Paul M. Wax; Jeffery Brent; P. A. Akpunonu; et al. (Journal of Medical Toxicology, 2020)

Rabies virus infection in mice up-regulates B7-H1 via epigenetic modifications - Comfort E. Ojedapo; Aliyu Muhammad; Grace S. N. Kia; Musa M. Abarshi; Maryam Abdulazeez; Joy Cecilia Atawodi; Jacob K. P. Kwaga (VirusDisease, 2020)

Recovery of mycorrhizal fungi from wild collected protocorms of Madagascan endemic orchid Aerangis ellisii (B.S. Williams) Schltr. and their use in seed germination in vitro - Jonathan P. Kendon; Kazutomo Yokoya; Lawrence W. Zettler; Alison S. Jacob; Faye McDiarmid; Martin I. Bidartondo; Viswambharan Sarasan (Mycorrhiza, 2020)
Orchid mycorrhizal fungi (OMF) are critical for seed germination and maintaining natural populations of orchids, yet the degree of specificity of most orchids to their mycorrhizal associates remains unknown. Many orchids are at risk of extinction, whether generalists or specialists, but orchid species of narrow fungal specificity are arguably under increased threat due to their requirement for specific fungal symbionts. This study characterises the fungi associated with Aerangis ellisii , a lithophytic orchid from a site in the Central Highlands of Madagascar. Culturable OMF isolated from spontaneous protocorms of this species from the wild were used for seed germination. In vitro germination and seedling development of A. ellisii were achieved with fungi derived from A. ellisii and an isolate from a different Aerangis species 30 km away. The significance of these findings and their importance to conservation strategies for this species and other Aerangis spp. is discussed. These results have important implications for the conservation of A. ellisii populations in Madagascar.

Progress in Operational Modeling in Support of Oil Spill Response - Christopher H. Barker; Vassiliki H. Kourafalou; CJ Beegle-Krause; Michel Boufadel; Mark A. Bourassa; Steve G. Buschang; Yannis Androulidakis; Eric P. Chassignet; Knut-Frode Dagestad; Donald G. Danmeier; Anusha L. Dissanayake; Jerry A. Galt; et al. (Journal of Marine Science and Engineering, 2020)
Following the 2010 Deepwater Horizon accident of a massive blow-out in the Gulf of Mexico, scientists from government, industry, and academia collaborated to advance oil spill modeling and share best practices in model algorithms, parameterizations, and application protocols. This synergy was greatly enhanced by research funded under the Gulf of Mexico Research Initiative (GoMRI), a 10-year enterprise that allowed unprecedented collection of observations and data products, novel experiments, and international collaborations that focused on the Gulf of Mexico, but resulted in the generation of scientific findings and tools of broader value. Operational oil spill modeling greatly benefited from research during the GoMRI decade. This paper provides a comprehensive synthesis of the related scientific advances, remaining challenges, and future outlook. Two main modeling components are discussed: Ocean circulation and oil spill models, to provide details on all attributes that contribute to the success and limitations of the integrated oil spill forecasts. These forecasts are discussed in tandem with uncertainty factors and methods to mitigate them. The paper focuses on operational aspects of oil spill modeling and forecasting, including examples of international operational center practices, observational needs, communication protocols, and promising new methodologies.

Long-Term Changes in Chironomid Assemblages Linked to Lake Liming and Fertilization in Previously Acidified Middle Lake (Sudbury, Canada) - Stephanie Pegler; Brigitte Simmatis; Andrew L. Labaj; Carsten Meyer-Jacob; John P. Smol (Water, Air, & Soil Pollution, 2020)

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Fitness, independent of physical activity is associated with cerebral blood flow in adults at risk for Alzheimer’s disease - Ryan J. Dougherty; Elizabeth A. Boots; Jacob B. Lindheimer; Aaron J. Stegner; Stephanie Van Riper; Dorothy F. Edwards; Catherine L. Gallagher; Cynthia M. Carlsson; Howard A. Rowley; Barbara B. Bendlin; Sanjay Asthana; Bruce P. Hermann; et al. (Brain Imaging and Behavior, 2020)

A first-of-its-kind multi-model convection permitting ensemble for investigating convective phenomena over Europe and the Mediterranean - Erika Coppola; Stefan Sobolowski; E. Pichelli; F. Raffaele; B. Ahrens; I. Anders; N. Ban; S. Bastin; M. Belda; D. Belusic; A. Caldas-Alvarez; R. M. Cardoso; et al. (Climate Dynamics, 2020)

An updated geographic distribution of Myxobolus cerebralis (Hofer, 1903) (Bivalvulida: Myxobolidae) and the first diagnosed case of whirling disease in wild‐caught trout in the south‐eastern United States - Steven P. Ksepka; Jacob M. Rash; Brandon L. Simcox; Doug A. Besler; Haley R. Dutton; Micah B. Warren; Stephen A. Bullard (Journal of Fish Diseases, 2020)
Myxobolus cerebralis (Bivalvulida: Myxobolidae), the aetiological agent of salmonid whirling disease, was detected in 2 river basins of North Carolina during 2015, which initiated the largest spatial–temporal monitoring project for the disease ever conducted within the south‐eastern United States (focused mainly in eastern Tennessee and western North Carolina). A total of 2072 rainbow trout Oncorhynchus mykiss , 1,004 brown trout Salmo trutta and 468 brook trout Salvelinus fontinalis were screened from 113 localities within 7 river basins during June 2017 through October 2019. Infections were detected by pepsin–trypsin digest, microscopy and the species‐specific nested polymerase chain reaction (PCR) in 19 localities across 6 river basins. Myxospore morphology was indistinguishable from the published literature. In 2019, five rainbow trout that symptomatic for whirling disease (sloping neurocranium and lordosis) were captured and processed for histopathology. Myxospores were detected in the calvarial cartilage of two deformed trout with associated erosion of the cartilage consistent with reported whirling disease lesions. This is the first report of M. cerebralis in Tennessee and the first histologically confirmed cases of whirling disease in southern Appalachian (south‐eastern United States) rivers and streams and expands the distribution of M. cerebralis throughout western North Carolina and eastern Tennessee.

Are the factors recommended by UNEP-SETAC for evaluating biodiversity in LCA achieving their promises: a case study of corrugated boxes produced in the US - Caroline Gaudreault; Craig Loehle; Stephen Prisley; Kevin A. Solarik; Jacob P. Verschuyl (The International Journal of Life Cycle Assessment, 2020)
Purpose We tested the effectiveness of the global and ecoregion-based average characterization factors (CFs) for “Potential Species Loss” recommended by the UNEP-SETAC Life Cycle Initiative to identify hotspots and improvement opportunities compared to using a land competition indicator for a product for which the predominant life cycle use of land is forest management. Methods For a case study of average corrugated boxes produced in the US, system boundaries were defined to encompass all life cycle stages from forest management to disposal. Fiber procurement was regionalized to US ecoregions, and (Chaudhary et al. Environ Sci Technol 49:9987–9995, 2015) ecoregion-specific CFs were applied. US-average CFs were applied to other background processes. Hotspots were identified using contribution analyses, and improvement opportunities were evaluated using scenarios. We compared the results with those from applying a land competition indicator, often used as a proxy for biodiversity in LCA. Results and discussion Forest management was identified as the activity within the life cycle of corrugated boxes that uses the greatest amount of land, allowing the definition of two potential improvement opportunities: reducing fiber consumption and intensifying forest management. By applying the recommended CFs, fiber procurement was also identified as the main contributor to “Potential Species Loss.” The CFs also allowed to identify ecoregions in which species were potentially the most affected by forest management and related potential improvement opportunities. Tradeoffs between taxonomic groups were discussed. In some cases, the results contradicted those from applying a land competition indicator, and in many cases, we were unable to reconcile the results obtained with existing scientific knowledge on species diversity and forest management. Conclusions and recommendations The results obtained by applying the recommended CFs could not always be reconciled with existing scientific knowledge on the effect of forest management on species diversity, significantly impairing the usefulness of these factors for assessing improvement opportunities and increasing the risk of counterproductive decisions. The local effect on species of forest management is likely to be misrepresented by the average number of species in a given ecoregion. Successful consideration of biodiversity response in the context of forest management would require the integration of other approaches, such as site-specific studies. Potential improvements to the proposed method include further spatialization of the CFs, defining a range of forest management practices for which CFs would be defined, considering forest productivity, and defining CFs using a baseline that would encourage better practices even within a given existing management regime.

Induction of Rabies Virus Infection in Mice Brain may Up and Down Regulate Type II Interferon gamma via epigenetic modifications - Maryam Abdulazeez; Grace S. N. Kia; Musa M. Abarshi; Aliyu Muhammad; Comfort E. Ojedapo; Joy Cecilia Atawodi; David Dantong; Jacob K. P. Kwaga (Metabolic Brain Disease, 2020)

Bacterial communities on the gills of bonefish (Albula vulpes) in the Florida Keys and The Bahamas show spatial structure and differential abundance of disease-associated bacteria - Christopher D. Dunn; Lewis J. Campbell; Elizabeth M. Wallace; Andy J. Danylchuk; Steven J. Cooke; Aaron D. Shultz; Brooke D. Black; Jacob W. Brownscombe; Lucas P. Griffin; David P. Philipp; Aaron J. Adams; Tony L. Goldberg (Marine Biology, 2020)

Fire history across the Little Ice Age in southern Pacific Costa Rica - Erik N. Johanson; Sally P. Horn; Chad S. Lane; Maureen Sánchez; Jacob Cecil (Journal of Paleolimnology, 2020)

Quantitative trait loci mapping for resistance to maize streak virus in F2:3 population of tropical maize - A. L. Garcia-Oliveira; A. Menkir; P. Lava Kumar; V. Azuh; O. O. Jacob; M. Gedil (Cereal Research Communications, 2020)
Maize streak virus (MSV) continues to be a major biotic constraint for maize production throughout Africa. Concerning the quantitative nature of inheritance of resistance to MSV disease (MSVD), we sought to identify new loci for MSV resistance in maize using F 2:3 population. The mapping population was artificially inoculated with viruliferous leafhoppers under screenhouse and evaluated for MSVD resistance. Using 948 DArT markers, we identified 18 quantitative trait loci (QTLs) associated with different components of MSVD resistance accounting for 3.1–21.4% of the phenotypic variance, suggesting that a total of eleven genomic regions covering chromosomes 1, 2, 3, 4, 5 and 7 are probably required for MSVD resistance. Two new genomic regions on chromosome 4 revealed the occurrence of co-localized QTLs for different parameters associated with MSVD resistance. Moreover, the consistent appearance of QTL on chromosome 7 for MSVD resistance is illustrating the need for fine-mapping of this locus. In conclusion, these QTLs could provide additional source for breeders to develop MSV resistance.

Post-windthrow salvage logging increases seedling and understory diversity with little impact on composition immediately after logging - Jacob B. Slyder; John W. Wenzel; Alejandro A. Royo; Michelle Elise Spicer; Walter P. Carson (New Forests, 2020)

Towards resolving the phosphorus chaos created by food systems - Paul J. A. Withers; Kirsty G. Forber; Christopher Lyon; Shane Rothwell; Donnacha G. Doody; Helen P. Jarvie; Julia Martin-Ortega; Brent Jacobs; Dana Cordell; Myles Patton; Miller A. Camargo-Valero; Rachel Cassidy (Ambio, 2020)
The chaotic distribution and dispersal of phosphorus (P) used in food systems (defined here as disorderly disruptions to the P cycle) is harming our environment beyond acceptable limits. An analysis of P stores and flows across Europe in 2005 showed that high fertiliser P inputs relative to productive outputs was driving low system P efficiency (38 % overall). Regional P imbalance (P surplus) and system P losses were highly correlated to total system P inputs and animal densities, causing unnecessary P accumulation in soils and rivers. Reducing regional P surpluses to zero increased system P efficiency (+ 16 %) and decreased total P losses by 35 %, but required a reduction in system P inputs of ca. 40 %, largely as fertiliser. We discuss transdisciplinary and transformative solutions that tackle the P chaos by collective stakeholder actions across the entire food value chain. Lowering system P demand and better regional governance of P resources appear necessary for more efficient and sustainable food systems.

Cercospora cf. nicotianae is a causal agent of Cercospora leaf blight of soybean - Francisco J. Sautua; Jacob Searight; Vinson P. Doyle; María M. Scandiani; Marcelo A. Carmona (European Journal of Plant Pathology, 2020)

Correction to: Alternative NADH dehydrogenase extends lifespan and increases resistance to xenobiotics in Drosophila - Dmytro V. Gospodaryov; Olha M. Strilbytska; Uliana V. Semaniuk; Natalia V. Perkhulyn; Bohdana M. Rovenko; Ihor S. Yurkevych; Ana G. Barata; Tobias P. Dick; Oleh V. Lushchak; Howard T. Jacobs (Biogerontology, 2020)
The article Alternative NADH dehydrogenase extends lifespan and increases resistance to xenobiotics in Drosophila , written by Dmytro V. Gospodaryov. Olha M. Strilbytska. Uliana V. Semaniuk. Natalia V. Perkhulyn. Bohdana M. Rovenko. Ihor S. Yurkevych. Ana G. Barata. Tobias P. Dick. Oleh V. Lushchak and Howard T. Jacobs, was originally published electronically on the publisher’s internet portal on 20 November 2019 without open access. With the author(s)’ decision to opt for Open Choice the copyright of the article changed on 27 January 2020 to © The Author(s) 2020 and the article is forthwith distributed under a Creative Commons Attribution 4.0 International License (https://creativecommons.org/licenses/by/4.0/), which permits use, sharing, adaptation, distribution and reproduction in any medium or format, as long as you give appropriate credit to the original author(s) and the source, provide a link to the Creative Commons licence, and indicate if changes were made. The original article has been corrected.

Alternative NADH dehydrogenase extends lifespan and increases resistance to xenobiotics in Drosophila - Dmytro V. Gospodaryov; Olha M. Strilbytska; Uliana V. Semaniuk; Natalia V. Perkhulyn; Bohdana M. Rovenko; Ihor S. Yurkevych; Ana G. Barata; Tobias P. Dick; Oleh V. Lushchak; Howard T. Jacobs (Biogerontology, 2020)
Mitochondrial alternative NADH dehydrogenase (aNDH) was found to extend lifespan when expressed in the fruit fly. We have found that fruit flies expressing aNDH from Ciona intestinalis (NDX) had 17–71% lifespan prolongation on media with different protein-tocarbohydrate ratios except NDX-expressing males that had 19% shorter lifespan than controls on a high protein diet. NDX-expressing flies were more resistant to organic xenobiotics, 2,4-dichlorophenoxyacetic acid and alloxan, and inorganic toxicant potassium iodate, and partially to sodium molybdate treatments. On the other hand, NDX-expressing flies were more sensitive to catechol and sodium chromate. Enzymatic analysis showed that NDX-expressing males had higher glucose 6-phosphate dehydrogenase activity, whilst both sexes showed increased glutathione S -transferase activity.

Preparing for a changing future in recreational fisheries: 100 research questions for global consideration emerging from a horizon scan - Peter E. Holder; Amanda L. Jeanson; Robert J. Lennox; Jacob W. Brownscombe; Robert Arlinghaus; Andy J. Danylchuk; Shannon D. Bower; Kieran Hyder; Len M. Hunt; Eli P. Fenichel; Paul A. Venturelli; Eva B. Thorstad; et al. (Reviews in Fish Biology and Fisheries, 2020)

Local climate determines vulnerability to camouflage mismatch in snowshoe hares - Marketa Zimova; Alexej P. K. Sirén; Joshua J. Nowak; Alexander M. Bryan; Jacob S. Ivan; Toni Lyn Morelli; Skyler L. Suhrer; Jesse Whittington; L. Scott Mills (Global Ecology and Biogeography, 2020)
Aim Phenological mismatches, when life‐events become mistimed with optimal environmental conditions, have become increasingly common under climate change. Population‐level susceptibility to mismatches depends on how phenology and phenotypic plasticity vary across a species’ distributional range. Here, we quantify the environmental drivers of colour moult phenology, phenotypic plasticity, and the extent of phenological mismatch in seasonal camouflage to assess vulnerability to mismatch in a common North American mammal. Location North America. Time period 2010–2017. Major taxa studied Snowshoe hare ( Lepus americanus ). Methods We used > 5,500 by‐catch photographs of snowshoe hares from 448 remote camera trap sites at three independent study areas. To quantify moult phenology and phenotypic plasticity, we used multinomial logistic regression models that incorporated geospatial and high‐resolution climate data. We estimated occurrence of camouflage mismatch between hares’ coat colour and the presence and absence of snow over 7 years of monitoring. Results Spatial and temporal variation in moult phenology depended on local climate conditions more so than on latitude. First, hares in colder, snowier areas moulted earlier in the fall and later in the spring. Next, hares exhibited phenotypic plasticity in moult phenology in response to annual variation in temperature and snow duration, especially in the spring. Finally, the occurrence of camouflage mismatch varied in space and time; white hares on dark, snowless background occurred primarily during low‐snow years in regions characterized by shallow, short‐lasting snowpack. Main conclusions Long‐term climate and annual variation in snow and temperature determine coat colour moult phenology in snowshoe hares. In most areas, climate change leads to shorter snow seasons, but the occurrence of camouflage mismatch varies across the species’ range. Our results underscore the population‐specific susceptibility to climate change‐induced stressors and the necessity to understand this variation to prioritize the populations most vulnerable under global environmental change.

Accumulation of high magnitude acceleration events predicts cerebrovascular reactivity changes in female high school soccer athletes - Diana O. Svaldi; Chetas Joshi; Emily C. McCuen; Jacob P. Music; Robert Hannemann; Larry J. Leverenz; Eric A. Nauman; Thomas M. Talavage (Brain Imaging and Behavior, 2020)

Characteristics of thunder and electromagnetic pulses from volcanic lightning at Bogoslof volcano, Alaska - Matthew M. Haney; Alexa R. Van Eaton; John J. Lyons; Rebecca L. Kramer; David Fee; Alexandra M. Iezzi; Robert P. Dziak; Jacob Anderson; Jeffrey B. Johnson; Jeff L. Lapierre; Michael Stock (Bulletin of Volcanology, 2020)

Status epilepticus and white matter ischemia complicating dural arteriovenous fistula - M. Derasse; K. Jacobs; T. Duprez; P. Goffette; P. Hantson (Acta Neurologica Belgica, 2020)

Seasonal occupancy and connectivity amongst nearshore flats and reef habitats by permit Trachinotus falcatus : considerations for fisheries management - Jacob W. Brownscombe; Lucas P. Griffin; Danielle Morley; Alejandro Acosta; John Hunt; Susan K. Lowerre‐Barbieri; Glenn T. Crossin; Sara J. Iverson; Ross Boucek; Aaron J. Adams; Steven J. Cooke; Andy J. Danylchuk (Journal of Fish Biology, 2020)
We used acoustic telemetry to quantify permit Trachinotus falcatus habitat use and connectivity in proximity to the Florida Keys, USA, and assessed these patterns relative to current habitat and fisheries management practices. From March 2017 to June 2018, 45 permit tagged within 16 km of the lower Florida Keys were detected at stationary acoustic receivers throughout the south Florida region, the majority of which remained within the Special Permit Zone, where more extensive fisheries harvest regulations are implemented. There was a high level of connectivity between nearshore flats ( i.e. ,

Bioextractive Removal of Nitrogen by Oysters in Great Bay Piscataqua River Estuary, New Hampshire, USA - Suzanne B. Bricker; Raymond E. Grizzle; Philip Trowbridge; Julie M. Rose; Joao G. Ferreira; Katharine Wellman; Changbo Zhu; Eve Galimany; Gary H. Wikfors; Camille Saurel; Robin Landeck Miller; James Wands; et al. (Estuaries and Coasts, 2020)
Eutrophication is a challenge to coastal waters around the globe. In many places, nutrient reductions from land-based sources have not been sufficient to achieve desired water quality improvements. Bivalve shellfish have shown promise as an in-water strategy to complement land-based nutrient management. A local-scale production model was used to estimate oyster ( Crassostrea virginica ) harvest and bioextraction of nitrogen (N) in Great Bay Piscataqua River Estuary (GBP), New Hampshire, USA, because a system-scale ecological model was not available. Farm-scale N removal results (0.072 metric tons acre −1 year −1 ) were up-scaled to provide a system-wide removal estimate for current (0.61 metric tons year −1 ), and potential removal (2.35 metric tons year −1 ) at maximum possible expansion of licensed aquaculture areas. Restored reef N removal was included to provide a more complete picture. Nitrogen removal through reef sequestration was ~ 3 times that of aquaculture. Estimated reef-associated denitrification, based on previously reported rates, removed 0.19 metric tons N year −1 . When all oyster processes (aquaculture and reefs) were included, N removal was 0.33% and 0.54% of incoming N for current and expanded acres, respectively. An avoided cost approach, with wastewater treatment as the alternative management measure, was used to estimate the value of the N removed. The maximum economic value for aquaculture-based removal was $105,000 and $405,000 for current and expanded oyster areas, respectively. Combined aquaculture and reef restoration is suggested to maximize N reduction capacity while limiting use conflicts. Comparison of removal based on per oyster N content suggests much lower removal rates than model results, but model harvest estimates are similar to reported harvest. Though results are specific to GBP, the approach is transferable to estuaries that support bivalve aquaculture but do not have complex system-scale hydrodynamic or ecological models.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Valuing non-market economic impacts from natural hazards - Abbie A. Rogers; Fiona L. Dempster; Jacob I. Hawkins; Robert J. Johnston; Peter C. Boxall; John Rolfe; Marit E. Kragt; Michael P. Burton; David J. Pannell (Natural Hazards, 2019)

The PNPLA3 I148M variant promotes lipid-induced hepatocyte secretion of CXC chemokines establishing a tumorigenic milieu - Hans Dieter Nischalke; Philipp Lutz; Eva Bartok; Benjamin Krämer; Bettina Langhans; Regina Frizler; Thomas Berg; Jochen Hampe; Stephan Buch; Christian Datz; Felix Stickel; Gunther Hartmann; et al. (Journal of Molecular Medicine, 2019)

SEASTAR: A Mission to Study Ocean Submesoscale Dynamics and Small-Scale Atmosphere-Ocean Processes in Coastal, Shelf and Polar Seas - Christine Gommenginger; Bertrand Chapron; Andy Hogg; Christian Buckingham; Baylor Fox-Kemper; Leif Eriksson; Francois Soulat; Clément Ubelmann; Francisco Ocampo-Torres; Bruno Buongiorno Nardelli; David Griffin; Paco Lopez-Dekker; et al. (Frontiers in Marine Science, 2019)

Preconditioning in the Rhesus Macaque Induces a Proteomic Signature Following Cerebral Ischemia that Is Associated with Neuroprotection - Susan L. Stevens; Tao Liu; Frances Rena Bahjat; Vladislav A. Petyuk; Athena A. Schepmoes; Ryan L. Sontag; Marina A. Gritsenko; Chaochao Wu; Sheng Wang; Anil K. Shukla; Jon M. Jacobs; Richard D. Smith; et al. (Translational Stroke Research, 2019)

Effect of external compression on femoral retrograde shear and microvascular oxygenation in exercise trained and recreationally active young men - Patricia Pagan Lassalle; Adam J. Palamar; Jacob P. DeBlois; Wesley K. Lefferts; Kevin S. Heffernan (European Journal of Applied Physiology, 2019)

Improving the performance of ecological indices by balancing reference site quality and representativeness - Kai Chen; John R. Olson; Jacob J. Vander Laan; Ryan A. Hill; Beixin Wang; Charles P. Hawkins (Hydrobiologia, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

A reply to the comment by Karlsson et al. - Eero Asmala; Jacob Carstensen; Daniel J. Conley; Caroline P. Slomp; Johanna Stadmark; Maren Voss (Limnology and Oceanography, 2019)

Conducting and interpreting fish telemetry studies: considerations for researchers and resource managers - Jacob W. Brownscombe; Elodie J. I. Lédée; Graham D. Raby; Daniel P. Struthers; Lee F. G. Gutowsky; Vivian M. Nguyen; Nathan Young; Michael J. W. Stokesbury; Christopher M. Holbrook; Travis O. Brenden; Christopher S. Vandergoot; Karen J. Murchie; et al. (Reviews in Fish Biology and Fisheries, 2019)

The successful uptake and sustainability of rapid infectious disease and antimicrobial resistance point-of-care testing requires a complex ‘mix-and-match’ implementation package - John P. Hays; Konstantinos Mitsakakis; Saturnino Luz; Alex van Belkum; Karsten Becker; Ann van den Bruel; Stephan Harbarth; John H. Rex; Gunnar Skov Simonsen; Guido Werner; Valentina Di Gregori; Gerd Lüdke; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Thermophysical properties and phase diagrams in the system MgO–SiO2–FeO at upper mantle and transition zone conditions derived from a multiple-Einstein method - Michael H. G. Jacobs; Rainer Schmid-Fetzer; Arie P. van den Berg (Physics and Chemistry of Minerals, 2019)

Climate change in context: putting people first in the Arctic - Henry P. Huntington; Mark Carey; Charlene Apok; Bruce C. Forbes; Shari Fox; Lene K. Holm; Aitalina Ivanova; Jacob Jaypoody; George Noongwook; Florian Stammler (Regional Environmental Change, 2019)

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

From Science to Evidence – How Biodiversity Indicators Can Be Used for Effective Marine Conservation Policy and Management - Abigail McQuatters-Gollop; Ian Mitchell; Cristina Vina-Herbon; Jacob Bedford; Prue F. E. Addison; Christopher P. Lynam; P. N. Geetha; Estee Ann Vermeulan; Kaylee Smit; Daniel T. I. Bayley; Elisabeth Morris-Webb; Holly J. Niner; et al. (Frontiers in Marine Science, 2019)

Environmental drivers of habitat use by a marine fish on a heterogeneous and dynamic reef flat - Jacob W. Brownscombe; Lucas P. Griffin; Tyler O. Gagne; Christopher R. Haak; Steven J. Cooke; John T. Finn; Andy J. Danylchuk (Marine Biology, 2019)

A comparison of juvenile bonefish diets in Eleuthera, The Bahamas, and Florida, U.S. - Lucas P. Griffin; Christopher R. Haak; Jacob W. Brownscombe; Curtice R. Griffin; Andy J. Danylchuk (Environmental Biology of Fishes, 2019)

Less is more: lemurs (Eulemur spp.) may benefit from loss of trichromatic vision - Rachel L. Jacobs; Carrie C. Veilleux; Edward E. Louis; James P. Herrera; Chihiro Hiramatsu; David C. Frankel; Mitchell T. Irwin; Amanda D. Melin; Brenda J. Bradley (Behavioral Ecology and Sociobiology, 2019)

Modeling Human Volunteers in Multidirectional, Uni-axial Sled Tests Using a Finite Element Human Body Model - James P. Gaewsky; Derek A. Jones; Xin Ye; Bharath Koya; Kyle P. McNamara; F. Scott Gayzik; Ashley A. Weaver; Jacob B. Putnam; Jeffrey T. Somers; Joel D. Stitzel (Annals of Biomedical Engineering, 2019)

Biomechanical parameters of the elbow stretch reflex in chronic hemiparetic stroke - Jacob G. McPherson; Arno H. A. Stienen; Brian D. Schmit; Julius P. A. Dewald (Experimental Brain Research, 2019)

Tundra Trait Team: A database of plant traits spanning the tundra biome - Anne D. Bjorkman; Isla H. Myers‐Smith; Sarah C. Elmendorf; Signe Normand; Haydn J. D. Thomas; Juha M. Alatalo; Heather Alexander; Alba Anadon‐Rosell; Sandra Angers‐Blondin; Yang Bai; Gaurav Baruah; Mariska te Beest; et al. (Global Ecology and Biogeography, 2018)
Motivation The Tundra Trait Team (TTT) database includes field‐based measurements of key traits related to plant form and function at multiple sites across the tundra biome. This dataset can be used to address theoretical questions about plant strategy and trade‐offs, trait–environment relationships and environmental filtering, and trait variation across spatial scales, to validate satellite data, and to inform Earth system model parameters. Main types of variable contained The database contains 91,970 measurements of 18 plant traits. The most frequently measured traits (> 1,000 observations each) include plant height, leaf area, specific leaf area, leaf fresh and dry mass, leaf dry matter content, leaf nitrogen, carbon and phosphorus content, leaf C:N and N:P, seed mass, and stem specific density. Spatial location and grain Measurements were collected in tundra habitats in both the Northern and Southern Hemispheres, including Arctic sites in Alaska, Canada, Greenland, Fennoscandia and Siberia, alpine sites in the European Alps, Colorado Rockies, Caucasus, Ural Mountains, Pyrenees, Australian Alps, and Central Otago Mountains (New Zealand), and sub‐Antarctic Marion Island. More than 99% of observations are georeferenced. Time period and grain All data were collected between 1964 and 2018. A small number of sites have repeated trait measurements at two or more time periods. Major taxa and level of measurement Trait measurements were made on 978 terrestrial vascular plant species growing in tundra habitats. Most observations are on individuals (86%), while the remainder represent plot or site means or maximums per species. Software format csv file and GitHub repository with data cleaning scripts in R; contribution to TRY plant trait database ( www.try-db.org ) to be included in the next version release.

ColorEM: analytical electron microscopy for element-guided identification and imaging of the building blocks of life - Nicole M. Pirozzi; Jacob P. Hoogenboom; Ben N. G. Giepmans (Histochemistry and Cell Biology, 2018)

Assessment of the indirect impact of wildfire (severity) on actual evapotranspiration in eucalyptus forest based on the surface energy balance estimated from remote-sensing techniques - Melanie Häusler; João P. Nunes; Paula Soares; Juan M. Sánchez; João M. N. Silva; Thorsten Warneke; Jan Jacob Keizer; José M. C. Pereira (International Journal of Remote Sensing, 2018)

Antibiotic resistance and molecular characteristics of Staphylococcus aureus isolated from backyard-raised pigs and pig workers - Asabe Halimat Momoh; Jacob K. P. Kwaga; Mohammed Bello; Anthony K. B. Sackey; Anders Rhod Larsen (Tropical Animal Health and Production, 2018)

Aortic stiffness, central pulse pressure and cognitive function following acute resistance exercise - Samuel Palmiere; Marcus Wade; Jacob P. DeBlois; Wesley K. Lefferts; Kevin S. Heffernan (European Journal of Applied Physiology, 2018)

Deep TMS of the insula using the H-coil modulates dopamine release: a crossover [11C] PHNO-PET pilot trial in healthy humans - Saima Malik; Mark Jacobs; Sang-Soo Cho; Isabelle Boileau; Daniel Blumberger; Markus Heilig; Alan Wilson; Zafiris J. Daskalakis; Antonio P. Strafella; Abraham Zangen; Bernard Le Foll (Brain Imaging and Behavior, 2018)

Isolation by marine barriers and climate explain areas of endemism in an island rodent - Thomas C. Giarla; Sean P. Maher; Anang S. Achmadi; Meagan K. Moore; Mark T. Swanson; Kevin C. Rowe; Jacob A. Esselstyn (Journal of Biogeography, 2018)
Aim The Indonesian island of Sulawesi is home to thousands of endemic terrestrial animal species. Phylogeographical studies of some of these taxa revealed concordant distribution patterns (areas of endemism; AoEs), suggestive of a shared evolutionary or ecological mechanism driving divergence among various terrestrial taxa. Generally, AoEs have been attributed to Pleistocene marine incursions, geological fault zones and Sulawesi's history as an archipelago. We test, for the first time, the hypothesis that population divergences are associated with unsuitable climate spaces at the boundaries between these areas. Location Sulawesi, Indonesia. Taxon Maxomys musschenbroekii , a common murid rodent endemic to Sulawesi. Methods We sequenced a mitochondrial gene, four nuclear protein‐coding genes and hundreds of ultraconserved elements from individuals sampled across the island, which we used to build intraspecific phylogenies and identify population structure. To test climate‐related hypotheses, we used multiple regression to assess the extent to which genetic distances, over‐land geographical distances, environmental distances (derived from ecological niche model resistance surfaces) and areas of endemism are correlated. Results In all three genetic datasets, we inferred phylogeographical structure that is geographically concordant with previously defined AoEs. Ecological niche models showed a similar geography of suitability across the island since the Last Glacial Maximum, with varying levels of unsuitable climate space between AoEs. Genetic distances were more strongly correlated with environmental distances than geographical distances and interspecific divergences arose just in the past 1.5 Myr. Main Conclusions Population divergences within M. musschenbroekii are consistent with AoE definitions from other taxa. Stable areas of unsuitable habitat near AoE boundaries probably supplemented marine incursions in generating population structure within M. musschenbroekii and other co‐distributed species.

The use of spatial management tools in rights‐based groundfish fisheries - Owen R. Liu; Kristin M. Kleisner; Sarah L. Smith; Jacob P. Kritzer (Fish and Fisheries, 2018)
The role of spatial management, including marine protected areas, in achieving fisheries outcomes alongside conservation goals is debated. In fisheries that fail to meet fishing mortality targets, closed areas are sometimes implemented to reduce fishing mortality. However, fisheries with stronger management, including rights‐based approaches that can address overcapacity and overfishing problems, often employ spatial management as well. Here, we compare the objectives, design, and performance of spatial management in nine temperate demersal fisheries in North America, Oceania, Europe, and Africa that employ rights‐based systems. Common objectives of spatial management included protecting habitat, juveniles, and spawners and reducing discards. Recovering age structure and creating scientific reference sites were less common objectives, despite being widely cited benefits of spatial management. Some fisheries adopted single closures to achieve single objectives, whereas others adopted diverse networks to achieve multiple objectives. Importantly, many spatial protections are implemented primarily through industry initiatives. Environmental change compromised the efficacy of spatial management in some cases, suggesting the need to design spatial management systems that are robust to changing ocean conditions. Fisheries with diverse and extensive spatial management systems have generally healthier fish stocks. Whether this implies that spatial management contributed substantially to fishery performance is unclear due to an absence of large‐scale, long‐term studies aimed at discerning different drivers of success. Although these targeted monitoring studies of closed areas are limited, such studies are necessary to help resolve the ongoing debate and to enable more purposeful design of spatial management for fisheries and conservation.

The perpetual state of emergency that sacrifices protected areas in a changing climate - Dirac Twidwell; Carissa L. Wonkka; Christine H. Bielski; Craig R. Allen; David G. Angeler; Jacob Drozda; Ahjond S. Garmestani; Julia Johnson; Larkin A. Powell; Caleb P. Roberts (Conservation Biology, 2018)
A modern challenge for conservation biology is to assess the consequences of policies that adhere to assumptions of stationarity (e.g., historic norms) in an era of global environmental change. Such policies may result in unexpected and surprising levels of mitigation given future climate‐change trajectories, especially as agriculture looks to protected areas to buffer against production losses during periods of environmental extremes. We assessed the potential impact of climate‐change scenarios on the rates at which grasslands enrolled in the Conservation Reserve Program (CRP) are authorized for emergency harvesting (i.e., biomass removal) for agricultural use, which can occur when precipitation for the previous 4 months is below 40% of the normal or historical mean precipitation for that 4‐month period. We developed and analyzed scenarios under the condition that policy will continue to operate under assumptions of stationarity, thereby authorizing emergency biomass harvesting solely as a function of precipitation departure from historic norms. Model projections showed the historical likelihood of authorizing emergency biomass harvesting in any given year in the northern Great Plains was 33.28% based on long‐term weather records. Emergency biomass harvesting became the norm (>50% of years) in the scenario that reflected continued increases in emissions and a decrease in growing‐season precipitation, and areas in the Great Plains with higher historical mean annual rainfall were disproportionately affected and were subject to a greater increase in emergency biomass removal. Emergency biomass harvesting decreased only in the scenario with rapid reductions in emissions. Our scenario‐impact analysis indicated that biomass from lands enrolled in the CRP would be used primarily as a buffer for agriculture in an era of climatic change unless policy guidelines are adapted or climate‐change projections significantly depart from the current consensus.

Dual‐guild herbivory disrupts predator‐prey interactions in the field - Carmen K. Blubaugh; Jacob S. Asplund; Sanford D. Eigenbrode; Matthew J. Morra; Christopher R. Philips; Inna E. Popova; John P. Reganold; William E. Snyder (Ecology, 2018)
Plant defenses often mediate whether competing chewing and sucking herbivores indirectly benefit or harm one another. Dual‐guild herbivory also can muddle plant signals used by specialist natural enemies to locate prey, further complicating the net impact of herbivore–herbivore interactions in naturally diverse settings. While dual‐guild herbivore communities are common in nature, consequences for top‐down processes are unclear, as chemically mediated tri‐trophic interactions are rarely evaluated in field environments. Combining observational and experimental approaches in the open field, we test a prediction that chewing herbivores interfere with top‐down suppression of phloem feeders on Brassica oleracea across broad landscapes. In a two‐year survey of 52 working farm sites, we found that parasitoid and aphid densities on broccoli plants positively correlated at farms where aphids and caterpillars rarely co‐occurred, but this relationship disappeared at farms where caterpillars commonly co‐occurred. In a follow‐up experiment, we compared single and dual‐guild herbivore communities at four local farm sites and found that caterpillars ( P. rapae ) caused a 30% reduction in aphid parasitism (primarily by Diaeretiella rapae ), and increased aphid colony ( Brevicoryne brassicae ) growth at some sites. Notably, in the absence of predators, caterpillars indirectly suppressed, rather than enhanced, aphid growth. Amid considerable ecological noise, our study reveals a pattern of apparent commensalism: herbivore–herbivore facilitation via relaxed top‐down suppression. This work suggests that enemy‐mediated apparent commensalism may override constraints to growth induced by competing herbivores in field environments, and emphasizes the value of placing chemically mediated interactions within their broader environmental and community contexts.

Inhibition of proinflammatory pathways by bioactive fraction of Tinospora cordifolia - Jenny Jacob; Bashi M. Babu; Mohind C. Mohan; A. P. Abhimannue; B. Prakash Kumar (Inflammopharmacology, 2018)

Guillain-Barré syndrome following varicella-zoster virus infection - Badrul Islam; Zhahirul Islam; Corine H. GeurtsvanKessel; Israt Jahan; Hubert P. Endtz; Quazi D. Mohammad; Bart C. Jacobs (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

The proteasome and proteasome inhibitors in multiple myeloma - Sara Gandolfi; Jacob P. Laubach; Teru Hideshima; Dharminder Chauhan; Kenneth C. Anderson; Paul G. Richardson (Cancer and Metastasis Reviews, 2017)

Organic macromolecules in shells of Arctica islandica: comparison with nacroprismatic bivalve shells - Oluwatoosin B. A. Agbaje; Denise E. Thomas; Bernie V. Mclnerney; Mark P. Molloy; Dorrit E. Jacob (Marine Biology, 2017)

A risk categorisation and analysis of the geographic and temporal dynamics of the European import of plants for planting - René Eschen; Jacob C. Douma; Jean-Claude Grégoire; François Mayer; Ludovic Rigaux; Roel P. J. Potting (Biological Invasions, 2017)

Efficiency of the coastal filter: Nitrogen and phosphorus removal in the Baltic Sea - Eero Asmala; Jacob Carstensen; Daniel J. Conley; Caroline P. Slomp; Johanna Stadmark; Maren Voss (Limnology and Oceanography, 2017)
An important function of coastal ecosystems is the reduction of the nutrient flux from land to the open sea, the coastal filter. In this study, we focused on the two most important coastal biogeochemical processes that remove nitrogen and phosphorus permanently: denitrification and phosphorus burial. We compiled removal rates from coastal systems around the Baltic Sea and analyzed their spatial variation and regulating environmental factors. These analyses were used to scale up denitrification and phosphorus burial rates for the entire Baltic Sea coastal zone. Denitrification rates ranged from non‐detectable to 12 mmol N m −2 d −1 , and correlated positively with both bottom water nitrate concentration and sediment organic carbon content. The rates exhibited a strong decreasing gradient from land to the open coast, which was likely driven by the availability of nitrate and labile organic carbon, but a high proportion of non‐cohesive sediments in the coastal zone decreased the denitrification efficiency relative to the open sea. Phosphorus burial rates varied from 0.21 g P m −2 yr −1 in open coastal systems to 2.28 g P m −2 yr −1 in estuaries. Our analysis suggests that archipelagos are important phosphorus traps and account for 45% of the coastal P removal, while covering only 17% of the coastal areas. High burial rates could partly be sustained by phosphorus import from the open Baltic Sea. We estimate that the coastal filter in the Baltic Sea removes 16% of nitrogen and 53% of phosphorus inputs from land.

Integrating Science-Based Co-management, Partnerships, Participatory Processes and Stewardship Incentives to Improve the Performance of Small-Scale Fisheries - Kendra A. Karr; Rod Fujita; Ramon Carcamo; Lawrence Epstein; James R. Foley; José A. Fraire-Cervantes; Mauro Gongora; Ollin T. Gonzalez-Cuellar; Pablo Granados-Dieseldorff; Julius Guirjen; Amy H. Weaver; Héctor Licón-González; et al. (Frontiers in Marine Science, 2017)

The coevolution of play and the cortico-cerebellar system in primates - Max Kerney; Jeroen B. Smaers; P. Thomas Schoenemann; Jacob C. Dunn (Primates, 2017)

Multi-scale methods predict invasion speeds in variable landscapes - Jacob P. Duncan; Rachel N. Rozum; James A. Powell; Karin M. Kettenring (Theoretical Ecology, 2017)

PLXNA3 Variant rs5945430 is Associated with Severe Clinical Course in Male Multiple Sclerosis Patients - Moaz Qureshi; Mohamed Hatem; Raed Alroughani; Sindhu P. Jacob; Rabeah Abbas Al-Temaimi (NeuroMolecular Medicine, 2017)

Effects of climate change on four New England groundfish species - Emily S. Klein; Sarah L. Smith; Jacob P. Kritzer (Reviews in Fish Biology and Fisheries, 2017)

Taxonomic clarification and re-description of two deep-sea roughies of genus Hoplostethus from the Indian Ocean - Jacob Vinu; M. P. Rajeeshkumar; K. S. Sumod; K. M. Meera; M. Hashim; V. N. Sanjeevan; M. Sudhakar (Marine Biodiversity, 2017)

Occurrence of a rare gigantic sized deep-sea cod Lepidion inosimae (Günther, 1887) in the Northwestern Indian Ocean - Jacob Vinu; M. P. Rajeesh Kumar; K. S. Sumod; K. P. Deepa; M. Hashim; V. N. Sanjeevan; M. Sudhakar (Marine Biodiversity, 2017)

Pan-European inter-laboratory studies on a panel of in vitro cytotoxicity and pro-inflammation assays for nanoparticles - Jean-Pascal Piret; Olesja M. Bondarenko; Matthew S. P. Boyles; Martin Himly; Ana R. Ribeiro; Federico Benetti; Caroline Smal; Braulio Lima; Annegret Potthoff; Monica Simion; Elise Dumortier; Paulo Emilio C. Leite; et al. (Archives of Toxicology, 2017)

The Andes Cordillera. Part IV: spatio‐temporal freshwater run‐off distribution to adjacent seas (1979–2014) - Sebastian H. Mernild; Glen E. Liston; Christopher Hiemstra; Andrew P. Beckerman; Jacob C. Yde; James McPhee (International Journal of Climatology, 2017)
The spatio‐temporal freshwater river run‐off pattern from individual basins, including their run‐off magnitude and change (1979/1980–2013/2014), was simulated for the Andes Cordillera west of the Continental Divide in an effort to understand run‐off variations and freshwater fluxes to adjacent fjords, Pacific Ocean, and Drake Passage. The modelling tool SnowModel/HydroFlow was applied to simulate river run‐off at 3‐h intervals to resolve the diurnal cycle and at 4‐km horizontal grid increments using atmospheric forcing from NASA Modern‐Era Retrospective Analysis for Research and Applications (MERRA) data sets. Simulated river run‐off hydrographs were verified against independent observed hydrographs. For the domain, 86% of the simulated run‐off originated from rain, 12% from snowmelt, and 2% from ice melt, whereas for Chile, the water‐source distribution was 69, 24, and 7%, respectively. Along the Andes Cordillera, the 35‐year mean basin outlet‐specific run‐off (L s −1 km −2 ) showed a characteristic regional hourglass shape pattern with highest run‐off in both Colombia and Ecuador and in Patagonia, and lowest run‐off in the Atacama Desert area. An Empirical Orthogonal Function analysis identified correlations between the spatio‐temporal pattern of run‐off and flux to the El Niño Southern Oscillation Index and to the Pacific Decadal Oscillation.

Hydrogen Peroxide Cycling in High-Temperature Acidic Geothermal Springs and Potential Implications for Oxidative Stress Response - Margaux M. Meslé; Jacob P. Beam; Zackary J. Jay; Brynna Bodle; Eric Bogenschutz; William P. Inskeep (Frontiers in Marine Science, 2017)

Development of site fidelity in the nocturnal amblypygid, Phrynus marginemaculatus - Jacob M. Graving; Verner P. Bingman; Eileen A. Hebets; Daniel D. Wiegmann (Journal of Comparative Physiology A, 2017)

Delving deeper: Metabolic processes in the metalimnion of stratified lakes - Darren P. Giling; Peter A. Staehr; Hans Peter Grossart; Mikkel René Andersen; Bertram Boehrer; Carmelo Escot; Fatih Evrendilek; Lluís Gómez‐Gener; Mark Honti; Ian D. Jones; Nusret Karakaya; Alo Laas; et al. (Limnology and Oceanography, 2017)
Many lakes exhibit seasonal stratification, during which they develop strong thermal and chemical gradients. An expansion of depth‐integrated monitoring programs has provided insight into the importance of organic carbon processing that occurs below the upper mixed layer. However, the chemical and physical drivers of metabolism and metabolic coupling remain unresolved, especially in the metalimnion. In this depth zone, sharp gradients in key resources such as light and temperature co‐occur with dynamic physical conditions that influence metabolic processes directly and simultaneously hamper the accurate tracing of biological activity. We evaluated the drivers of metalimnetic metabolism and its associated uncertainty across 10 stratified lakes in Europe and North America. We hypothesized that the metalimnion would contribute highly to whole‐lake functioning in clear oligotrophic lakes, and that metabolic rates would be highly variable in unstable polymictic lakes. Depth‐integrated rates of gross primary production (GPP) and ecosystem respiration (ER) were modelled from diel dissolved oxygen curves using a Bayesian approach. Metabolic estimates were more uncertain below the epilimnion, but uncertainty was not consistently related to lake morphology or mixing regime. Metalimnetic rates exhibited high day‐to‐day variability in all trophic states, with the metalimnetic contribution to daily whole‐lake GPP and ER ranging from 0% to 87% and

Content of testis-specific isoform of Na/K-ATPase (ATP1A4) is increased during bovine sperm capacitation through translation in mitochondrial ribosomes - Gayathri D. Rajamanickam; John P. Kastelic; Jacob C. Thundathil (Cell and Tissue Research, 2017)

Individual-level behavioral responses of immature green turtles to snorkeler disturbance - Lucas P. Griffin; Jacob W. Brownscombe; Tyler O. Gagné; Alexander D. M. Wilson; Steven J. Cooke; Andy J. Danylchuk (Oecologia, 2017)

Hepatocyte spheroids as a competent in vitro system for drug biotransformation studies: nevirapine as a bioactivation case study - Pedro F. Pinheiro; Sofia A. Pereira; Shrika G. Harjivan; Inês L. Martins; Aline T. Marinho; Madalena Cipriano; Cristina C. Jacob; Nuno G. Oliveira; Matilde F. Castro; M. Matilde Marques; Alexandra M. M. Antunes; Joana P. Miranda (Archives of Toxicology, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Straddling the divide: invasive aquatic species in Illinois and movement between the Great Lakes and Mississippi basins - Abigail I. Jacobs; Reuben P. Keller (Biological Invasions, 2017)

Phase diagrams, thermodynamic properties and sound velocities derived from a multiple Einstein method using vibrational densities of states: an application to MgO–SiO2 - Michael H. G. Jacobs; Rainer Schmid-Fetzer; Arie P. van den Berg (Physics and Chemistry of Minerals, 2017)

CO and NO bind to Fe(II) DiGeorge critical region 8 heme but do not restore primary microRNA processing activity - Judy P. Hines; Aaron T. Smith; Jose P. Jacob; Gudrun S. Lukat-Rodgers; Ian Barr; Kenton R. Rodgers; Feng Guo; Judith N. Burstyn (JBIC Journal of Biological Inorganic Chemistry, 2016)

Multi-generational evaluation of genetic diversity and parentage in captive southern pygmy perch (Nannoperca australis) - Catherine R. M. Attard; Chris J. Brauer; Jacob D. Van Zoelen; Minami Sasaki; Michael P. Hammer; Leslie Morrison; James O. Harris; Luciana M. Möller; Luciano B. Beheregaray (Conservation Genetics, 2016)

Three new records of rare deep-sea Anglerfishes (Lophiiformes: Ceratioidei) from the Northern Indian Ocean - Rajeeshkumar M. P.; Vinu Jacob; Sumod K. S.; Sanjeevan V. N.; Hashim M.; Sudhakar M. (Marine Biodiversity, 2016)

The distribution, diversity and function of predominant Thermoproteales in high‐temperature environments of Yellowstone National Park - Zackary J. Jay; Jacob P. Beam; Mark A. Kozubal; Ryan deM. Jennings; Douglas B. Rusch; William P. Inskeep (Environmental Microbiology, 2016)
Summary High‐temperature environments (> 70°C) contain diverse and abundant members of the crenarchaeal order Thermoproteales. However, a comprehensive study of the distribution and function of diverse members of this group across different habitat types has not been conducted. Consequently, the goals of this study were to determine the distribution of different Thermoproteales genera across geochemically distinct geothermal habitats of Yellowstone National Park, and to identify key functional attributes of major genera that correlate with environmental parameters. Curated sequence assemblies belonging to five genera were characterized in replicate samples of 11 high‐temperature communities ranging in pH from 3 to 9. Thermocladium , Vulcanisaeta and Caldivirga spp. were the primary Thermoproteales populations present in low pH (pH Thermoproteus populations were found in mildly‐acidic (pH 5–6) sulfur sediments, and Pyrobaculum populations were confined to higher pH (pH > 6) sulfur sediments and/or filamentous ‘streamer’ communities. Metabolic reconstruction and comparative genomics among assemblies show that these populations are primarily chemoorganotrophs that utilize different electron acceptors depending on geochemical conditions. The presence of potential CO 2 fixation pathways in some Thermoproteales populations appears to be linked with NiFe hydrogenases, which combined with high levels of H 2 in many sulfidic systems, may provide the energy required to fix inorganic C.

Large herbivores promote habitat specialization and beta diversity of African savanna trees - Robert M. Pringle; Kirsten M. Prior; Todd M. Palmer; Truman P. Young; Jacob R. Goheen (Ecology, 2016)
Edaphic variation in plant community composition is widespread, yet its underlying mechanisms are rarely understood and often assumed to be physiological. In East African savannas, Acacia tree species segregate sharply across soils of differing parent material: the ant‐defended whistling thorn, A. drepanolobium ( ACDR ), is monodominant on cracking clay vertisols that are nutrient rich but physically stressful, whereas poorly defended species such as A. brevispica ( ACBR ) dominate on nutrient‐poor but otherwise less‐stressful sandy loams. Using a series of field experiments, we show that large‐mammal herbivory interacts with soil properties to maintain this pattern. In the absence of large herbivores, transplanted saplings of both species established on both soil types. Browsers strongly suppressed survival and growth of ACDR saplings on sandy soil, where resource limitation constrained defensive investment. On clay soil, ACBR saplings established regardless of herbivory regime, but elephants prevented recruitment to maturity, apparently because trees could not tolerate the combination of biotic and abiotic stressors. Hence, each tree species was filtered out of one habitat by browsing in conjunction with different edaphic factors and at different ontogenetic stages. Browser abundance was greater on sandy soil, where trees were less defended, consistent with predicted feedbacks between plant community assembly and herbivore distributions. By exploring two inversely related axes of soil “quality” (abiotic stress and nutrient content), our study extends the range of mechanisms by which herbivores are known to promote edaphic specialization, illustrates how the high cost of a protection mutualism can constrain the realized niche of host trees, and shows that large‐scale properties of savanna ecosystems are shaped by species interactions in cryptic ways that mimic simple abiotic determinism. These results suggest that ongoing declines in large‐herbivore populations may relax spatial heterogeneity in plant assemblages and reduce the beta diversity of communities.

Bridging the Gap between Policy and Science in Assessing the Health Status of Marine Ecosystems - Angel Borja; Michael Elliott; Paul V. R. Snelgrove; Melanie C. Austen; Torsten Berg; Sabine Cochrane; Jacob Carstensen; Roberto Danovaro; Simon Greenstreet; Anna-Stiina Heiskanen; Christopher P. Lynam; Marianna Mea; et al. (Frontiers in Marine Science, 2016)

Erratum to: Environmental Enrichment Mitigates Detrimental Cognitive Effects of Ketogenic Diet in Weanling Rats - John M. Scichilone; Kalyan Yarraguntla; Ana Charalambides; Jacob P. Harney; David Butler (Journal of Molecular Neuroscience, 2016)

Environmental Enrichment Mitigates Detrimental Cognitive Effects of Ketogenic Diet in Weanling Rats - John M. Scichilone; Kalyan Yarraguntla; Ana Charalambides; Jacob P. Harney; David Butler (Journal of Molecular Neuroscience, 2016)

Do age and sex impact on the absolute cell numbers of human brain regions? - Ana V. Oliveira-Pinto; Carlos H. Andrade-Moraes; Lays M. Oliveira; Danielle R. Parente-Bruno; Raquel M. Santos; Renan A. Coutinho; Ana T. L. Alho; Renata E. P. Leite; Claudia K. Suemoto; Lea T. Grinberg; Carlos A. Pasqualucci; Wilson Jacob-Filho; et al. (Brain Structure and Function, 2016)

First description of the neuro‐anatomy of a larval coral reef fish Amphiprion ocellaris - H. Jacob; M. Metian; R. M. Brooker; E. Duran; N. Nakamura; N. Roux; P. Masanet; O. Soulat; D. Lecchini (Journal of Fish Biology, 2016)
The present study described the neuro‐anatomy of a larval coral reef fish Amphiprion ocellaris and hypothesized that morphological changes during the transition from the oceanic environment to a reef environment ( i.e. recruitment) have the potential to be driven by changes to environmental conditions and associated changes to cognitive requirements. Quantitative comparisons were made of the relative development of three specific brain areas (telencephalon, mesencephalon and cerebellum) between 6 days post‐hatch (dph) larvae (oceanic phase) and 11 dph (at reef recruitment). The results showed that 6 dph larvae had at least two larger structures (telencephalon and mesencephalon) than 11 dph larvae, while the size of cerebellum remained identical. These results suggest that the structure and organization of the brain may reflect the cognitive demands at every stage of development. This study initiates analysis of the relationship between behavioural ecology and neuroscience in coral reef fishes.

Infection risk decreases with increasing mismatch in host and pathogen environmental tolerances - A. Justin Nowakowski; Steven M. Whitfield; Evan A. Eskew; Michelle E. Thompson; Jonathan P. Rose; Benjamin L. Caraballo; Jacob L. Kerby; Maureen A. Donnelly; Brian D. Todd (Ecology Letters, 2016)
The fungal pathogen Batrachochytrium dendrobatidis ( Bd ) has caused the greatest known wildlife pandemic, infecting over 500 amphibian species. It remains unclear why some host species decline from disease‐related mortality whereas others persist. We introduce a conceptual model that predicts that infection risk in ectotherms will decrease as the difference between host and pathogen environmental tolerances (i.e. tolerance mismatch) increases. We test this prediction using both local‐scale data from Costa Rica and global analyses of over 11 000 Bd infection assays. We find that infection prevalence decreases with increasing thermal tolerance mismatch and with increasing host tolerance of habitat modification. The relationship between environmental tolerance mismatches and Bd infection prevalence is generalisable across multiple amphibian families and spatial scales, and the magnitude of the tolerance mismatch effect depends on environmental context. These findings may help explain patterns of amphibian declines driven by a global wildlife pandemic.

Chronic methamphetamine exposure prior to middle cerebral artery occlusion increases infarct volume and worsens cognitive injury in Male mice - Damian G. Zuloaga; Jianming Wang; Sydney Weber; Gregory P. Mark; Stephanie J. Murphy; Jacob Raber (Metabolic Brain Disease, 2016)

An Evaluation of Harvest Control Methods for Fishery Management - Owen R. Liu; Lennon R. Thomas; Michaela Clemence; Rod Fujita; Jacob P. Kritzer; Gavin McDonald; Cody Szuwalski (Reviews in Fisheries Science & Aquaculture, 2016)

Effect of speed endurance and strength training on performance, running economy and muscular adaptations in endurance-trained runners - Jacob Vorup; Jonas Tybirk; Thomas P. Gunnarsson; Tanja Ravnholt; Sarah Dalsgaard; Jens Bangsbo (European Journal of Applied Physiology, 2016)

Adaptive and neutral genetic differentiation among Scottish and endangered Irish red grouse (Lagopus lagopus scotica) - Yvonne Meyer-Lucht; Kevin P. Mulder; Marianne C. James; Barry J. McMahon; Kieran Buckley; Stuart B. Piertney; Jacob Höglund (Conservation Genetics, 2016)

Extreme air–sea interaction over the North Atlantic subpolar gyre during the winter of 2013–2014 and its sub-surface legacy - Jeremy P. Grist; Simon A. Josey; Zoe L. Jacobs; Robert Marsh; Bablu Sinha; Erik Van Sebille (Climate Dynamics, 2016)

Acanthocephalan Parasites (Acanthogyrus sp.) of Nile Tilapia (Oreochromis niloticus) as Biosink of Lead (Pb) Contamination in a Philippine Freshwater Lake - Vachel Gay V. Paller; Dan Jacob B. Resurreccion; Christian Paul P. de la Cruz; Modesto Z. Bandal (Bulletin of Environmental Contamination and Toxicology, 2016)

First record of deep-sea gigantic pycnogonid Colossendeis colossea Wilson, 1881 from the Western Indian Ocean - Jacob Vinu; M. P. Rajeesh Kumar; K. S. Sumod; K. P. Deepa; M. Hashim; V. N. Sanjeevan; M. Sudhakar (Marine Biodiversity, 2016)

Role of lutoid membrane transport and protein synthesis in the regeneration mechanism of latex in different Hevea clones - S. Sreelatha; Sheela P. Simon; V. C. Mercykutty; Kavitha K. Mydin; R. Krishnakumar; K. Annamalainathan; James Jacob (Acta Physiologiae Plantarum, 2016)

Recurrent candidiasis and early-onset gastric cancer in a patient with a genetically defined partial MYD88 defect - Ingrid P. Vogelaar; Marjolijn J. L. Ligtenberg; Rachel S. van der Post; Richarda M. de Voer; C. Marleen Kets; Trees J. G. Jansen; Liesbeth Jacobs; Gerty Schreibelt; I. Jolanda M. de Vries; Mihai G. Netea; Nicoline Hoogerbrugge (Familial Cancer, 2016)

Evolution of GOUNDRY , a cryptic subgroup of Anopheles gambiae s.l ., and its impact on susceptibility to Plasmodium infection - Jacob E. Crawford; Michelle M. Riehle; Kyriacos Markianos; Emmanuel Bischoff; Wamdaogo M. Guelbeogo; Awa Gneme; N'Fale Sagnon; Kenneth D. Vernick; Rasmus Nielsen; Brian P. Lazzaro (Molecular Ecology, 2016)
The recent discovery of a previously unknown genetic subgroup of Anopheles gambiae sensu lato underscores our incomplete understanding of complexities of vector population demographics in Anopheles . This subgroup, named GOUNDRY , does not rest indoors as adults and is highly susceptible to Plasmodium infection in the laboratory. Initial description of GOUNDRY suggested it differed from other known Anopheles taxa in surprising and sometimes contradictory ways, raising a number of questions about its age, population size and relationship to known subgroups. To address these questions, we sequenced the complete genomes of 12 wild‐caught GOUNDRY specimens and compared these genomes to a panel of Anopheles genomes. We show that GOUNDRY is most closely related to Anopheles coluzzii , and the timing of cladogenesis is not recent, substantially predating the advent of agriculture. We find a large region of the X chromosome that has swept to fixation in GOUNDRY within the last 100 years, which may be an inversion that serves as a partial barrier to contemporary gene flow. Interestingly, we show that GOUNDRY has a history of inbreeding that is significantly associated with susceptibility to Plasmodium infection in the laboratory. Our results illuminate the genomic evolution of one of probably several cryptic, ecologically specialized subgroups of Anopheles and provide a potent example of how vector population dynamics may complicate efforts to control or eradicate malaria.

Regional age differences in gray matter diffusivity among healthy older adults - Lauren E. Salminen; Thomas E. Conturo; David H. Laidlaw; Ryan P. Cabeen; Erbil Akbudak; Elizabeth M. Lane; Jodi M. Heaps; Jacob D. Bolzenius; Laurie M. Baker; Sarah Cooley; Staci Scott; Lee M. Cagle; et al. (Brain Imaging and Behavior, 2016)

Deformity, Erosion, Lesion, and Tumor Occurrence, Fluctuating Asymmetry, and Population Parameters for Bluntnose Minnow (Pimephales notatus) as Indicators of Recovering Water Quality in a Great Lakes Area of Concern, USA - Thomas P. Simon; Jacob L. Burskey (Archives of Environmental Contamination and Toxicology, 2016)

Looking into the past – the reaction of three grouse species to climate change over the last million years using whole genome sequences - Radoslav Kozma; Páll Melsted; Kristinn P. Magnússon; Jacob Höglund (Molecular Ecology, 2016)
Tracking past population fluctuations can give insight into current levels of genetic variation present within species. Analysing population dynamics over larger timescales can be aligned to known climatic changes to determine the response of species to varying environments. Here, we applied the Pairwise Sequentially Markovian Coalescent ( psmc ) model to infer past population dynamics of three widespread grouse species; black grouse, willow grouse and rock ptarmigan. This allowed the tracking of the effective population size ( N e ) of all three species beyond 1 Mya, revealing that (i) early Pleistocene cooling (~2.5 Mya) caused an increase in the willow grouse and rock ptarmigan populations, (ii) the mid‐Brunhes event (~430 kya) and following climatic oscillations decreased the N e of willow grouse and rock ptarmigan, but increased the N e of black grouse and (iii) all three species reacted differently to the last glacial maximum ( LGM ) – black grouse increased prior to it, rock ptarmigan experienced a severe bottleneck and willow grouse was maintained at large population size. We postulate that the varying psmc signal throughout the LGM depicts only the local history of the species. Nevertheless, the large population fluctuations in willow grouse and rock ptarmigan indicate that both species are opportunistic breeders while black grouse tracks the climatic changes more slowly and is maintained at lower N e . Our results highlight the usefulness of the psmc approach in investigating species’ reaction to climate change in the deep past, but also that caution should be taken in drawing general conclusions about the recent past.

The effect of personal medical history and family history of cancer on the uptake of risk-reducing salpingo-oophorectomy - Jessica E. van der Aa; Jacob P. Hoogendam; Els S. F. Butter; Margreet G. E. M. Ausems; René H. M. Verheijen; Ronald P. Zweemer (Familial Cancer, 2015)

Physiological stress and reflex impairment of recreationally angled bonefish in Puerto Rico - Jacob W. Brownscombe; Lucas P. Griffin; Tyler Gagne; Christopher R. Haak; Steven J. Cooke; Andy J. Danylchuk (Environmental Biology of Fishes, 2015)

Temporal genetic analysis of the endangered tidewater goby: extinction–colonization dynamics or drift in isolation? - Andrew P. Kinziger; Michael Hellmair; W. Tyler McCraney; David K. Jacobs; Greg Goldsmith (Molecular Ecology, 2015)
Extinction and colonization dynamics are critical to understanding the evolution and conservation of metapopulations. However, traditional field studies of extinction–colonization are potentially fraught with detection bias and have rarely been validated. Here, we provide a comparison of molecular and field‐based approaches for assessment of the extinction–colonization dynamics of tidewater goby ( Eucyclogobius newberryi ) in northern California. Our analysis of temporal genetic variation across 14 northern California tidewater goby populations failed to recover genetic change expected with extinction–colonization cycles. Similarly, analysis of site occupancy data from field studies (94 sites) indicated that extinction and colonization are very infrequent for our study populations. Comparison of the approaches indicated field data were subject to imperfect detection, and falsely implied extinction–colonization cycles in several instances. For northern California populations of tidewater goby, we interpret the strong genetic differentiation between populations and high degree of within‐site temporal stability as consistent with a model of drift in the absence of migration, at least over the past 20–30 years. Our findings show that tidewater goby exhibit different population structures across their geographic range (extinction–colonization dynamics in the south vs. drift in isolation in the north). For northern populations, natural dispersal is too infrequent to be considered a viable approach for recolonizing extirpated populations, suggesting that species recovery will likely depend on artificial translocation in this region. More broadly, this work illustrates that temporal genetic analysis can be used in combination with field data to strengthen inference of extinction–colonization dynamics or as a stand‐alone tool when field data are lacking.

Fostering effective international collaboration for marine science in small island states - Edward J. Hind; Steven M. Alexander; Stephanie J. Green; Jacob P. Kritzer; Michael J. Sweet; Ayana Elizabeth Johnson; Fabian P. Amargós; Nicola S. Smith; Angelie M. Peterson (Frontiers in Marine Science, 2015)

Effect of moderate exercise-induced heat stress on carotid wave intensity - Denise L. Smith; Jacob P. DeBlois; Margaret Wharton; Patricia C. Fehling; Sushant M. Ranadive (European Journal of Applied Physiology, 2015)

Regional climate modelling in CLARIS-LPB: a concerted approach towards twentyfirst century projections of regional temperature and precipitation over South America - E. Sánchez; S. Solman; A. R. C. Remedio; H. Berbery; P. Samuelsson; R. P. Da Rocha; C. Mourão; L. Li; J. Marengo; M. de Castro; D. Jacob (Climate Dynamics, 2015)

Staphylococcus aureus nasal carriage among healthcare workers in Kisangani, the Democratic Republic of the Congo - H. De Boeck; S. Vandendriessche; M. Hallin; B. Batoko; J.-P. Alworonga; B. Mapendo; C. Van Geet; N. Dauly; O. Denis; J. Jacobs (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Future habitat loss and extinctions driven by land‐use change in biodiversity hotspots under four scenarios of climate‐change mitigation - Samuel M. Jantz; Brian Barker; Thomas M. Brooks; Louise P. Chini; Qiongyu Huang; Rachel M. Moore; Jacob Noel; George C. Hurtt (Conservation Biology, 2015)
Numerous species have been pushed into extinction as an increasing portion of Earth's land surface has been appropriated for human enterprise. In the future, global biodiversity will be affected by both climate change and land‐use change, the latter of which is currently the primary driver of species extinctions. How societies address climate change will critically affect biodiversity because climate‐change mitigation policies will reduce direct climate‐change impacts; however, these policies will influence land‐use decisions, which could have negative impacts on habitat for a substantial number of species. We assessed the potential impact future climate policy could have on the loss of habitable area in biodiversity hotspots due to associated land‐use changes. We estimated past extinctions from historical land‐use changes (1500–2005) based on the global gridded land‐use data used for the Intergovernmental Panel on Climate Change Fifth Assessment Report and habitat extent and species data for each hotspot. We then estimated potential extinctions due to future land‐use changes under alternative climate‐change scenarios (2005–2100). Future land‐use changes are projected to reduce natural vegetative cover by 26‐58% in the hotspots. As a consequence, the number of additional species extinctions, relative to those already incurred between 1500 and 2005, due to land‐use change by 2100 across all hotspots ranged from about 220 to 21000 (0.2% to 16%), depending on the climate‐change mitigation scenario and biological factors such as the slope of the species–area relationship and the contribution of wood harvest to extinctions. These estimates of potential future extinctions were driven by land‐use change only and likely would have been higher if the direct effects of climate change had been considered. Future extinctions could potentially be reduced by incorporating habitat preservation into scenario development to reduce projected future land‐use changes in hotspots or by lessening the impact of future land‐use activities on biodiversity within hotspots.

Prevalence and distribution of beta-lactamase coding genes in third-generation cephalosporin-resistant Enterobacteriaceae from bloodstream infections in Cambodia - E. R. Vlieghe; T.-D. Huang; T. Phe; P. Bogaerts; C. Berhin; B. De Smet; W. E. Peetermans; J. A. Jacobs; Y. Glupczynski (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Individual differences in predators but not producers mediate the magnitude of a trophic cascade - Carl N. Keiser; Jacob B. Slyder; Walter P. Carson; Jonathan N. Pruitt (Arthropod-Plant Interactions, 2015)

In Vitro Susceptibility of Brazilian Pythium insidiosum Isolates to Essential Oils of Some Lamiaceae Family Species - A. O. S. Fonseca; D. I. B. Pereira; R. G. Jacob; F. S. Maia Filho; D. H. Oliveira; B. P. Maroneze; J. S. S. Valente; L. G. Osório; S. A. Botton; M. C. A. Meireles (Mycopathologia, 2015)

Enhanced science–stakeholder communication to improve ecosystem model performances for climate change impact assessments - Anna Maria Jönsson; Olle Anderbrant; Jennie Holmér; Jacob Johansson; Guy Schurgers; Glenn P. Svensson; Henrik G. Smith (Ambio, 2015)

Environmental disturbance can increase beta diversity of stream macroinvertebrate assemblages - Charles P. Hawkins; Heikki Mykrä; Jari Oksanen; Jacob J. Vander Laan (Global Ecology and Biogeography, 2015)
Aim Freshwater biodiversity is declining world‐wide as a result of human‐caused degradation of freshwater ecosystems. Declines in species richness are well documented for many taxonomic groups, but less is known about how and why species composition and beta diversity (β) change in response to environmental degradation in freshwater environments. Location The Mid‐ A tlantic Highlands region of the USA (36–42° N , 74–82° E ) and F inland in northern E urope (60–68° N , 20–32° E ). Methods We used null models, occupancy analyses, ordinations and multitaxon niche models to assess how β of stream macroinvertebrate assemblages in two biogeographically distinct regions responded to environmental alteration and what mechanisms were most likely to have caused the observed differences in β. Results Macroinvertebrate assemblages at anthropogenically disturbed sites were significantly more dissimilar from one another than were reference sites, a result contrary to those reported in several other studies. In this study, anthropogenic disturbances decreased the regional prevalence of most common taxa and increased the prevalence of several less common taxa. These differences in taxon occupancies and β between the reference condition and disturbed streams are unlikely to be the result of a single mechanism, although environmental filtering was probably of primary importance. Main conclusions The effects of anthropogenic disturbance on assemblage composition can be variable and probably depend on: initial ecological conditions; the magnitude, type and uniformity of environmental alteration occurring in a region; and the sensitivity of individual taxa. It is unlikely that β is controlled by a single mechanism, and these variable mechanisms may have diverse effects on taxon occupancies and hence β. Restoration ecologists will need to consider how β varies naturally across different landscape settings and in response to different types of disturbance when developing region‐wide restoration strategies.

Patterns, causes and consequences of defensive microbiome dynamics across multiple scales - Andrew H. Smith; Piotr Łukasik; Michael P. O'Connor; Amanda Lee; Garrett Mayo; Milton T. Drott; Steven Doll; Robert Tuttle; Rachael A. Disciullo; Andrea Messina; Kerry M. Oliver; Jacob A. Russell (Molecular Ecology, 2015)
The microbiome can significantly impact host phenotypes and serve as an additional source of heritable genetic variation. While patterns across eukaryotes are consistent with a role for symbiotic microbes in host macroevolution, few studies have examined symbiont‐driven host evolution or the ecological implications of a dynamic microbiome across temporal, spatial or ecological scales. The pea aphid, Acyrthosiphon pisum , and its eight heritable bacterial endosymbionts have served as a model for studies on symbiosis and its potential contributions to host ecology and evolution. But we know little about the natural dynamics or ecological impacts of the heritable microbiome of this cosmopolitan insect pest. Here we report seasonal shifts in the frequencies of heritable defensive bacteria from natural pea aphid populations across two host races and geographic regions. Microbiome dynamics were consistent with symbiont responses to host‐level selection and findings from one population suggested symbiont‐driven adaptation to seasonally changing parasitoid pressures. Conversely, symbiont levels were negatively correlated with enemy‐driven mortality when measured across host races, suggesting important ecological impacts of host race microbiome divergence. Rapid drops in symbiont frequencies following seasonal peaks suggest microbiome instability in several populations, with potentially large costs of ‘superinfection’ under certain environmental conditions. In summary, the realization of several laboratory‐derived, a priori expectations suggests important natural impacts of defensive symbionts in host‐enemy eco‐evolutionary feedbacks. Yet negative findings and unanticipated correlations suggest complexities within this system may limit or obscure symbiont‐driven contemporary evolution, a finding of broad significance given the widespread nature of defensive microbes across plants and animals.

Greenland precipitation trends in a long‐term instrumental climate context (1890–2012): evaluation of coastal and ice core records - Sebastian H. Mernild; Edward Hanna; Joseph R. McConnell; Michael Sigl; Andrew P. Beckerman; Jacob C. Yde; John Cappelen; Jeppe K. Malmros; Konrad Steffen (International Journal of Climatology, 2015)
Here, we present an analysis of monthly, seasonal, and annual long‐term precipitation time‐series compiled from coastal meteorological stations in Greenland and Greenland Ice Sheet ( GrIS ) ice cores (including three new ice core records from ACT11D , Tunu2013, and Summit2010). The dataset covers the period from 1890 to 2012, a period of climate warming. For approximately the first decade of the new millennium (2001–2012) minimum and maximum mean annual precipitation conditions are found in Northeast Greenland (Tunu2013 c. 120 mm water equivalent (w.e.) year −1 ) and South Greenland (Ikerasassuaq: c. 2300 mm w.e. year −1 ), respectively. The coastal meteorological stations showed on average increasing trends for 1890–2012 (3.5 mm w.e. year −2 ) and 1961–2012 (1.3 mm w.e. year −2 ). Years with high coastal annual precipitation also had a: (1) significant high number of precipitation days ( r 2 = 0.59); and (2) high precipitation intensity measured as 24‐h precipitation ( r 2 = 0.54). For the GrIS the precipitation estimated from ice cores increased on average by 0.1 mm w.e. year −2 (1890–2000), showing an antiphase variability in precipitation trends between the GrIS and the coastal regions. Around 1960 a major shift occurred in the precipitation pattern towards wetter precipitation conditions for coastal Greenland, while drier conditions became more prevalent on the GrIS . Differences in precipitation trends indicate a heterogeneous spatial distribution of precipitation in Greenland. An Empirical Orthogonal Function analysis reveals a spatiotemporal cycle of precipitation that is linked instantaneously to the North Atlantic Oscillation and the Atlantic Multidecadal Oscillation and with an ∼6 years lag time response to the Greenland Blocking Index.

Changes in digestive traits and body nutritional composition accommodate a trophic niche shift in Trinidadian guppies - Karen E. Sullam; Christopher M. Dalton; Jacob A. Russell; Susan S. Kilham; Rana El-Sabaawi; Donovan P. German; Alexander S. Flecker (Oecologia, 2015)

The interaction of escitalopram and R-citalopram at the human serotonin transporter investigated in the mouse - Jacob P. R. Jacobsen; Per Plenge; Benjamin D. Sachs; Alan L. Pehrson; Manuel Cajina; Yunzhi Du; Wendy Roberts; Meghan L. Rudder; Prachiti Dalvi; Taylor J. Robinson; Sharon P. O’Neill; King S. Khoo; et al. (Psychopharmacology, 2014)

Comparative population structure analysis of Campylobacter jejuni from human and poultry origin in Bangladesh - Z. Islam; A. van Belkum; J. A. Wagenaar; A. J. Cody; A. G. de Boer; S. K. Sarker; B. C. Jacobs; K. A. Talukder; H. P. Endtz (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Erratum to: Phenotypic and molecular confirmation of durable adult plant leaf rust resistance (APR) genes Lr34 +, Lr46 + and Lr67 + linked to leaf tip necrosis (LTN) in select registered Indian wheat ( T. aestivum ) genetic stocks - M. Sivasamy; M. Aparna; J. Kumar; P. Jayaprakash; V.K. Vikas; P. John; R. Nisha; K. Srinivasan; J. Radhamani; S.R. Jacob; S. Kumar; Satyaprakash; et al. (Cereal Research Communications, 2014)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

A compendium of cell and natural unit biovolumes for >1200 freshwater phytoplankton species - Colin T. Kremer; Jacob P. Gillette; Lars G. Rudstam; Pål Brettum; Robert Ptacnik (Ecology, 2014)
Cell size determination is a critical part of sampling phytoplankton communities, as size is both a fundamental trait determining species' ecological niches and a quantity necessary for generating unbiased estimates of community composition. The sizes of algal cells span orders of magnitude, driving variation in growth parameters, sinking rates, herbivore defense, and biogeochemical roles. Size variation occurs at both intra‐ and interspecific levels. Many central questions in community and ecosystem ecology require estimating and comparing the relative abundances of species. Cell counts provide insufficient estimates, due to interspecific variation in cell size, as they over‐estimate the importance of abundant, small species. While cell size (or biovolume) estimation has become standard practice in limnology, many older data sets lack this information, limiting their interpretation and utility. To address these challenges, and advance the study of freshwater phytoplankton communities, we have compiled a database of >260 000 algal biovolume estimates, spanning ∼400 genera and ∼1200 species. This represents the most extensive, standardized, and taxonomically diverse data set of its kind, drawing on both publicly and privately held sources. Estimates of the sizes of colonies or filaments are included, where applicable. With these data researchers will be able to account for intra‐ and interspecific variation in cell size, enabling new and improved analyses of classic data sets.

The surface radiation budget over South America in a set of regional climate models from the CLARIS-LPB project - Natalia L. Pessacg; Silvina A. Solman; Patrick Samuelsson; Enrique Sanchez; José Marengo; Laurent Li; Armelle Reca C. Remedio; Rosmeri P. da Rocha; Caroline Mourão; Daniela Jacob (Climate Dynamics, 2014)

Evidence That Loss-of-Function Filaggrin Gene Mutations Evolved in Northern Europeans to Favor Intracutaneous Vitamin D3 Production - Jacob P. Thyssen; Daniel D. Bikle; Peter M. Elias (Evolutionary Biology, 2014)

Hemorrhagic and ischemic stroke secondary to herpes simplex virus type 2 meningitis and vasculopathy - Samuel B. Snider; Claire S. Jacobs; Patricia S. Scripko; Joshua P. Klein; Jennifer L. Lyons (Journal of NeuroVirology, 2014)

The effects of 12 weeks of beta-hydroxy-beta-methylbutyrate free acid supplementation on muscle mass, strength, and power in resistance-trained individuals: a randomized, double-blind, placebo-controlled study - Jacob M. Wilson; Ryan P. Lowery; Jordan M. Joy; J. C. Andersen; Stephanie M. C. Wilson; Jeffrey R. Stout; Nevine Duncan; John C. Fuller; Shawn M. Baier; Marshall A. Naimo; John Rathmacher (European Journal of Applied Physiology, 2014)

Hydrographical characteristics and oxygen isotopic signatures of water in a coastal environment (Mangalore) along the southeastern Arabian Sea - Josia Jacob; Prosenjit Ghosh; A. P. Dineshbabu; P. Sabu; K. Srinivas; Bindu Sulochanan (Journal of Oceanography, 2014)

A Volatile Relationship: Profiling an Inter-Kingdom Dialogue Between two Plant Pathogens, Ralstonia Solanacearum and Aspergillus Flavus - Joseph E. Spraker; Kelsea Jewell; Ludmila V. Roze; Jacob Scherf; Dora Ndagano; Randolph Beaudry; John E. Linz; Caitilyn Allen; Nancy P. Keller (Journal of Chemical Ecology, 2014)

Stem and leaf rust resistance in wild relatives of wheat with D genome (Aegilops spp.) - V. K. Vikas; M. Sivasamy; J. Kumar; P. Jayaprakash; Sundeep Kumar; R. Parimalan; Arun Kumar; Kalyani Srinivasan; J. Radhamani; Sherry Rachel Jacob; Mamata Yadav; Jyotisna Rani; et al. (Genetic Resources and Crop Evolution, 2014)

Bimineralic bryozoan skeletons: a comparison of three modern genera - G. Benedix; D. E. Jacob; P. D. Taylor (Facies, 2014)

Hypoxia in the Baltic Sea: Biogeochemical Cycles, Benthic Fauna, and Management - Jacob Carstensen; Daniel J. Conley; Erik Bonsdorff; Bo G. Gustafsson; Susanna Hietanen; Urzsula Janas; Tom Jilbert; Alexey Maximov; Alf Norkko; Joanna Norkko; Daniel C. Reed; Caroline P. Slomp; et al. (Ambio, 2014)

A relocation-based initialization scheme to improve track-forecasting of tropical cyclones - Feng Gao; Peter P. Childs; Xiang-Yu Huang; Neil A. Jacobs; Jinzhong Min (Advances in Atmospheric Sciences, 2014)

Simulation of rainfall anomalies leading to the 2005 drought in Amazonia using the CLARIS LPB regional climate models - J. Marengo; S. Chou; C. Mourao; S. Solman; E. Sanchez; P. Samuelsson; R. P. da Rocha; L. Li; N. Pessacg; A. R. C. Remedio; A. F. Carril; I. F Cavalcanti; et al. (Climate Dynamics, 2013)

Meeting Report: Metabolites in Safety Testing (MIST) Symposium—Safety Assessment of Human Metabolites: What’s REALLY Necessary to Ascertain Exposure Coverage in Safety Tests? - Hongying Gao; Abigail Jacobs; Ronald E. White; Brian P. Booth; R. Scott Obach (The AAPS Journal, 2013)

Lack of association of Lysyl oxidase (LOX) gene polymorphisms with intracranial aneurysm in a south Indian population - Sanish Sathyan; Linda Koshy; K. R. Sarada Lekshmi; H. V. Easwer; S. Premkumar; Jacob P. Alapatt; Suresh Nair; R. N. Bhattacharya; Moinak Banerjee (Molecular Biology Reports, 2013)

Thermal equation of state of synthetic orthoferrosilite at lunar pressures and temperatures - J. de Vries; M. H. G. Jacobs; A. P. van den Berg; M. Wehber; C. Lathe; C. A. McCammon; W. van Westrenen (Physics and Chemistry of Minerals, 2013)

Evaluation of an ensemble of regional climate model simulations over South America driven by the ERA-Interim reanalysis: model performance and uncertainties - Silvina A. Solman; E. Sanchez; P. Samuelsson; R. P. da Rocha; L. Li; J. Marengo; N. L. Pessacg; A. R. C. Remedio; S. C. Chou; H. Berbery; H. Le Treut; M. de Castro; et al. (Climate Dynamics, 2013)

Impact of body mass index on neuronal fiber bundle lengths among healthy older adults - Jacob D. Bolzenius; David H. Laidlaw; Ryan P. Cabeen; Thomas E. Conturo; Amanda R. McMichael; Elizabeth M. Lane; Jodi M. Heaps; Lauren E. Salminen; Laurie M. Baker; John Gunstad; Robert H. Paul (Brain Imaging and Behavior, 2013)

In situ analysis of oxygen consumption and diffusive transport in high‐temperature acidic iron‐oxide microbial mats - Hans C. Bernstein; Jacob P. Beam; Mark A. Kozubal; Ross P. Carlson; William P. Inskeep (Environmental Microbiology, 2013)
Summary The role of dissolved oxygen as a principal electron acceptor for microbial metabolism was investigated within Fe ( III )‐oxide microbial mats that form in acidic geothermal springs of Y ellowstone N ational P ark ( USA ). Specific goals of the study were to measure and model dissolved oxygen profiles within high‐temperature (65–75°C) acidic (pH = 2.7–3.8) Fe ( III )‐oxide microbial mats, and correlate the abundance of aerobic, iron‐oxidizing M etallosphaera yellowstonensis organisms and mRNA gene expression levels to Fe ( II )‐oxidizing habitats shown to consume oxygen. In situ oxygen microprofiles were obtained perpendicular to the direction of convective flow across the aqueous phase/ Fe ( III )‐oxide microbial mat interface using oxygen microsensors. Dissolved oxygen concentrations dropped from ∼ 50–60 μM in the bulk‐fluid/mat surface to below detection ( −4 μmol cm −2 s −1 . Dimensionless parameters were used to model dissolved oxygen profiles and establish that mass transfer rates limit the oxygen consumption. A zone of higher dissolved oxygen at the mat surface promotes Fe ( III )‐oxide biomineralization, which was supported using molecular analysis of M etallosphaera yellowstonensis 16 S rRNA gene copy numbers and mRNA expression of haem Cu oxidases ( FoxA ) associated with Fe ( II )‐oxidation.

A role for indirect facilitation in maintaining diversity in a guild of African acacia ants - Todd M. Palmer; Maureen L. Stanton; Truman P. Young; John S. Lemboi; Jacob R. Goheen; Robert M. Pringle (Ecology, 2013)
Determining how competing species coexist is essential to understanding patterns of biodiversity. Indirect facilitation, in which a competitively dominant species exerts a positive effect on one competitor by more strongly suppressing a third, shared competitor, is a potentially potent yet understudied mechanism for competitive coexistence. Here we provide evidence for indirect facilitation in a guild of four African Acacia ant species that compete for nesting space on the host plant Acacia drepanolobium , showing that a competitively dominant acacia ant species indirectly creates establishment opportunities for the most subordinate species that may help to maintain diversity. Using long‐term observational data and field experiments, we demonstrate that the competitively dominant ant species outcompetes two competitively intermediate species, while tolerating colonies of the subordinate competitor; this creates opportunities for local colonization and establishment of colonies of the subordinate species within the dominant species' territories. Host plants occupied by this subordinate species are then more likely to be colonized by the intermediate species, which in turn are more likely to be displaced by the dominant species. This process has the potential to generate a cyclical succession of ant species on host trees, contributing to stable coexistence within this highly competitive community.

Altered calsequestrin glycan processing is common to diverse models of canine heart failure - Sony Jacob; Naama H. Sleiman; Stephanie Kern; Larry R. Jones; Javier A. Sala-Mercado; Timothy P. McFarland; Hani H. Sabbah; Steven E. Cala (Molecular and Cellular Biochemistry, 2013)

The dimensionality of ecological networks - Anna Eklöf; Ute Jacob; Jason Kopp; Jordi Bosch; Rocío Castro‐Urgal; Natacha P. Chacoff; Bo Dalsgaard; Claudio de Sassi; Mauro Galetti; Paulo R. Guimarães; Silvia Beatriz Lomáscolo; Ana M. Martín González; et al. (Ecology Letters, 2013)
How many dimensions (trait‐axes) are required to predict whether two species interact? This unanswered question originated with the idea of ecological niches, and yet bears relevance today for understanding what determines network structure. Here, we analyse a set of 200 ecological networks, including food webs, antagonistic and mutualistic networks, and find that the number of dimensions needed to completely explain all interactions is small (

Germline mutations of regulator of telomere elongation helicase 1, RTEL1, in Dyskeratosis congenita - Bari J. Ballew; Meredith Yeager; Kevin Jacobs; Neelam Giri; Joseph Boland; Laurie Burdett; Blanche P. Alter; Sharon A. Savage (Human Genetics, 2013)

Increased paternal age and the influence on burden of genomic copy number variation in the general population - Jacobine E. Buizer-Voskamp; Hylke M. Blauw; Marco P. M. Boks; Kristel R. van Eijk; Jan H. Veldink; Eric A. M. Hennekam; Jacob A. S. Vorstman; Flip Mulder; Henning Tiemeier; André G. Uitterlinden; Lambertus A. Kiemeney; Leonard H. van den Berg; et al. (Human Genetics, 2013)

Storage and eruption of near-liquidus rhyolite magma at Cordón Caulle, Chile - Jonathan M. Castro; C. Ian Schipper; Sebastian P. Mueller; A. S. Militzer; Alvaro Amigo; Carolina Silva Parejas; Dorrit Jacob (Bulletin of Volcanology, 2013)

Polymorphisms in genes related to one-carbon metabolism are not related to pancreatic cancer in PanScan and PanC4 - Max Leenders; Samsiddhi Bhattacharjee; Paolo Vineis; Victoria Stevens; H. Bas Bueno-de-Mesquita; Xiao-Ou Shu; Laufey Amundadottir; Myron Gross; Geoffrey S. Tobias; Jean Wactawski-Wende; Alan A. Arslan; Eric J. Duell; et al. (Cancer Causes & Control, 2013)

An alternative use of Kieffer’s lattice dynamics model using vibrational density of states for constructing thermodynamic databases - Michael H. G. Jacobs; Rainer Schmid-Fetzer; Arie P. van den Berg (Physics and Chemistry of Minerals, 2013)

A novel link between Campylobacter jejuni bacteriophage defence, virulence and Guillain–Barré syndrome - R. Louwen; D. Horst-Kreft; A. G. Boer; L. Graaf; G. Knegt; M. Hamersma; A. P. Heikema; A. R. Timms; B. C. Jacobs; J. A. Wagenaar; H. P. Endtz; J. Oost; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2013)

Live imaging of DORNRÖSCHEN and DORNRÖSCHEN-LIKE promoter activity reveals dynamic changes in cell identity at the microcallus surface of Arabidopsis embryonic suspensions - M. Cole; B. Jacobs; L. Soubigou-Taconnat; S. Balzergue; J. P. Renou; J. W. Chandler; W. Werr (Plant Cell Reports, 2013)

Outcome definitions and clinical predictors influence pharmacogenetic associations between HTR3A gene polymorphisms and response to clozapine in patients with schizophrenia - A. P. Rajkumar; B. Poonkuzhali; A. Kuruvilla; A. Srivastava; M. Jacob; K. S. Jacob (Psychopharmacology, 2012)

Performance of a multi-RCM ensemble for South Eastern South America - A. F. Carril; C. G. Menéndez; A. R. C. Remedio; F. Robledo; A. Sörensson; B. Tencer; J.-P. Boulanger; M. de Castro; D. Jacob; H. Le Treut; L. Z. X. Li; O. Penalba; et al. (Climate Dynamics, 2012)

Erratum to: Future projections of the surface heat and water budgets of the Mediterranean Sea in an ensemble of coupled atmosphere–ocean regional climate models - C. Dubois; S. Somot; S. Calmanti; A. Carillo; M. Déqué; A. Dell’Aquila; A. Elizalde; S. Gualdi; D. Jacob; B. L’Hévéder; L. Li; P. Oddo; et al. (Climate Dynamics, 2012)

Future projections of the surface heat and water budgets of the Mediterranean Sea in an ensemble of coupled atmosphere–ocean regional climate models - C. Dubois; S. Somot; S. Calmanti; A. Carillo; M. Déqué; A. Dell’Aquilla; A. Elizalde; S. Gualdi; D. Jacob; B. L’Hévéder; L. Li; P. Oddo; et al. (Climate Dynamics, 2012)

Neuroglial Expression of the MHCI Pathway and PirB Receptor Is Upregulated in the Hippocampus with Advanced Aging - Heather D. VanGuilder Starkey; Colleen A. Van Kirk; Georgina V. Bixler; Caesar G. Imperio; Vijay P. Kale; Jacob M. Serfass; Julie A. Farley; Han Yan; Junie P. Warrington; Song Han; Matthew Mitschelen; William E. Sonntag; et al. (Journal of Molecular Neuroscience, 2012)

Endometrial epithelial cell modifications in response to embryonic signals in bonnet monkeys (Macaca radiata) - Shruti Nimbkar-Joshi; Rajendraprasad R. Katkam; Uddhav K. Chaudhari; Sheeba Jacob; Dhananjay D. Manjramkar; Sidhhanath M. Metkari; Indira Hinduja; Vijay Mangoli; Sadhana Desai; Sanjeeva D. Kholkute; Chander P. Puri; Geetanjali Sachdeva (Histochemistry and Cell Biology, 2012)

Evaporation from Heterogeneous and Sparse Canopies: On the Formulations Related to Multi-Source Representations - J. P. Lhomme; C. Montes; F. Jacob; L. Prévot (Boundary-Layer Meteorology, 2012)

Gait adaptability training is affected by visual dependency - Rachel A. Brady; Brian T. Peters; Crystal D. Batson; Robert Ploutz-Snyder; Ajitkumar P. Mulavara; Jacob J. Bloomberg (Experimental Brain Research, 2012)

Environmental and ecological factors that shape the gut bacterial communities of fish: a meta‐analysis - KAREN E. SULLAM; STEVEN D. ESSINGER; CATHERINE A. LOZUPONE; MICHAEL P. O’CONNOR; GAIL L. ROSEN; ROB KNIGHT; SUSAN S. KILHAM; JACOB A. RUSSELL (Molecular Ecology, 2012)
Symbiotic bacteria often help their hosts acquire nutrients from their diet, showing trends of co‐evolution and independent acquisition by hosts from the same trophic levels. While these trends hint at important roles for biotic factors, the effects of the abiotic environment on symbiotic community composition remain comparably understudied. In this investigation, we examined the influence of abiotic and biotic factors on the gut bacterial communities of fish from different taxa, trophic levels and habitats. Phylogenetic and statistical analyses of 25 16S rRNA libraries revealed that salinity, trophic level and possibly host phylogeny shape the composition of fish gut bacteria. When analysed alongside bacterial communities from other environments, fish gut communities typically clustered with gut communities from mammals and insects. Similar consideration of individual phylotypes (vs. communities) revealed evolutionary ties between fish gut microbes and symbionts of animals, as many of the bacteria from the guts of herbivorous fish were closely related to those from mammals. Our results indicate that fish harbour more specialized gut communities than previously recognized. They also highlight a trend of convergent acquisition of similar bacterial communities by fish and mammals, raising the possibility that fish were the first to evolve symbioses resembling those found among extant gut fermenting mammals.

Genetic variation among endangered Irish red grouse (Lagopus lagopus hibernicus) populations: implications for conservation and management - Barry J. McMahon; Magnus P. Johansson; Stuart B. Piertney; Kieran Buckley; Jacob Höglund (Conservation Genetics, 2012)

Brazilian psychiatric brain bank: a new contribution tool to network studies - K. C. de Oliveira; F. G. Nery; R. E. L. Ferreti; M. C. Lima; C. Cappi; A. Machado-Lima; L. Polichiso; L. L. Carreira; C. Ávila; A. T. D. L. Alho; H. P. Brentani; E. C. Miguel; et al. (Cell and Tissue Banking, 2012)

Matrix composition regulates three-dimensional network formation by endothelial cells and mesenchymal stem cells in collagen/fibrin materials - Rameshwar R. Rao; Alexis W. Peterson; Jacob Ceccarelli; Andrew J. Putnam; Jan P. Stegemann (Angiogenesis, 2012)

Low intensity blood flow restriction training: a meta-analysis - Jeremy P. Loenneke; Jacob M. Wilson; Pedro J. Marín; Michael C. Zourdos; Michael G. Bemben (European Journal of Applied Physiology, 2012)

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Various Anticoagulants and Fluoride do not Affect HbA1C Level - Maneesh Mailankot; Thushara Thomas; P. Praveena; Juliet Jacob; Jobin Rajan Benjamin; D. M. Vasudevan (Indian Journal of Clinical Biochemistry, 2012)

A welcome can of worms? Hypoxia mitigation by an invasive species - Joanna Norkko; Daniel C. Reed; Karen Timmermann; Alf Norkko; Bo G. Gustafsson; Erik Bonsdorff; Caroline P. Slomp; Jacob Carstensen; Daniel J. Conley (Global Change Biology, 2012)
Invasive species and bottom‐water hypoxia both constitute major global threats to the diversity and integrity of marine ecosystems. These stressors may interact with unexpected consequences, as invasive species that require an initial environmental disturbance to become established can subsequently become important drivers of ecological change. There is recent evidence that improved bottom‐water oxygen conditions in coastal areas of the northern Baltic Sea coincide with increased abundances of the invasive polychaetes M arenzelleria spp. Using a reactive‐transport model, we demonstrate that the long‐term bioirrigation activities of dense M arenzelleria populations have a major impact on sedimentary phosphorus dynamics. This may facilitate the switch from a seasonally hypoxic system back to a normoxic system by reducing the potential for sediment‐induced eutrophication in the upper water column. In contrast to short‐term laboratory experiments, our simulations, which cover a 10‐year period, show that M arenzelleria has the potential to enhance long‐term phosphorus retention in muddy sediments. Over time bioirrigation leads to a substantial increase in the iron‐bound phosphorus content of sediments while reducing the concentration of labile organic carbon. As surface sediments are maintained oxic, iron oxyhydroxides are able to persist and age into more refractory forms. The model illustrates mechanisms through which M arenzelleria can act as a driver of ecological change, although hypoxic disturbance or natural population declines in native species may be needed for them to initially become established. Invasive species are generally considered to have a negative impact; however, we show here that one of the main recent invaders in the Baltic Sea may provide important ecosystem services. This may be of particular importance in low‐diversity systems, where disturbances may dramatically alter ecosystem services due to low functional redundancy. Thus, an environmental problem in one region may be either exacerbated or alleviated by a single species from another region, with potentially ecosystem‐wide consequences.

Design of Water Distribution Network for Equitable Supply - Jacob Chandapillai; K. P. Sudheer; S. Saseendran (Water Resources Management, 2012)

Regional landslide susceptibility: spatiotemporal variations under dynamic soil moisture conditions - Ram L. Ray; Jennifer M. Jacobs; Thomas P. Ballestero (Natural Hazards, 2011)

Uranium carcinogenicity in humans might depend on the physical and chemical nature of uranium and its isotopic composition: results from pilot epidemiological study of French nuclear workers - I. Guseva Canu; S. Jacob; E. Cardis; P. Wild; S. Caër; B. Auriol; J. P. Garsi; M. Tirmarche; D. Laurier (Cancer Causes & Control, 2011)

Systematic documentation of landslide events in Limbe area (Mt Cameroon Volcano, SW Cameroon): geometry, controlling, and triggering factors - V. B. Che; M. Kervyn; G. G. J. Ernst; P. Trefois; S. Ayonghe; P. Jacobs; E. Van Ranst; C. E. Suh (Natural Hazards, 2011)

Regulation of caspase pathways by protein kinase CK2: identification of proteins with overlapping CK2 and caspase consensus motifs - Jacob P. Turowec; James S. Duncan; Greg B. Gloor; David W. Litchfield (Molecular and Cellular Biochemistry, 2011)

Genomic analysis of the phenylacetyl-CoA pathway in Burkholderia xenovorans LB400 - Marianna A. Patrauchan; J. Jacob Parnell; Michael P. McLeod; Christine Florizone; James M. Tiedje; Lindsay D. Eltis (Archives of Microbiology, 2011)

The evolution of chloroplast genes and genomes in ferns - Paul G. Wolf; Joshua P. Der; Aaron M. Duffy; Jacob B. Davidson; Amanda L. Grusz; Kathleen M. Pryer (Plant Molecular Biology, 2011)

Evidence of Surface Connectivity for Texas Gulf Coast Depressional Wetlands - Bradford P. Wilcox; Dex D. Dean; John S. Jacob; Andrew Sipocz (Wetlands, 2011)

Study of changes in bacterial and viral abundance in formaldehyde-fixed water samples by epifluorescence microscopy - Ammini Parvathi; Seetha Radhakrishnan; M. P. Sajila; Breezy Jacob (Environmental Monitoring and Assessment, 2011)

Increased CD36 expression in middle-aged mice contributes to obesity-related cardiac hypertrophy in the absence of cardiac dysfunction - Miranda M. Y. Sung; Debby P. Y. Koonen; Carrie-Lynn M. Soltys; René L. Jacobs; Maria Febbraio; Jason R. B. Dyck (Journal of Molecular Medicine, 2011)

Proposed Hydrogeomorphic Classification for Wetlands of the Mid-Atlantic Region, USA - Robert P. Brooks; Mark M. Brinson; Kirk J. Havens; Carl S. Hershner; Richard D. Rheinhardt; Denice H. Wardrop; Dennis F. Whigham; Amy D. Jacobs; Jennifer M. Rubbo (Wetlands, 2011)

Improving balance function using vestibular stochastic resonance: optimizing stimulus characteristics - Ajitkumar P. Mulavara; Matthew J. Fiedler; Igor S. Kofman; Scott J. Wood; Jorge M. Serrador; Brian Peters; Helen S. Cohen; Millard F. Reschke; Jacob J. Bloomberg (Experimental Brain Research, 2011)

Gait training improves performance in healthy adults exposed to novel sensory discordant conditions - Crystal D. Batson; Rachel A. Brady; Brian T. Peters; Robert J. Ploutz-Snyder; Ajitkumar P. Mulavara; Helen S. Cohen; Jacob J. Bloomberg (Experimental Brain Research, 2011)

Small-scale mineralogical heterogeneity from variations in phase assemblages in the transition zone and D″ layer predicted by convection modelling - Arie P. van den Berg; David A. Yuen; Michael H. G. Jacobs; Maarten V. de Hoop (Journal of Earth Science, 2011)

Effects of Postfire Salvage Logging on Deadwood‐Associated Beetles - T. P. COBB; J. L. MORISSETTE; J. M. JACOBS; M. J. KOIVULA; J. R. SPENCE; D. W. LANGOR (Conservation Biology, 2011)
In Canada and the United States pressure to recoup financial costs of wildfire by harvesting burned timber is increasing, despite insufficient understanding of the ecological consequences of postfire salvage logging. We compared the species richness and composition of deadwood‐associated beetle assemblages among undisturbed, recently burned, logged, and salvage‐logged, boreal, mixed‐wood stands. Species richness was lowest in salvage‐logged stands, largely due to a negative effect of harvesting on the occurrence of wood‐ and bark‐boring species. In comparison with undisturbed stands, the combination of wildfire and logging in salvage‐logged stands had a greater effect on species composition than either disturbance alone. Strong differences in species composition among stand treatments were linked to differences in quantity and quality (e.g., decay stage) of coarse woody debris. We found that the effects of wildfire and logging on deadwood‐associated beetles were synergistic, such that the effects of postfire salvage logging could not be predicted reliably on the basis of data on either disturbance alone. Thus, increases in salvage logging of burned forests may have serious negative consequences for deadwood‐associated beetles and their ecological functions in early postfire successional forests.

Microbial properties of soil aggregates created by earthworms and other factors: spherical and prismatic soil aggregates from unreclaimed post-mining sites - J. Frouz; V. Krištůfek; M. Livečková; D. van Loo; P. Jacobs; L. Van Hoorebeke (Folia Microbiologica, 2011)

Atrophy in the parahippocampal gyrus as an early biomarker of Alzheimer’s disease - C. Echávarri; P. Aalten; H. B. M. Uylings; H. I. L. Jacobs; P. J. Visser; E. H. B. M. Gronenschild; F. R. J. Verhey; S. Burgmans (Brain Structure and Function, 2011)

Pooled analyses of 13 prospective cohort studies on folate intake and colon cancer - Dong-Hyun Kim; Stephanie A. Smith-Warner; Donna Spiegelman; Shiaw-Shyuan Yaun; Graham A. Colditz; Jo L. Freudenheim; Edward Giovannucci; R. Alexandra Goldbohm; Saxon Graham; Lisa Harnack; Eric J. Jacobs; Michael Leitzmann; et al. (Cancer Causes & Control, 2010)

Evolutionary history of the Paradoxurus palm civets – a new model for Asian biogeography - Marie‐Lilith Patou; Andreas Wilting; Philippe Gaubert; Jacob A. Esselstyn; Corinne Cruaud; Andrew P. Jennings; Jörns Fickel; Géraldine Veron (Journal of Biogeography, 2010)
Aim Using molecular data and dental features, we investigated the genetic and morphological diversity among species of palm civets in the genus Paradoxurus , with a focus on the common palm civet, Paradoxurus hermaphroditus (Carnivora, Viverridae), in order to address biogeographic scenarios and provide recommendations for a taxonomic revision. Location Asia: Pakistan to the Lesser Sunda Islands. Methods We investigated the genetic diversity within Paradoxurus using two mitochondrial (cytochrome b , control region) and one nuclear (intron 7 of the β‐fibrinogen) markers. We used samples from 85 individuals of P. hermaphroditus (including 20 museum specimens) and one representative of each of the other species in the genus Paradoxurus : Paradoxurus jerdoni and Paradoxurus zeylonensis . DNA sequences were analysed using phylogenetic and haplotype network methods, and divergence dates were estimated for the clades retrieved. Furthermore, we examined dental characters from a large series of specimens and compared the morphological variation with the molecular data. Results Our phylogenetic analyses revealed that P. hermaphroditus is paraphyletic. We identified three major lineages distributed: (1) in the Indian subcontinent, south China, Hainan and in areas above 200 m in Indochina; (2) in Peninsular Malaysia, Java, Sumatra and in areas below 200 m in Indochina; and (3) in Borneo, the Philippines and the Mentawai archipelago. Our morphological observations were congruent with these three molecular lineages. Divergence date estimates inferred a Pliocene origin for Paradoxurus (2.8–5.7 Ma), with the three main clades diversifying from the mid–Early Pliocene to the end of the Pliocene. We suggest that the flooding of the Isthmus of Kra during the Pliocene was a major event shaping the diversification of Paradoxurus palm civets. We also hypothesize that the elevational segregation of the two lineages on the mainland could have resulted from the vegetational changes that were induced by Late Pliocene glacial episodes. Main conclusions The Isthmus of Kra is a major boundary between two major lineages of P. hermaphroditus . There is a need for a taxonomic revision for P. hermaphroditus , and we suggest that this species should be split into at least three species.

Locomotor function after long-duration space flight: effects and motor learning during recovery - Ajitkumar P. Mulavara; Alan H. Feiveson; James Fiedler; Helen Cohen; Brian T. Peters; Chris Miller; Rachel Brady; Jacob J. Bloomberg (Experimental Brain Research, 2010)

Evaluation of the Immunoquick+4 malaria rapid diagnostic test in a non-endemic setting - D. P. J. Dijk; P. Gillet; E. Vlieghe; L. Cnops; M. Esbroeck; J. Jacobs (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Emissions of N2O from fertilized and grazed grassland on organic soil in relation to groundwater level - C. L. van Beek; M. Pleijter; C. M. J. Jacobs; G. L. Velthof; J. W. van Groenigen; P. J. Kuikman (Nutrient Cycling in Agroecosystems, 2010)

Environmental constraints modify the way an interceptive action is controlled - Antoine H. P. Morice; Matthieu François; David M. Jacobs; Gilles Montagne (Experimental Brain Research, 2010)

Downscaling extreme month-long anomalies in southern South America - C. G. Menéndez; M. de Castro; J.-P. Boulanger; A. D’Onofrio; E. Sanchez; A. A. Sörensson; J. Blazquez; A. Elizalde; D. Jacob; H. Le Treut; Z. X. Li; M. N. Núñez; et al. (Climatic Change, 2010)

Potato Transformation with Modified Nucleotide Sequences of the cry9Aa2 Gene Improves Resistance to Potato Tuber Moth - Jeanne M. E. Jacobs; Michael F. G. Takla; Lisa C. Docherty; Christina M. Frater; Ngaire P. Markwick; Sathiyamoorthy Meiyalaghan; Anthony J. Conner (Potato Research, 2009)

Biogenic volatile organic compounds from an invasive species: impacts on plant–plant interactions - Jacob N. Barney; Jed P. Sparks; Jim Greenberg; Thomas H. Whitlow; Alex Guenther (Plant Ecology, 2009)

Haptoglobin genotype and endothelial function in diabetes mellitus: a pilot study - Lior Dayan; Andrew P. Levy; Shany Blum; Rachel Miller-Lotan; Uzi Melman; Jonia Alshiek; Giris Jacob (European Journal of Applied Physiology, 2009)

Geospatial variability in the egg raft distribution and abundance of Culex pipiens and Culex restuans in Urbana‐Champaign, Illinois - B. G. Jacob; R. L. Lampman; M. P. Ward; E. J. Muturi; J. A. Morris; E. X. Caamano; R. J. Novak (International Journal of Remote Sensing, 2009)

The distribution and habitat preference of coastally occurring minke whales (Balaenoptera acutorostrata) in the outer southern Moray Firth, northeast Scotland - Kevin P. Robinson; Michael J. Tetley; E. Gay Mitchelson-Jacob (Journal of Coastal Conservation, 2009)

Influence of agricultural practices on micrometerological spatial variations at local and regional scales - D. Courault; F. Jacob; V. Benoit; M. Weiss; O. Marloie; J. F. Hanocq; E. Fillol; A. Olioso; G. Dedieu; P. Gouaux; M. Gay; A. French (International Journal of Remote Sensing, 2009)

Adverse effects of parenteral antimicrobial therapy for chronic bone infections - C. Pulcini; T. Couadau; E. Bernard; A. Lorthat-Jacob; T. Bauer; E. Cua; V. Mondain; R.-M. Chichmanian; P. Dellamonica; P.-M. Roger (European Journal of Clinical Microbiology & Infectious Diseases, 2008)

Pichia surface display: display of proteins on the surface of glycoengineered Pichia pastoris strains - Pieter P. Jacobs; Stefan Ryckaert; Steven Geysens; Kristof De Vusser; Nico Callewaert; Roland Contreras (Biotechnology Letters, 2008)

Escherichia coli FtnA acts as an iron buffer for re-assembly of iron–sulfur clusters in response to hydrogen peroxide stress - Jacob P. Bitoun; Genfu Wu; Huangen Ding (BioMetals, 2008)

Remote sensing study of sector collapses and debris avalanche deposits at Oldoinyo Lengai and Kerimasi volcanoes, Tanzania - M. Kervyn; G. G. J. Ernst; J. Klaudius; J. Keller; E. Mbede; P. Jacobs (International Journal of Remote Sensing, 2008)

A new approach to assess long‐term lava flow hazard and risk using GIS and low‐cost remote sensing: the case of Mount Cameroon, West Africa - K. Bonne; M. Kervyn; L. Cascone; S. Njome; E. Van Ranst; E. Suh; S. Ayonghe; P. Jacobs; G. Ernst (International Journal of Remote Sensing, 2008)

Mapping volcano topography with remote sensing: ASTER vs . SRTM - M. Kervyn; G. G. J. Ernst; R. Goossens; P. Jacobs (International Journal of Remote Sensing, 2008)

Thermal remote sensing of the low‐intensity carbonatite volcanism of Oldoinyo Lengai, Tanzania - M. Kervyn; G. G. J. Ernst; A. J. L. Harris; F. Belton; E. Mbede; P. Jacobs (International Journal of Remote Sensing, 2008)

The influence of the Gulf Stream induced SST gradients on the US East Coast winter storm of 24–25 January 2000 - N. A. Jacobs; S. Raman; G. M. Lackmann; P. P. Childs (International Journal of Remote Sensing, 2008)

The effect of water turbidity on the near-surface water temperature of larval habitats of the malaria mosquito Anopheles gambiae - K. P. Paaijmans; W. Takken; A. K. Githeko; A. F. G. Jacobs (International Journal of Biometeorology, 2008)

A simplified model to predict diurnal water temperature dynamics in a shallow tropical water pool - Krijn P. Paaijmans; Bert G. Heusinkveld; Adrie F. G. Jacobs (International Journal of Biometeorology, 2008)

Testing the role of expansion in the prospective control of locomotion - Julien Bastin; David M. Jacobs; Antoine H. P. Morice; Cathy Craig; Gilles Montagne (Experimental Brain Research, 2008)

An integrated modelling and remote sensing approach for hydrological study in arid and semi‐arid regions: the SUDMED Programme - A. Chehbouni; R. Escadafal; B. Duchemin; G. Boulet; V. Simonneaux; G. Dedieu; B. Mougenot; S. Khabba; H. Kharrou; P. Maisongrande; O. Merlin; A. Chaponnière; et al. (International Journal of Remote Sensing, 2008)

Comprehensive resequence analysis of a 136 kb region of human chromosome 8q24 associated with prostate and colon cancers - Meredith Yeager; Nianqing Xiao; Richard B. Hayes; Pascal Bouffard; Brian Desany; Laura Burdett; Nick Orr; Casey Matthews; Liqun Qi; Andrew Crenshaw; Zdenek Markovic; Karin M. Fredrikson; et al. (Human Genetics, 2008)

Assessment of factors that confound MRI and neuropathological correlation of human postmortem brain tissue - Lea T. Grinberg; Edson Amaro; Stefan Teipel; Denis Dionizio dos Santos; Carlos Augusto Pasqualucci; Renata E. P. Leite; Celia Regina Camargo; Jaqueline Alba Gonçalves; Ariadne Gonçalves Sanches; Miriam Santana; Renata E. L. Ferretti; Wilson Jacob-Filho; et al. (Cell and Tissue Banking, 2008)

Insensitivity of NMRI mice to selective serotonin reuptake inhibitors in the tail suspension test can be reversed by co-treatment with 5-hydroxytryptophan - Jacob P. R. Jacobsen; Elsebet Ø. Nielsen; Rene Hummel; John Paul Redrobe; Naheed Mirza; Pia Weikop (Psychopharmacology, 2008)

Imaging aspects of cardiovascular disease at the cell and molecular level - Douglas J. Taatjes; Marilyn P. Wadsworth; Anthony S. Quinn; Jacob H. Rand; Edwin G. Bovill; Burton E. Sobel (Histochemistry and Cell Biology, 2008)

Cognitive and motor function are associated following mild traumatic brain injury - Jacob J. Sosnoff; Steven P. Broglio; Michael S. Ferrara (Experimental Brain Research, 2008)

Hydrographic characterization of southeast Arabian Sea during the wane of southwest monsoon and spring intermonsoon - K. G. Vimal Kumar; P. K. Dinesh Kumar; B. R. Smitha; H. Habeeb Rahman; Jacob Josia; K. R. Muraleedharan; V. N. Sanjeevan; C. T. Achuthankutty (Environmental Monitoring and Assessment, 2008)

Diurnal temperature fluctuations in an artificial small shallow water body - Adrie F. G. Jacobs; Bert G. Heusinkveld; Aline Kraai; Krijn P. Paaijmans (International Journal of Biometeorology, 2008)

An evaluation of Arctic cloud and radiation processes during the SHEBA year: simulation results from eight Arctic regional climate models - K. Wyser; C. G. Jones; P. Du; E. Girard; U. Willén; J. Cassano; J. H. Christensen; J. A. Curry; K. Dethloff; J.-E. Haugen; D. Jacob; M. Køltzow; et al. (Climate Dynamics, 2008)

Object localization through the lateral line system of fish: theory and experiment - Julie Goulet; Jacob Engelmann; Boris P. Chagnaud; Jan-Moritz P. Franosch; Maria D. Suttner; J. Leo van Hemmen (Journal of Comparative Physiology A, 2008)

Atypical status of bovine spongiform encephalopathy in Poland: a molecular typing study - M. P. Polak; J. F. Zmudzinski; J. G. Jacobs; J. P. M. Langeveld (Archives of Virology, 2008)

Induction of experimental cerebral malaria is independent of TLR2/4/9 - Bernd Lepenies; Jakob P. Cramer; Gerd D. Burchard; Hermann Wagner; Carsten J. Kirschning; Thomas Jacobs (Medical Microbiology and Immunology, 2007)

Niche width collapse in a resilient top predator following ecosystem fragmentation - Craig A. Layman; John P. Quattrochi; Caroline M. Peyer; Jacob E. Allgeier (Ecology Letters, 2007)
Much research has focused on identifying species that are susceptible to extinction following ecosystem fragmentation, yet even those species that persist in fragmented habitats may have fundamentally different ecological roles than conspecifics in unimpacted areas. Shifts in trophic role induced by fragmentation, especially of abundant top predators, could have transcendent impacts on food web architecture and stability, as well as ecosystem function. Here we use a novel measure of trophic niche width, based on stable isotope ratios, to assess effects of aquatic ecosystem fragmentation on trophic ecology of a resilient, dominant, top predator. We demonstrate collapse in trophic niche width of the predator in fragmented systems, a phenomenon related to significant reductions in diversity of potential prey taxa. Collapsed niche width reflects a homogenization of energy flow pathways to top predators, likely serving to destabilize remnant food webs and render apparently resilient top predators more susceptible to extinction through time.

Comparing functional assessments of wetlands to measurements of soil characteristics and nitrogen processing - Thomas E. Jordan; Mary Pittek Andrews; Ryan P. Szuch; Dennis F. Whigham; Donald E. Weller; Amy Deller Jacobs (Wetlands, 2007)

A genetically encoded indicator for monitoring intracellular chloride - O. Markova; E. Réal; Y. Jacob; M. Mukhtarov; P. Bregestovski (Neurophysiology, 2007)

Extracellular heat shock protein 60 (Hsp60) levels in children with septic shock - D. S. Wheeler; P. Lahni; K. Odoms; B. R. Jacobs; J. A. Carcillo; L. A. Doughty; H. R. Wong (Inflammation Research, 2007)

An intercomparison of regional climate simulations for Europe: assessing uncertainties in model projections - M. Déqué; D. P. Rowell; D. Lüthi; F. Giorgi; J. H. Christensen; B. Rockel; D. Jacob; E. Kjellström; M. de Castro; B. van den Hurk (Climatic Change, 2007)

The interplay between strategic and adaptive control mechanisms in plastic recalibration of locomotor function - Jason T. Richards; Ajitkumar P. Mulavara; Jacob J. Bloomberg (Experimental Brain Research, 2007)

The influence of matrix attachment regions on transgene expression in Arabidopsis thaliana wild type and gene silencing mutants - Miguel F. C. De Bolle; Katleen M. J. Butaye; Inge J. W. M. Goderis; Piet F. J. Wouters; Anni Jacobs; Stijn L. Delauré; Ann Depicker; Bruno P. A. Cammue (Plant Molecular Biology, 2007)

Monocyte macrophage differentiation in vitro: Fibronectin-dependent upregulation of certain macrophage-specific activities - P. R. Sudhakaran; A. Radhika; S. S. Jacob (Glycoconjugate Journal, 2006)

Exploration and Collection of Coconut Germplasm in Kadmat and Amini Islands of Lakshadweep, India - K. Samsudeen; P. M. Jacob; V. Niral; P. M. Kumaran; Radha Salooja; H. Moosa (Genetic Resources and Crop Evolution, 2006)

Evaluation of an ensemble of Arctic regional climate models: spatiotemporal fields during the SHEBA year - A. Rinke; K. Dethloff; J. J. Cassano; J. H. Christensen; J. A. Curry; P. Du; E. Girard; J.-E. Haugen; D. Jacob; C. G. Jones; M. Køltzow; R. Laprise; et al. (Climate Dynamics, 2006)

Racial Differences in Clinical Progression Among Medicare Recipients After Treatment for Localized Prostate Cancer (United States) - Jacob H. Cohen; Victor J. Schoenbach; Jay S. Kaufman; James A. Talcott; Anna P. Schenck; Sharon Peacock; Michael Symons; M. Ahinee Amamoo; William R. Carpenter; Paul A. Godley (Cancer Causes & Control, 2006)

Effect of training and detraining on catecholamine responses to sprint exercise in adolescent girls - M. Botcazou; H. Zouhal; C. Jacob; A. Gratas-Delamarche; P. M. Berthon; D. Bentué-Ferrer; P. Delamarche (European Journal of Applied Physiology, 2006)

Evaluation of an ensemble of Arctic regional climate models: spatiotemporal fields during the SHEBA year - A. Rinke; K. Dethloff; J. J. Cassano; J. H. Christensen; J. A. Curry; P. Du; E. Girard; J.-E. Haugen; D. Jacob; C. G. Jones; M. Køltzow; R. Laprise; et al. (Climate Dynamics, 2006)

A clinical and molecular study of 26 females with Xp deletions with special emphasis on inherited deletions - K. L. Lachlan; S. Youings; T. Costa; P. A. Jacobs; N. S. Thomas (Human Genetics, 2006)

International, open-label, noncomparative, clinical trial of micafungin alone and in combination for treatment of newly diagnosed and refractory candidemia - L. Ostrosky-Zeichner; D. Kontoyiannis; J. Raffalli; K. M. Mullane; J. Vazquez; E. J. Anaissie; J. Lipton; P. Jacobs; J. H. Jansen Rensburg; J. H. Rex; W. Lau; D. Facklam; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Effects of Urbanization on the Distribution and Abundance of Amphibians and Invasive Species in Southern California Streams - SETH P. D. RILEY; GARY T. BUSTEED; LEE B. KATS; THOMAS L. VANDERGON; LENA F. S. LEE; ROSI G. DAGIT; JACOB L. KERBY; ROBERT N. FISHER; RAYMOND M. SAUVAJOT (Conservation Biology, 2005)
Urbanization negatively affects natural ecosystems in many ways, and aquatic systems in particular. Urbanization is also cited as one of the potential contributors to recent dramatic declines in amphibian populations. From 2000 to 2002 we determined the distribution and abundance of native amphibians and exotic predators and characterized stream habitat and invertebrate communities in 35 streams in an urbanized landscape north of Los Angeles (U.S.A.). We measured watershed development as the percentage of area within each watershed occupied by urban land uses. Streams in more developed watersheds often had exotic crayfish (Procambarus clarkii) and fish, and had fewer native species such as California newts (Taricha torosa) and California treefrogs (Hyla cadaverina). These effects seemed particularly evident above 8% development, a result coincident with other urban stream studies that show negative impacts beginning at 10–15% urbanization. For Pacific treefrogs (H. regilla), the most widespread native amphibian, abundance was lower in the presence of exotic crayfish, although direct urbanization effects were not found. Benthic macroinvertebrate communities were also less diverse in urban streams, especially for sensitive species. Faunal community changes in urban streams may be related to changes in physical stream habitat, such as fewer pool and more run habitats and increased water depth and flow, leading to more permanent streams. Variation in stream permanence was particularly evident in 2002, a dry year when many natural streams were dry but urban streams were relatively unchanged. Urbanization has significantly altered stream habitat in this region and may enhance invasion by exotic species and negatively affect diversity and abundance of native amphibians.

International, open-label, noncomparative, clinical trial of micafungin alone and in combination for treatment of newly diagnosed and refractory candidemia - L. Ostrosky-Zeichner; D. Kontoyiannis; J. Raffalli; K. M. Mullane; J. Vazquez; E. J. Anaissie; J. Lipton; P. Jacobs; J. H. Jansen Rensburg; J. H. Rex; W. Lau; D. Facklam; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Early life history and settlement of the slender filefish, Monacanthus tuckeri (Monacanthidae), at Calabash Caye, Turneffe Atoll, Belize - Jessica Ben-David; Jacob P. Kritzer (Environmental Biology of Fishes, 2005)

Thyroxine-induced alterations in the testis and seminal vesicles of air-breathing catfish, Clarias gariepinus - T. N. Jacob; J. P. Pandey; K. Raghuveer; G. Sreenivasulu; A. D. Gupta; M. Yoshikuni; A. Jagota; B. Senthilkumaran (Fish Physiology and Biochemistry, 2005)

Evidence for emergence of an amphibian iridoviral disease because of human‐enhanced spread - J. K. JANCOVICH; E. W. DAVIDSON; N. PARAMESWARAN; J. MAO; V. G. CHINCHAR; J. P. COLLINS; B. L. JACOBS; A. STORFER (Molecular Ecology, 2005)
Our understanding of origins and spread of emerging infectious diseases has increased dramatically because of recent applications of phylogenetic theory. Iridoviruses are emerging pathogens that cause global amphibian epizootics, including tiger salamander ( Ambystoma tigrinum ) die‐offs throughout western North America. To explain phylogeographical relationships and potential causes for emergence of western North American salamander iridovirus strains, we sequenced major capsid protein and DNA methyltransferase genes, as well as two noncoding regions from 18 geographically widespread isolates. Phylogenetic analyses of sequence data from the capsid protein gene showed shallow genetic divergence ( Ranavirus , suggesting a single introduction and radiation. Analysis of capsid protein sequences also provided support for a closer relationship of tiger salamander virus strains to those isolated from sport fish (e.g. rainbow trout) than other amphibian isolates. Despite monophyly based on capsid protein sequences, there was low genetic divergence among all strains ( Ambystoma mexicanum ) colony. Human enhancement of viral movement is a mechanism consistent with these results. These findings suggest North American salamander ranaviruses cause emerging disease, as evidenced by apparent recent spread over a broad geographical area.

Evaluation of water and energy budgets in regional climate models applied over Europe - S. Hagemann; B. Machenhauer; R. Jones; O. B. Christensen; M. Dqu; D. Jacob; P. L. Vidale (Climate Dynamics, 2004)

Effects of Noncompliance on the Success of Alternative Designs of Marine Protected‐Area Networks for Conservation and Fisheries Management - JACOB P. KRITZER (Conservation Biology, 2004)
Studies examining the efficacy of marine protected areas (MPAs) rarely consider the potential for noncompliance. Violation of MPAs will typically occur near boundaries, so perimeter‐to‐area ratios will be important determinants of actual protection, suggesting that MPAs should be larger and likely fewer. If larval dispersal is highly localized, however, MPAs will need to be more numerous, widespread, and likely smaller in order to replenish many fished areas. Thus, there is a discord between the MPA network that would best achieve external replenishment and that which would maximize compliance. I investigated these competing criteria with a spatially structured model of a hypothetical marine fishery exploiting a sedentary reef‐dwelling organism. With full compliance, a network of several small MPAs protects a population of similar size to that in a single large MPA and produces higher fishery yield across a range of fishing mortality rates. As noncompliance increases, however, the protected population in the network of several small MPAs approaches zero, whereas the single, large MPA population declines much less. Furthermore, at high levels of fishing mortality and noncompliance, yield with the network of several small MPAs begins to mirror that with no MPAs and drops below the yield with the single large MPA. Temporal variability in both the protected population size and yield are similar between the two designs with full compliance, but the single large MPA provides much greater stability in both metrics at high fishing mortality rates as noncompliance increases. My results highlight the important effects of noncompliance in realized MPA benefits and can explain why observed and expected effects might differ. Moreover, my results support a call for increased attention to rates of noncompliance and their ecological effects and greater collaboration among natural scientists, social scientists, managers, and stakeholders in understanding and altering illegal behavior.

Metapopulation ecology in the sea: from Levins' model to marine ecology and fisheries science - Jacob P Kritzer; Peter F Sale (Fish and Fisheries, 2004)
Marine and fisheries scientists are increasingly using metapopulation concepts to better understand and model their focal systems. Consequently, they are considering what defines a metapopulation. One perspective on this question emphasizes the importance of extinction probability in local populations. This view probably stems from the focus on extinction in Levins' original metapopulation model, but places unnecessary emphasis on extinction–recolonization dynamics. Metapopulation models with more complex structure than Levins' patch‐occupancy model and its variants allow a broader range of population phenomena to be examined, such as changes in population size, age structure and genetic structure. Analyses along these lines are critical in fisheries science, where presence–absence resolution is far too coarse to understand stock dynamics in a meaningful way. These more detailed investigations can, but need not, aim to assess extinction risk or deal with extinction‐prone local populations. Therefore, we emphasize the coupling of spatial scales as the defining feature of metapopulations. It is the degree of demographic connectivity that characterizes metapopulations, with the dynamics of local populations strongly dependent upon local demographic processes, but also influenced by a nontrivial element of external replenishment. Therefore, estimating rates of interpopulation exchange must be a research priority. We contrast metapopulations with other spatially structured populations that differ in the degree of local closure of their component populations. We conclude with consideration of the implications of metapopulation structure for spatially explicit management, particularly the design of marine protected area networks.

Dopamine deficits and regulation of the cAMP second messenger system in brains of simian immunodeficiency virus–infected rhesus monkeys - M Jenuwein; C Scheller; E Neuen-Jacob; S Sopper; T Tatschner; V Meulen; P Riederer; E Koutsilieri (Journal of NeuroVirology, 2004)

Analysis of relatedness and determination of the source of founders in the captive bearded vulture, Gypaetus barbatus, population - Barbara Gautschi; Gwenaël Jacob; Juan J. Negro; Jose A. Godoy; Jürg P. Müller; Bernhard Schmid (Conservation Genetics, 2003)

Volumetric and aerial rates of heterotrophic bacterial production in epi- and hypolimnia: the role of nutrients and system morphometry - André C. P. Cimbleris; Jacob Kalff (Hydrobiologia, 2003)

Occurrence of MRSA Endocarditis During Linezolid Treatment - E. H. Ben Mansour; E. Jacob; M. Monchi; D. Ledoux; J.-L. Canivet; P. De Mol; P. Damas (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Instability of short-sequence DNA repeats of pear pathogenic Erwinia strains from Japan and Erwinia amylovora fruit tree and raspberry strains - S. Jock; T. Jacob; W.-S. Kim; M. Hildebrand; H.-P. Vosberg; K. Geider (Molecular Genetics and Genomics, 2003)

Behaviour of carbon dioxide and water vapour flux densities from a disturbed raised peat bog - Joost P. Nieveen; Adrie F. G. Jacobs (International Journal of Climatology, 2002)
Measurements of carbon dioxide and water vapour flux densities were carried out for a disturbed raised peat bog in the north of the Netherlands during an 18 month continuous experiment. Tussock grass (sp. Molinea caerulae ) mainly dominated the vegetation of the bog area. The maximum leaf area index (LAI) of the vegetation reached a numerical value of about 1.7 in mid‐August. When the LAI is large enough (LAI > 0.2), a mean net uptake of carbon dioxide is observed with a clear daily pattern. The total evapotranspiration consists of a soil, an open water, and a plant transpiration part. When the LAI is large enough (LAI > 0.2), plant transpiration dominates the total evapotranspiration. The mean daily transpiration pattern, however, is not similar to the carbon dioxide uptake pattern. During the summer months, the daytime carbon dioxide uptake shows a single early morning maximum value followed by a decline in uptake during the rest of the day. The evapotranspiration, however, follows more or less the incoming short‐wave radiation pattern. Effects of the vapour pressure deficit are suggested as a possible cause of this discrepancy. Copyright © 2002 Royal Meteorological Society.

Sorghum lysine-rich cultivar verification by SDS-PAGE and Southern blot - N. P. Eswara Reddy; M. Jacobs (Acta Physiologiae Plantarum, 2002)

Analysis of Dihydrodipicolinate Synthase Promoter Activity in Arabidopsis thaliana by In-Planta Transformation - N. P. Eswara Reddyl; M. Anuradha; Marc Vauterin; M. Jacobs; David J. Oliver (Journal of Plant Biochemistry and Biotechnology, 2002)

Benzo-a-Pyrene Residues in Liver and in Bile of Fish Following Oral Exposure - M. U. Beg; P. G. Jacob; K. Al-Matrouk; K. R. Beg; M. Al-Bahloul; T. Saeed (Bulletin of Environmental Contamination and Toxicology, 2002)

Stock Structure, Mortality and Growth of The Decorated Goby, Istigobius decoratus (Gobiidae), at Lizard Island, Great Barrier Reef - Jacob P. Kritzer (Environmental Biology of Fishes, 2002)

Ceftazidime- and Imipenem-Induced Endotoxin Release During Treatment of Gram-Negative Infections - B. Byl; P. Clevenbergh; A. Kentos; F. Jacobs; A. Marchant; J. Vincent; J. Thys (European Journal of Clinical Microbiology & Infectious Diseases, 2001)

Comment on Elit et al.: Prophylactic oophorectomy in Ontario - R. P. Zweemer; I. J. Jacobs (Familial Cancer, 2001)

A comprehensive model inter-comparison study investigating the water budget during the BALTEX-PIDCAP period - D. Jacob; B. J. J. M. Van den Hurk; U. Andr; G. Elgered; C. Fortelius; L. P. Graham; S. D. Jackson; U. Karstens; Chr. Kpken; R. Lindau; R. Podzun; B. Rockel; et al. (Meteorology and Atmospheric Physics, 2001)

Biomarker Response in Sheim ( Acanthopagrus latus ) Exposed to Polycyclic Aromatic Hydrocarbons - M. U. Beg; M. Al-Bahloul; P. G. Jacob; K. R. Beg; K. Al-Matrouk; K. Abdel-Elah (Bulletin of Environmental Contamination and Toxicology, 2001)

Metabolism of chicory fructooligosaccharides by bifidobacteria - A. Durieux; C. Fougnies; H. Jacobs; J.-P. Simon (Biotechnology Letters, 2001)

Biochemical Characterisation and Cloning of α-Kafirin Gene from Sorghum (Sorghum bicolor L Moench) - N. P. Eswara Reddy; Marc Vauterin; Valérié Frankard; M. Jacobs (Journal of Plant Biochemistry and Biotechnology, 2001)

Independent origins and horizontal transfer of bacterial symbionts of aphids - Jonas P. Sandström; Jacob A. Russell; Joshua P. White; Nancy A. Moran (Molecular Ecology, 2001)
Many insect groups have obligate associations with primary endosymbionts: mutualistic bacteria that are maternally transmitted and derived from an ancient infection. Often, the same insects are hosts to ‘secondary’ bacterial symbionts which are maternally transmitted but relatively labile within host lineages. To explore the dynamics of secondary symbiont associations in aphids, we characterized bacteria infecting 15 species of macrosiphine aphids using DNA sequencing, diagnostic polymerase chain reaction (PCR), diagnostic restriction digests, phylogenetic analyses, and electron microscopy to examine aphids from nature and from laboratory colonies. Three types of bacteria besides Buchnera were found repeatedly; all three fall within the Enterobacteriaceae. The R‐type has a 16S rDNA less than 0.1% different from that of the secondary symbiont previously reported from Acyrthosiphon pisum and is related to Serratia species. The T‐type includes a symbiont previously reported from a whitefly; the U‐type comprises a new cluster near the T‐type. The T‐type was found in every one of 40 Uroleucon ambrosiae clones collected throughout the United States. In contrast, A. pisum individuals were infected by any combination of the three symbiont types. Secondary symbionts were maternally transmitted for 11 months within laboratory‐reared A. pisum clones and were present in sexually produced eggs. PCR screens for a bacteriophage, APSE‐1, indicated its presence in both A. pisum and U. ambrosiae containing secondary symbionts. Electron microscopy of R‐type and T‐type bacteria in A. pisum and in U. ambrosiae revealed rod‐shaped organisms that attain extremely high densities within a few bacteriocytes.

Evaluation of a New Commercial Immunoassay >for Rapid Detection of Campylobacter jejuni in Stool Samples - H. P. Endtz; C. W. Ang; N. van den Braak; A. Luijendijk; B. C. Jacobs; P. de Man; J.M. van Duin; A. van Belkum; H. A. Verbrugh (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Activity of Trovafloxacin, Alone and in Combination with Other Agents, Against Enterobacteriaceae by Time-Kill Analysis - C. L. Clark; L. M. Kelly; M. R. Jacobs; P. C. Appelbaum (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

Carriage of Antibiotic-Resistant Streptococcus pneumoniae in Greek Infants and Toddlers - G. A. Syrogiannopoulos; I. N. Grivea; G. D. Katopodis; P. Geslin; M. R. Jacobs; N. G. Beratis (European Journal of Clinical Microbiology & Infectious Diseases, 2000)

The major and a minor class II β-chain (B-LB ) gene flank the Tapasin gene in the B-F /B-L region of the chicken major histocompatibility complex - J. P. Jacob; S. Milne; S. Beck; J. Kaufman (Immunogenetics, 2000)

P-glycoprotein inhibition by glibenclamide and related compounds - P. E. Golstein; A. Boom; J. van Geffel; P. Jacobs; B. Masereel; R. Beauwens (Pflügers Archiv - European Journal of Physiology, 1999)

Effects of Eddy Variability on the Circulation of the Japan/East Sea - G. A. Jacobs; P. J. Hogan; K. R. Whitmer (Journal of Oceanography, 1999)

Diurnal and seasonal variation of carbon dioxide exchange from a former true raised bog - JOOST P. NIEVEEN; COR. M. J. JACOBS; ADRIE F. G. JACOBS (Global Change Biology, 1998)
Carbon dioxide exchange was measured, using the eddy covariance technique, during a one and a half year period in 1994 and 1995. The measurements took place over a former true raised bog, characterized by a shallow peat layer and a vegetation dominated by Molinia caerulea . The growing season extended from May until late October, with a maximum LAI in August of 1.7. The carbon balance shows a net release of 97 g C m –2 y –1 (265 kg C ha –1 y –1 ) from the peat bog ecosystem to the atmosphere. During June, July and August there is net consumption of CO 2 , while during the rest of the year there is net production of CO 2 . The average daytime assimilation rates ranged between – 0.2 and – 0.5 mg CO 2 m –2 s –1 (– 45 and –11.3 μmol CO 2 m –2 s –1 ), in a period where the LAI ranged between 1 and 1.7. A high vapour pressure deficit (> 15 hPa) corresponding with high temperatures was found to reduce the assimilation rate by on average 50%. Apart from these factors, LAI and the soil temperature codetermine the net exchange of CO 2 . The total nocturnal respiration during the growing season lies within the same order as the average daytime net assimilation rate. Temperature was found to be the main factor controlling soil respiration, with a Q 10 of 4.8.

A molecular basis for retinol stimulation of vesicle budding in vivo and in vitro - Dorothy M. Morré; Sui Wang; P.-J. Chueh; Juliana Lawler; Keri Safranski; Elizabeth Jacobs; D. James Morré (Molecular and Cellular Biochemistry, 1998)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)

Planktonic bacterial respiration as a function of C:N:P ratios across temperate lakes - André C. P. Cimbleris; Jacob Kalff (Hydrobiologia, 1998)

Genomic sequence of physalis mottle virus and its evolutionary relationship with other tymoviruses - C. T. Ranjith-Kumar; K. Gopinath; A. N. K. Jacob; V. Srividhya; P. Elango; H. S. Savithri (Archives of Virology, 1998)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

A study of females with deletions of the short arm of the X chromosome - Rowena S. James; Brian Coppin; Paola Dalton; Nicholas R. Dennis; Caroline Mitchell; Andrew J. Sharp; David H. Skuse; N. Simon Thomas; P. A. Jacobs (Human Genetics, 1998)

Clean catalytic technology for liquid phase hydrocarbon oxidation - G. Langhendries; D. E. De Vos; B. F. Sels; I. Vankelecom; P. A. Jacobs; G. V. Baron (Clean Technologies and Environmental Policy, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)

Temperature Behavior of a Natural Shallow Water Body during a Summer Period - A. F. G. Jacobs; B. G. Heusinkveld; J. P. Nieveen (Theoretical and Applied Climatology, 1998)

Interval mapping and congenic strains for a blood pressure QTL on rat Chromosome 13 - Q. Y. Zhang; H. Dene; A. Y. Deng; M. R. Garrett; H. J. Jacob; J. P. Rapp (Mammalian Genome, 1997)

Neuromuscular activation patterns during treadmill walking after space flight - Charles S. Layne; P. Vernon McDonald; Jacob J. Bloomberg (Experimental Brain Research, 1997)

Mate sampling behaviour of black grouse females ( Tetrao tetrix ) - Rauno V. Alatalo; Jacob Hglund; P. T. Rintamki; Arne Lundberg (Behavioral Ecology and Sociobiology, 1995)

Characterization of rabies glycoprotein expressed in yeast - Sharon R. Klepfer; Christine Debouck; J. Uffelman; P. Jacobs; A. Bollen; Elaine V. Jones (Archives of Virology, 1993)

Characterization of Orbiviruses of the Kemerovo serogroup: Isolations and serological comparisons - S. C. Jacobs; D. Carey; C. Chastel; T. G. Schwan; P. A. Nuttall (Archives of Virology, 1986)

National survey of elements and other constituents in municipal sewage sludges - Ralph O. Mumma; Dale C. Raupach; Joseph P. Waldman; Stephen S. C. Tong; M. Leroy Jacobs; John G. Babish; Joseph H. Hotchkiss; Patricia C. Wszolek; Walter H. Gutenman; Carl A. Bache; Donald J. Lisk (Archives of Environmental Contamination and Toxicology, 1984)

The genus Apodachlya - R. P. W. M. Jacobs (Antonie van Leeuwenhoek, 1982)

Pythiaceous fungi associated with the decomposition of Nymphoides peltata - R. P. W. M. Jacobs (Antonie van Leeuwenhoek, 1982)

In vivo and in vitro inhibition of cholinesterase by methyl-1 (S methyl phosphoryl-3) imidazolium (MSPI), a model of an ?instantly? aged phosphorylated enzyme - P. E. Chabrier; J. Jacob (Archives of Toxicology, 1980)

Chemical and immunological studies of liver microsomes from mouse mutants with ultrastructurally abnormal hepatic endoplasmic reticulum - Robert P. Erickson; Philip Siekevitz; Kenneth Jacobs; Salome Gluecksohn-Waelsch (Biochemical Genetics, 1974)

The influence of irrigation on the nitrogen, phosphorous and potash requirements of different potato varieties - W. C. Jacob; R. H. White-Stevens; P. H. Wessels (American Journal of Potato Research, 1949)